Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 89313335 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "TaxonKey is one of (Abies amabilis Douglas ex J.Forbes, Abies bracteata (D.Don) A.Poit., Abies concolor (Gordon) Lindl. ex Hildebr., Abies grandis (Douglas ex D.Don) Lindl., Abies lasiocarpa var. lasiocarpa, Abies magnifica A.Murray bis, Abies procera Rehd., Abronia alpina Brandegee, Abronia latifolia Eschsch., Abronia maritima Nutt. ex S.Watson, Abronia nana var. covillei (Heimerl) Munz, Abronia pogonantha Heimerl, Abronia turbinata Torr. ex S.Watson, Abronia umbellata Lam., Abronia umbellata var. breviflora (Standl.) L.A.Galloway, Abronia villosa S.Watson, Abronia villosa var. aurita (Abrams) Jeps., Abutilon palmeri A.Gray, Abutilon parvulum A.Gray, Abutilon theophrasti Medik., Acacia baileyana F.Muell., Acacia dealbata Link, Acacia decurrens Willd., Acacia longifolia (Andrews) Willd., Acacia mearnsii De Wild., Acacia melanoxylon R.Br., Acacia podalyriifolia A.Cunn. ex G.Don, Acacia redolens Maslin, Acacia retinodes Schltdl., Acacia saligna (Labill.) H.L.Wendl., Acacia verticillata (L'Her.) Willd., Acaena novae-zelandiae Kirk, Acaena pallida (Kirk) J.W.Dawson, Acaena pinnatifida var. californica (Bitter) Jeps., Acalypha californica Benth., Acamptopappus shockleyi A.Gray, Acamptopappus sphaerocephalus (Harv. & A.Gray) A.Gray, Acamptopappus sphaerocephalus var. hirtellus S.F.Blake, Acamptopappus sphaerocephalus var. sphaerocephalus, Acanthomintha duttonii (Abrams) Jokerst, Acanthomintha ilicifolia A.Gray, Acanthomintha lanceolata Curran, Acanthomintha obovata Jeps., Acer campestre L., Acer circinatum Pursh, Acer glabrum Torr., Acer glabrum var. diffusum (Greene) Smiley, Acer glabrum var. glabrum, Acer macrophyllum Pursh, Acer negundo L., Acer saccharinum L., Achillea millefolium L., Achlys californica Fukuda & Baker, Achyrachaena mollis S.Schauer, Achyronychia cooperi A.Gray, Acleisanthes longiflora A.Gray, Acourtia microcephala DC., Actaea rubra (Aiton) Willd., Adenocaulon bicolor Hook., Adenophyllum cooperi (A.Gray) Strother, Adenophyllum porophylloides (A.Gray) Strother, Adenostoma fasciculatum Hook. & Arn., Adenostoma fasciculatum var. obtusifolium S.Watson, Adenostoma sparsifolium Torr., Adiantum aleuticum (Rupr.) C.A.Paris, Adiantum capillus-veneris L., Adiantum jordanii Müll.Hal., Adiantum shastense Huiet & A.R.Sm., Adolphia californica S.Watson, Adonis aestivalis L., Aegilops cylindrica Host, Aegilops geniculata Roth, Aegilops triuncialis L., Aeonium arboreum subsp. arboreum, Aeonium haworthii Salm-Dyck ex Webb & Berthel., Aeschynomene rudis Benth., Aesculus californica (Spach) Nutt., Agastache parvifolia Eastw., Agastache urticifolia (Benth.) Kuntze, Agave deserti Engelm., Agave shawii subsp. shawii, Agave utahensis Engelm., Agave utahensis var. eborispina (Hester) Breitung, Agave utahensis var. nevadensis Engelm. ex Greenm. & Roush, Ageratina adenophora (Spreng.) R.M.King & H.Rob., Ageratina herbacea (A.Gray) R.M.King & H.Rob., Ageratina occidentalis (Hook.) R.M.King & H.Rob., Ageratina shastensis (Taylor & Stebbins) R.M.King & H.Rob., Agoseris apargioides (Less.) Greene, Agoseris apargioides var. apargioides, Agoseris apargioides var. eastwoodiae (Fedde) Munz, Agoseris apargioides var. maritima (E.Sheld.) Cronquist, Agoseris aurantiaca var. aurantiaca, Agoseris glauca var. glauca, Agoseris grandiflora (Nutt.) Greene, Agoseris grandiflora var. grandiflora, Agoseris grandiflora var. leptophylla G.I.Baird, Agoseris heterophylla (Nutt.) Greene, Agoseris heterophylla var. heterophylla, Agoseris retrorsa (Benth.) Greene, Agrimonia gryposepala Wallr., Agrimonia striata Michx., Agrostis blasdalei Hitchc., Agrostis capillaris L., Agrostis densiflora Vasey, Agrostis elliottiana Schult., Agrostis exarata Trin., Agrostis gigantea Roth, Agrostis hallii Vasey, Agrostis hendersonii Hitchc., Agrostis hooveri Swallen, Agrostis humilis Vasey, Agrostis idahoensis Nash, Agrostis lacuna-vernalis P.M.Peterson & Soreng, Agrostis microphylla Steud., Agrostis oregonensis Vasey, Agrostis pallens Trin., Agrostis scabra Willd., Agrostis stolonifera L., Agrostis tandilensis (Kuntze) Parodi, Agrostis variabilis Rydb., Ailanthus altissima (Mill.) Swingle, Aira caryophyllea L., Aira elegans Willd. ex Roem. & Schult., Aira praecox L., Albizia julibrissin Durazz., Alcea rosea L., Alhagi maurorum Medik., Aliciella hutchinsifolia (Rydb.) J.M.Porter, Aliciella lottiae (A.G.Day) J.M.Porter, Aliciella micromeria (A.Gray) J.M.Porter, Aliciella monoensis J.M.Porter & A.G.Day, Aliciella ripleyi (Barneby) J.M.Porter, Aliciella triodon (Eastw.) Brand, Alisma gramineum Lej., Alisma lanceolatum With., Alisma triviale Pursh, Allenrolfea occidentalis (S.Watson) Kuntze, Allionia incarnata f. incarnata, Allionia incarnata var. villosa (Standl.) Munz, Allium abramsii (Ownbey & Aase ex Traub) McNeal, Allium acuminatum Hook., Allium amplectens Torr., Allium anceps Kellogg, Allium atrorubens S.Watson, Allium atrorubens var. atrorubens, Allium atrorubens var. cristatum (S.Watson) McNeal, Allium bisceptrum S.Watson, Allium bolanderi S.Watson, Allium bolanderi var. bolanderi, Allium bolanderi var. mirabile (L.F.Hend.) McNeal, Allium burlewii Davidson, Allium campanulatum S.Watson, Allium cepa L., Allium cratericola Eastw., Allium crispum Greene, Allium diabolense (Ownbey & Aase ex Traub) McNeal, Allium dichlamydeum Greene, Allium falcifolium Hook. & Arn., Allium fimbriatum S.Watson, Allium fimbriatum var. fimbriatum, Allium fimbriatum var. mohavense Jeps., Allium fimbriatum var. purdyi (Eastw.) Ownbey ex McNeal, Allium haematochiton S.Watson, Allium hickmanii Eastw., Allium hoffmanii Ownbey ex Traub, Allium howellii Eastw., Allium howellii var. clokeyi Ownbey & Aase ex Traub, Allium howellii var. howellii, Allium howellii var. sanbenitense (Traub) Ownbey & Aase, Allium hyalinum Curran, Allium jepsonii (Ownbey & Aase ex Traub) S.S.Denison & McNeal, Allium lacunosum S.Watson, Allium lacunosum var. davisiae (M.E.Jones) McNeal & Ownbey, Allium lacunosum var. lacunosum, Allium lacunosum var. micranthum Eastw., Allium lemmonii S.Watson, Allium membranaceum Ownbey ex Traub, Allium monticola Davidson, Allium munzii (Ownbey & Aase ex Traub) McNeal, Allium neapolitanum Cirillo, Allium nevadense S.Watson, Allium obtusum Lemmon, Allium obtusum var. conspicuum Mortola & McNeal, Allium obtusum var. obtusum, Allium paniculatum subsp. paniculatum, Allium parishii S.Watson, Allium parvum Kellogg, Allium peninsulare Lemmon ex Greene, Allium peninsulare var. franciscanum McNeal & Ownbey, Allium peninsulare var. peninsulare, Allium platycaule S.Watson, Allium praecox Brandegee, Allium punctum L.F.Hend., Allium sanbornii Alph.Wood, Allium sanbornii var. congdonii Jeps., Allium sanbornii subsp. sanbornii, Allium sanbornii var. sanbornii, Allium sativum L., Allium serra McNeal & Ownbey, Allium sharsmithiae (Ownbey & Aase ex Traub) McNeal, Allium shevockii McNeal, Allium siskiyouense Ownbey ex Traub, Allium tolmiei var. tolmiei, Allium tribracteatum Torr., Allium triquetrum L., Allium tuolumnense (Ownbey & Aase ex Traub) S.S.Denison & McNeal, Allium unifolium Kellogg, Allium validum S.Watson, Allium vineale L., Allium yosemitense Eastw., Allophyllum divaricatum (Nutt.) A.D.Grant & V.E.Grant, Allophyllum gilioides (Benth.) A.D.Grant & V.E.Grant, Allophyllum glutinosum (Benth.) A.D.Grant & V.E.Grant, Allophyllum integrifolium (Brand) A.D.Grant & V.E.Grant, Allotropa virgata Torr. & A.Gray, Almutaster pauciflorus (Nutt.) Á.Löve & D.Löve, Alnus rhombifolia Nutt., Alnus rubra Bong., Alopecurus aequalis Sobol., Alopecurus aequalis subsp. aequalis, Alopecurus carolinianus Walter, Alopecurus geniculatus L., Alopecurus myosuroides Huds., Alopecurus pratensis L., Alopecurus saccatus Vasey, Aloysia wrightii A.Heller, Alternanthera caracasana Kunth, Alternanthera philoxeroides (Mart.) Griseb., Alyssum alyssoides (L.) L., Amaranthus albus L., Amaranthus arenicola I.M.Johnst., Amaranthus blitoides S.Watson, Amaranthus californicus (Moq.) S.Watson, Amaranthus caudatus L., Amaranthus cruentus L., Amaranthus deflexus L., Amaranthus fimbriatus (Torr.) Benth. ex S.Watson, Amaranthus hybridus L., Amaranthus hypochondriacus L., Amaranthus palmeri S.Watson, Amaranthus powellii S.Watson, Amaranthus retroflexus L., Amaranthus spinosus L., Amaranthus torreyi (A.Gray) Benth. ex S.Watson, Amaranthus viridis L., Amaranthus watsonii Standl., Amblyopappus pusillus Hook. & Arn., Ambrosia acanthicarpa Hook., Ambrosia ambrosioides (Cav.) W.W.Payne, Ambrosia artemisiifolia L., Ambrosia chamissonis (Less.) Greene, Ambrosia chenopodiifolia (Benth.) W.W.Payne, Ambrosia confertiflora DC., Ambrosia dumosa (A.Gray) W.W.Payne, Ambrosia eriocentra (A.Gray) W.W.Payne, Ambrosia ilicifolia (A.Gray) W.W.Payne, Ambrosia psilostachya DC., Ambrosia pumila (Nutt.) A.Gray, Ambrosia trifida L., Amelanchier alnifolia (Nutt.) Nutt., Amelanchier alnifolia var. semiintegrifolia (Hook.) C.L.Hitchc., Amelanchier utahensis Koehne, Ammannia coccinea Rottb., Ammannia robusta Heer ex Regel, Ammi majus L., Ammi visnaga Linnaeus, 1753, Ammophila arenaria (L.) Link, Amorpha californica Nutt., Amorpha californica var. californica, Amorpha californica var. napensis Jeps., Amorpha fruticosa L., Amphipappus fremontii var. fremontii, Amphipappus fremontii var. spinosus (A.Nelson) Ced.Porter, Amsinckia douglasiana A.DC., Amsinckia eastwoodiae J.F.Macbr., Amsinckia grandiflora (Kleeb. ex A.Gray) Kleeb. ex Greene, Amsinckia intermedia Fisch. & C.A.Mey., Amsinckia lunaris J.F.Macbr., Amsinckia lycopsoides Lehm., Amsinckia menziesii (Lehm.) A.Nelson & J.F.Macbr., Amsinckia spectabilis Fisch. & C.A.Mey., Amsinckia spectabilis var. spectabilis, Amsinckia tessellata A.Gray, Amsinckia vernicosa Hook. & Arn., Amsonia tomentosa Torr. & Frém., Anaphalis margaritacea (L.) Benth., Anchusa azurea Mill., Anchusa officinalis L., Ancistrocarphus filagineus A.Gray, Ancistrocarphus keilii Morefield, Andropogon virginicus var. virginicus, Androsace filiformis Retz., Androsace occidentalis Pursh, Androsace septentrionalis L., Androstephium breviflorum S.Watson, Anelsonia eurycarpa (A.Gray) J.F.Macbr. & Payson, Anemone lyallii Britton, Anemone multifida subsp. multifida, Anemone multifida var. multifida, Anemone tuberosa Rydb., Anemopsis californica (Nutt.) Hook. & Arn., Anethum graveolens L., Angelica arguta Nutt. ex Torr. & A.Gray, Angelica breweri A.Gray, Angelica californica Jeps., Angelica callii Mathias & Constance, Angelica genuflexa Nutt. ex Torr. & A.Gray, Angelica hendersonii J.M.Coult. & Rose, Angelica kingii (S.Watson) J.M.Coult. & Rose, Angelica lineariloba A.Gray, Angelica lucida L., Angelica tomentosa S.Watson, Anisocarpus madioides Nutt., Anisocarpus scabridus (Eastw.) B.G.Baldwin, Anisocoma acaulis Torr. & A.Gray, Anoda cristata (L.) Schltdl., Anoda pentaschista A.Gray, Anredera cordifolia (Ten.) Steenis, Antennaria argentea (A.Gray) Benth., Antennaria corymbosa E.E.Nelson, Antennaria dimorpha (Nutt.) Torr. & A.Gray, Antennaria flagellaris A.Gray, Antennaria geyeri A.Gray, Antennaria luzuloides Torr. & A.Gray, Antennaria marginata Greene, Antennaria media Greene, Antennaria microphylla Rydb., Antennaria pulchella Greene, Antennaria racemosa Hook., Antennaria rosea Greene, Antennaria sawyeri R.J.Bayer & Figura, Antennaria suffrutescens Greene, Antennaria umbrinella Rydb., Anthemis arvensis L., Anthemis cotula L., Anthoxanthum odoratum L., Anthriscus caucalis M.Bieb., Antirrhinum majus L., Anulocaulis annulatus (Coville) Standl., Apera interrupta (L.) P.Beauv., Apera spica-venti (L.) P.Beauv., Aphanisma blitoides Nutt. ex Moq., Apiastrum angustifolium Nutt., Apium graveolens L., Apium nodiflorum Linnaeus, 1753, Apocynum androsaemifolium L., Apocynum cannabinum L., Aponogeton distachyos L.f., Aquilegia eximia Van Houtte ex Planch., Aquilegia formosa Fisch., Aquilegia pubescens Coville, Arabidopsis thaliana (L.) Heynh., Arabis blepharophylla Hook. & Arn., Arabis eschscholtziana Andrz., Arabis mcdonaldiana Eastw., Arabis modesta Rollins, Arabis oregana Rollins, Aralia californica S.Watson, Araujia sericifera Brot., Arbutus menziesii Pursh, Arceuthobium americanum Nutt. ex A.Gray, Arceuthobium campylopodum A.Gray, Arceuthobium douglasii Engelm., Arctium lappa L., Arctium minus (Hill) Bernh., Arctomecon merriamii Coville, Arctostaphylos andersonii A.Gray, Arctostaphylos auriculata Eastw., Arctostaphylos bakeri Eastw., Arctostaphylos canescens Eastw., Arctostaphylos catalinae P.V.Wells, Arctostaphylos columbiana Piper, Arctostaphylos confertiflora Eastw., Arctostaphylos cruzensis Roof, Arctostaphylos densiflora M.S.Baker, Arctostaphylos edmundsii J.T.Howell, Arctostaphylos gabilanensis V.T.Parker & M.C.Vasey, Arctostaphylos glandulosa Eastw., Arctostaphylos glauca Lindl., Arctostaphylos glutinosa B.Schreib., Arctostaphylos hispidula J.T.Howell, Arctostaphylos hookeri G.Don, Arctostaphylos hooveri P.V.Wells, Arctostaphylos imbricata Eastw., Arctostaphylos insularis Greene & Parry, Arctostaphylos klamathensis S.W.Edwards, Keeler-Wolf & W.Knight, Arctostaphylos luciana P.V.Wells, Arctostaphylos malloryi (W.Knight & Gankin) P.V.Wells, Arctostaphylos manzanita Parry, Arctostaphylos mewukka Merriam, Arctostaphylos montaraensis Roof, Arctostaphylos montereyensis Hoover, Arctostaphylos morroensis Wiesl. & B.Schreib., Arctostaphylos myrtifolia Parry, Arctostaphylos nevadensis A.Gray, Arctostaphylos nissenana Merriam, Arctostaphylos nummularia A.Gray, Arctostaphylos obispoensis Eastw., Arctostaphylos ohloneana M.C.Vasey & V.T.Parker, Arctostaphylos osoensis P.V.Wells, Arctostaphylos otayensis Wiesl. & B.Schreib., Arctostaphylos pacifica Roof, Arctostaphylos pajaroensis (J.E.Adams ex Mc Minn) J.E.Adams, Arctostaphylos pallida Eastw., Arctostaphylos parryana Lemmon, Arctostaphylos patula Greene, Arctostaphylos pechoensis (Abrams) Dudley, Arctostaphylos pilosula Jeps. & Wiesl., Arctostaphylos pumila Nutt., Arctostaphylos pungens Kunth, Arctostaphylos purissima P.V.Wells, Arctostaphylos rainbowensis J.E.Keeley & Massihi, Arctostaphylos refugioensis Gankin, Arctostaphylos regismontana Eastw., Arctostaphylos rudis Jeps. & Wiesl., Arctostaphylos silvicola Jeps. & Wiesl., Arctostaphylos stanfordiana Parry, Arctostaphylos tomentosa (Pursh) Lindl., Arctostaphylos uva-ursi (L.) Spreng., Arctostaphylos virgata Eastw., Arctostaphylos viridissima (Eastw.) Mc Minn, Arctostaphylos viscida Parry, Arctotheca calendula (L.) Levyns, Arenaria lanuginosa var. saxosa (A.Gray) Zarucci, R.L.Hartman & Rabeler, Arenaria paludicola Rob., Arenaria serpyllifolia subsp. serpyllifolia, Argemone corymbosa Greene, Argemone munita Durand & Hilg., Argyrochosma jonesii (Maxon) Windham, Aristida adscensionis L., Aristida californica Thurb., Aristida dichotoma Michx., Aristida divaricata Humb. & Bonpl. ex Willd., Aristida oligantha Michx., Aristida purpurea Nutt., Aristocapsa insignis (Curran) Reveal & C.B.Hardham, Armoracia rusticana P.Gaertn., B.Mey. & Scherb., Arnica cernua Howell, Arnica chamissonis Less., Arnica cordifolia Hook., Arnica discoidea Benth., Arnica fulgens Pursh, Arnica latifolia Bong., Arnica longifolia D.C.Eaton, Arnica mollis Hook., Arnica nevadensis A.Gray, Arnica parryi A.Gray, Arnica sororia Greene, Arnica spathulata Greene, Arnica venosa H.M.Hall, Arnica viscosa A.Gray, Arrhenatherum elatius (L.) P.Beauv. ex J.Presl & C.Presl, Artemisia annua L., Artemisia arbuscula Nutt., Artemisia biennis Willd., Artemisia bigelovii A.Gray, Artemisia californica Less., Artemisia douglasiana Besser, Artemisia dracunculus L., Artemisia ludoviciana Nutt., Artemisia michauxiana Besser, Artemisia nesiotica P.H.Raven, Artemisia nova A.Nelson, Artemisia palmeri A.Gray, Artemisia pycnocephala (Less.) DC., Artemisia rothrockii A.Gray, Artemisia suksdorfii Piper, Artemisia tridentata (Nutt.) W.A.Weber, Arum italicum Mill., Aruncus dioicus var. acuminatus (Douglas ex Hook.) Rydb. ex H.Hara, Arundo donax L., Asarum caudatum Lindl., Asarum hartwegii S.Watson, Asarum lemmonii S.Watson, Asarum marmoratum Piper, Asclepias albicans S.Watson, Asclepias californica Greene, Asclepias cordifolia (Benth.) Jeps., Asclepias cryptoceras S.Watson, Asclepias curassavica L., Asclepias eriocarpa Benth., Asclepias erosa Torr., Asclepias fascicularis Decne., Asclepias latifolia (Torr.) Raf., Asclepias nyctaginifolia A.Gray, Asclepias solanoana Woodson, Asclepias speciosa Torr., Asclepias subulata Decne., Asclepias vestita Hook. & Arn., Asparagus aethiopicus L., Asparagus asparagoides (L.) Druce, Asparagus setaceus (Kunth) Jessop, Asperugo procumbens L., Asphodelus fistulosus L., Aspidotis californica (Nutt. ex Hook.) Nutt. ex Copel., Aspidotis carlotta-halliae (W.H.Wagner & E.F.Gilbert) Lellinger, Aspidotis densa (Brack.) Lellinger, Asplenium septentrionale (L.) Hoffm., Asplenium vespertinum Maxon, Asplenium viride Huds., Astragalus accidens var. hendersonii M.E.Jones, Astragalus acutirostris S.Watson, Astragalus agnicidus Barneby, Astragalus agrestis Douglas ex G.Don, Astragalus albens Greene, Astragalus andersonii A.Gray, Astragalus argophyllus var. argophyllus, Astragalus aridus A.Gray, Astragalus asymmetricus E.Sheld., Astragalus atratus var. mensanus M.E.Jones, Astragalus austiniae A.Gray ex W.H.Brewer & S.Watson, Astragalus bernardinus M.E.Jones, Astragalus bicristatus A.Gray, Astragalus bolanderi A.Gray, Astragalus brauntonii Parish, Astragalus breweri A.Gray, Astragalus californicus (A.Gray) Greene, Astragalus canadensis var. brevidens (Gand.) Barneby, Astragalus casei A.Gray, Astragalus cicer L., Astragalus cimae var. sufflatus Barneby, Astragalus claranus Jeps., Astragalus clevelandii Greene, Astragalus coccineus (Parry) Brandegee, Astragalus congdonii S.Watson, Astragalus crotalariae (Benth.) A.Gray, Astragalus curtipes A.Gray, Astragalus deanei (Rydb.) Barneby, Astragalus didymocarpus var. dispermus (A.Gray) Jeps., Astragalus didymocarpus var. milesianus (Rydb.) Jeps., Astragalus didymocarpus var. obispoensis (Rydb.) Jeps., Astragalus douglasii var. parishii (A.Gray) M.E.Jones, Astragalus douglasii var. perstrictus (Rydb.) Munz, Astragalus ertterae Barneby & Shevock, Astragalus filipes Torr. ex A.Gray, Astragalus funereus M.E.Jones, Astragalus gambelianus E.Sheld., Astragalus gibbsii Kellogg, Astragalus gilmanii Tidestr., Astragalus insularis var. harwoodii Munz & McBurney, Astragalus inversus M.E.Jones, Astragalus inyoensis E.Sheld., Astragalus jaegerianus Munz, Astragalus johannis-howellii Barneby, Astragalus kentrophyta subsp. danaus (Barneby) W.A.Weber, Astragalus kentrophyta subsp. elatus (S.Watson) W.A.Weber, Astragalus kentrophyta var. tegetarius (S.Watson) Dorn, Astragalus kentrophyta subsp. ungulatus (M.E.Jones) W.A.Weber, Astragalus layneae Greene, Astragalus lemmonii A.Gray, Astragalus lentiformis A.Gray, Astragalus lentiginosus var. albifolius M.E.Jones, Astragalus lentiginosus var. antonius Barneby, Astragalus lentiginosus var. borreganus M.E.Jones, Astragalus lentiginosus var. chartaceus M.E.Jones, Astragalus lentiginosus var. coachellae Shreve & Wiggins, Astragalus lentiginosus var. floribundus A.Gray, Astragalus lentiginosus var. fremontii (A.Gray ex Torr.) S.Watson, Astragalus lentiginosus var. idriensis M.E.Jones, Astragalus lentiginosus var. ineptus (A.Gray) M.E.Jones, Astragalus lentiginosus var. kernensis (Jeps.) Barneby, Astragalus lentiginosus var. lentiginosus, Astragalus lentiginosus var. micans Barneby, Astragalus lentiginosus var. nigricalycis M.E.Jones, Astragalus lentiginosus var. piscinensis Barneby, Astragalus lentiginosus var. salinus (Howell) Barneby, Astragalus lentiginosus var. semotus Jeps., Astragalus lentiginosus var. sesquimetralis (Rydb.) Barneby, Astragalus lentiginosus var. sierrae M.E.Jones, Astragalus lentiginosus var. variabilis Barneby, Astragalus leucolobus Parry ex M.E.Jones, Astragalus macrodon (Hook. & Arn.) A.Gray, Astragalus magdalenae var. peirsonii (Munz & McBurney) Barneby, Astragalus malacus A.Gray, Astragalus miguelensis Greene, Astragalus minthorniae var. villosus Barneby, Astragalus mohavensis var. hemigyrus (Clokey) Barneby, Astragalus monoensis Barneby, Astragalus nevinii A.Gray ex Lyon, Astragalus nutans M.E.Jones, Astragalus nuttallianus var. austrinus (Small) Barneby, Astragalus nuttallianus var. cedrosensis M.E.Jones, Astragalus nuttallianus var. imperfectus (Rydb.) Barneby, Astragalus nuttallii var. virgatus (A.Gray) Barneby, Astragalus obscurus S.Watson, Astragalus oocarpus A.Gray, Astragalus oophorus S.Watson, Astragalus oophorus var. lavinii Barneby, Astragalus oxyphysus A.Gray, Astragalus pachypus var. jaegeri Munz, Astragalus palmeri A.Gray, Astragalus panamintensis E.Sheld. ex Coult., Astragalus pauperculus Greene, Astragalus platytropis A.Gray, Astragalus pomonensis M.E.Jones, Astragalus preussii var. laxiflorus A.Gray, Astragalus pulsiferae var. coronensis S.L.Welsh, Ondricek & G.Clifton, Astragalus pulsiferae var. suksdorfii (J.T.Howell) Barneby, Astragalus purshii var. lagopinus (Rydb.) Barneby, Astragalus purshii var. lectulus (S.Watson) M.E.Jones, Astragalus purshii var. purshii, Astragalus purshii var. tinctus M.E.Jones, Astragalus pycnostachyus var. lanosissimus (Rydb.) Munz, Astragalus rattanii var. jepsonianus Barneby, Astragalus ravenii Barneby, Astragalus sabulonum A.Gray, Astragalus sepultipes (Barneby) Barneby, Astragalus serenoi var. shockleyi (M.E.Jones) Barneby, Astragalus shevockii Barneby, Astragalus subvestitus (Jeps.) Barneby, Astragalus tener var. ferrisiae Liston, Astragalus tener var. titi (Eastw.) Barneby, Astragalus tephrodes var. brachylobus (A.Gray) Barneby, Astragalus tidestromii (Rydb.) Clokey, Astragalus traskiae Eastw., Astragalus tricarinatus A.Gray, Astragalus trichopodus var. lonchus (M.E.Jones) Barneby, Astragalus umbraticus E.Sheld., Astragalus webberi A.Gray, Astragalus whitneyi var. confusus Barneby, Astragalus whitneyi var. lenophyllus (Rydb.) Barneby, Astragalus whitneyi var. siskiyouensis (Rydb.) Barneby, Astrolepis cochisensis (Goodd.) D.M.Benham & Windham, Athysanus pusillus (Hook.) Greene, Athysanus unilateralis (M.E.Jones) Jeps., Atrichoseris platyphylla (A.Gray) A.Gray, Atriplex argentea Nutt., Atriplex argentea var. argentea, Atriplex canescens (Pursh) Nutt., Atriplex canescens var. canescens, Atriplex confertifolia (Torr. & Frém.) S.Watson, Atriplex cordulata Jeps., Atriplex coronata S.Watson, Atriplex coronata var. notatior Jeps., Atriplex coulteri (Moq.) D.Dietr., Atriplex depressa Jeps., Atriplex elegans (Moq.) D.Dietr., Atriplex elegans var. fasciculata (S.Watson) M.E.Jones, Atriplex fruticulosa Jeps., Atriplex gmelinii var. gmelinii, Atriplex hortensis L., Atriplex hymenelytra (Torr.) S.Watson, Atriplex lentiformis (Torr.) S.Watson, Atriplex leucophylla (Moq.) D.Dietr., Atriplex lindleyi Moq., Atriplex minuscula Standl., Atriplex nummularia Lindl., Atriplex pacifica A.Nelson, Atriplex parishii S.Watson, Atriplex parryi S.Watson, Atriplex patula L., Atriplex persistens Stutz & G.L.Chu, Atriplex polycarpa (Torr.) S.Watson, Atriplex prostrata DC., Atriplex pusilla (Torr.) S.Watson, Atriplex rosea L., Atriplex semibaccata R.Br., Atriplex serenana A.Nelson ex Abrams, Atriplex serenana var. davidsonii (Standl.) Munz, Atriplex spinifera J.F.Macbr., Atriplex suberecta I.Verd., Atriplex subtilis Stutz & G.L.Chu, Atriplex truncata (Torr.) Gray, Atriplex tularensis Coville, Atriplex watsonii A.Nelson ex Abrams, Aubrieta deltoidea (L.) DC., Avena barbata Pott ex Link, Avena fatua L., Avena sativa L., Avena sterilis L., Ayenia compacta Rose, Azolla filiculoides Lam., Baccharis brachyphylla A.Gray, Baccharis malibuensis R.M.Beauch. & Henrickson, Baccharis pilularis DC., Baccharis plummerae (A.Gray) F.H.Hellw., Baccharis salicina Torr. & A.Gray, Baccharis sarothroides A.Gray, Baccharis sergiloides A.Gray, Baccharis vanessae R.M.Beauch., Bacopa eisenii (Kellogg) Pennell, Bacopa monnieri (L.) Pennell, Bacopa repens (Sw.) Wettst., Bacopa rotundifolia (Michx.) Wettst., Baileya multiradiata Harv. & A.Gray ex Torr., Baileya pauciradiata Harv. & A.Gray ex A.Gray, Baileya pleniradiata Harv. & A.Gray, Balsamorhiza deltoidea Nutt., Balsamorhiza hookeri (Hook.) Nutt., Balsamorhiza lanata (W.M.Sharp) W.A.Weber, Balsamorhiza macrolepis Sharp, Balsamorhiza sagittata (Pursh) Nutt., Balsamorhiza sericea W.A.Weber, Balsamorhiza serrata A.Nelson & J.F.Macbr., Barbarea orthoceras Ledeb., Barbarea verna (Mill.) Asch., Barbarea vulgaris (L.) W.T.Aiton, Bassia hyssopifolia (Pall.) Kuntze, Batis maritima L., Bebbia juncea var. aspera Greene, Beckmannia syzigachne (Steud.) Fernald, Bellardia trixago (L.) All., Bellis perennis L., Benitoa occidentalis (H.M.Hall) D.D.Keck, Bensoniella oregona (Abrams & Bacig.) Morton, Berberis darwinii Hook., Berberis vulgaris L., Bergerocactus emoryi (Engelm.) Britton & Rose, Bergia texana (Hook.) Seub. ex Walp., Bernardia incana C.V.Morton, 1939, Berteroa incana (L.) DC., Berula erecta (Huds.) Coville, Betula glandulosa Michx., Betula occidentalis Hook., Bidens cernua L., Bidens frondosa L., Bidens laevis (L.) Britton, Sterns & Poggenb., Bidens pilosa L., Bidens tripartita L., Bidens vulgata Greene, Bituminaria bituminosa (L.) C.H.Stirt., Blennosperma bakeri Heiser, Blennosperma nanum (Hook.) S.F.Blake, Blennosperma nanum var. nanum, Blennosperma nanum var. robustum J.T.Howell, Blepharidachne kingii (S.Watson) Hack., Blepharipappus scaber Hook., Blepharizonia plumosa (Kellogg) Greene, Bloomeria crocea (Torr.) Coville, Bloomeria crocea var. aurea (Kellogg) Ingram, Bloomeria crocea var. crocea, Bloomeria crocea var. montana (Greene) Ingram, Bloomeria humilis Hoover, Boechera covillei (Greene) Windham & Al-Shehbaz, Boechera divaricarpa (A.Nelson) A.Löve & D.Löve, Boechera evadens Windham & Al-Shehbaz, Boechera pauciflora (Nutt.) Windham & Al-Shehbaz, Boechera rubicundula (Jepson) Windham, Al-Shehbaz & P.Alexander, Boechera serpenticola Windham & Al-Shehbaz, Boechera shevockii Windham & Al-Shehbaz, Boechera tularensis Windham & Al-Shehbaz, Boechera yorkii S.Boyd, Boehmeria cylindrica (L.) Sw., Boerhavia coccinea Mill., Boerhavia coulteri (Hook.fil.) S.Watson, Boerhavia coulteri var. palmeri (S.Watson) Spellenb., Boerhavia diffusa L., Boerhavia wrightii A.Gray, Bolandra californica A.Gray, Bolboschoenus glaucus (Lam.) S.G.Sm., Borago officinalis L., Bothriochloa barbinodis (Lag.) Herter, Bothriochloa ischaemum (L.) Keng, Botrychium ascendens W.H.Wagner, Botrychium crenulatum W.H.Wagner, Botrychium lineare W.H.Wagner, Botrychium lunaria (L.) Sw., Botrychium minganense Vict., Botrychium montanum W.H.Wagner, Botrychium paradoxum W.H.Wagner, Botrychium pinnatum H.St.John, Botrychium pumicola Coville, Botrychium simplex E.Hitchc., Botrychium tunux Stensvold & Farrar, Botrychium yaaxudakeit Stensvold & Farrar, Bouteloua curtipendula (Michx.) Torr., Bouteloua eriopoda (Torr.) Torr., Bouteloua gracilis (Kunth) Lag. ex Griffiths, Bouteloua trifida Thurb. ex S.Watson, Bowlesia incana Ruiz & Pav., Boykinia major A.Gray, Boykinia occidentalis Torr. & A.Gray, Boykinia rotundifolia Parry ex A.Gray, Brachypodium distachyon (L.) P.Beauv., Brachypodium pinnatum (L.) P.Beauv., Brachypodium sylvaticum (Huds.) P.Beauv., Brasenia schreberi J.F.Gmel., Brassica fruticulosa Cirillo, Brassica juncea (L.) Czern., Brassica napus L., Brassica nigra (L.) W.D.J.Koch, Brassica oleracea L., Brassica rapa L., Brassica tournefortii Gouan, Brickellia atractyloides A.Gray, Brickellia atractyloides var. arguta (B.L.Rob.) Jeps., Brickellia atractyloides var. atractyloides, Brickellia californica (Torr. & A.Gray) A.Gray, Brickellia frutescens A.Gray, Brickellia grandiflora (Hook.) Nutt., Brickellia greenei A.Gray, Brickellia incana A.Gray, Brickellia knappiana Drew, Brickellia longifolia S.Watson, Brickellia microphylla (Nutt.) A.Gray, Brickellia microphylla var. microphylla, Brickellia microphylla var. scabra A.Gray, Brickellia nevinii A.Gray, Brickellia oblongifolia var. linifolia (D.C.Eaton) B.L.Rob., Briza maxima L., Briza minor L., Brodiaea appendiculata Hoover, Brodiaea californica Lindl. ex Lem., Brodiaea coronaria (Salisb.) Jeps., Brodiaea filifolia S.Watson, Brodiaea insignis (Jeps.) Niehaus, Brodiaea jolonensis Eastw., Brodiaea kinkiensis Niehaus, Brodiaea matsonii R.E.Preston, Brodiaea minor (Benth.) S.Watson, Brodiaea orcuttii (Greene) Baker, Brodiaea pallida Hoover, Brodiaea santarosae T.J.Chester, W.P.Armstr. & Madore, Brodiaea sierrae R.E.Preston, Brodiaea stellaris S.Watson, Brodiaea terrestris Kellogg, Bromus arenarius Labill., Bromus arizonicus (Shear) Stebbins, Bromus arvensis L., Bromus briziformis Fisch. & C.A.Mey., Bromus catharticus Vahl, Bromus ciliatus L., Bromus commutatus Schrad., Bromus diandrus Roth, Bromus grandis (Shear) Hitchc., Bromus hordeaceus L., Bromus inermis Leyss., Bromus japonicus Houtt., Bromus laevipes Shear, Bromus madritensis L., Bromus orcuttianus Vasey, Bromus porteri (Coult.) Nash, Bromus pseudolaevipes Wagnon, Bromus racemosus L., Bromus rubens L., Bromus secalinus L., Bromus sitchensis Trin., Bromus sitchensis var. sitchensis, Bromus sterilis L., Bromus suksdorfii Vasey, Bromus tectorum L., Bromus vulgaris (Hook.) Shear, Buddleja davidii Franch., Buddleja saligna Willd., Buddleja utahensis Coville, Bulbostylis capillaris (L.) Kunth ex C.B.Clarke, Bursera microphylla A.Gray, Cabomba caroliniana A.Gray, Cacaliopsis nardosmia (A.Gray) A.Gray, Cakile edentula (Bigelow) Hook., Cakile maritima Scop., Calamagrostis bolanderi Thurb., Calamagrostis breweri Thurb., Calamagrostis canadensis (Michx.) P.Beauv., Calamagrostis canadensis subsp. canadensis, Calamagrostis foliosa Kearney, Calamagrostis koelerioides Vasey, Calamagrostis muiriana B.L.Wilson & Sami Gray, Calamagrostis nutkaensis (J.Presl) Steud., Calamagrostis ophitidis (J.T.Howell) Nygren, Calamagrostis purpurascens R.Br., Calamagrostis rubescens Buckley, Calamagrostis stricta (Timm) Koeler, Calandrinia breweri S.Watson, Calendula arvensis L., Calendula officinalis L., California macrophylla (Hook. & Arn.) Aldasoro, C.Navarro, P.Vargas, L.Sáez & Aedo, Calliandra eriophylla Benth., Callitriche fassettii Schotsman, Callitriche heterophylla Pursh, Callitriche longipedunculata Morong, Callitriche marginata Torr., Callitriche palustris L., Callitriche stagnalis Scop., Callitriche trochlearis Fassett, Calocedrus decurrens (Torr.) Florin, Calochortus albus (Benth.) Douglas ex Benth., Calochortus amabilis Purdy, Calochortus amoenus Greene, Calochortus argillosus (Hoover) Zebzll & Fielder, Calochortus bruneaunis A.Nelson & J.F.Macbr., Calochortus catalinae S.Watson, Calochortus clavatus S.Watson, Calochortus clavatus var. avius Jeps., Calochortus clavatus var. clavatus, Calochortus clavatus var. gracilis Ownbey, Calochortus clavatus var. pallidus (Hoover) P.L.Fiedl. & Zebell, Calochortus clavatus var. recurvifolius (Hoover) P.L.Fiedl. & Zebell, Calochortus coeruleus (Kellogg) S.Watson, Calochortus concolor (Baker) Purdy & L.H.Bailey, Calochortus dunnii Purdy, Calochortus elegans Pursh, Calochortus excavatus Greene, Calochortus flexuosus S.Watson, Calochortus greenei S.Watson, Calochortus invenustus Greene, Calochortus kennedyi Porter, Calochortus kennedyi var. kennedyi, Calochortus kennedyi var. munzii Jeps., Calochortus leichtlinii Hook.f., Calochortus longebarbatus var. longebarbatus, Calochortus luteus Douglas ex Lindl., Calochortus macrocarpus Douglas, Calochortus minimus Ownbey, Calochortus monanthus Ownbey, Calochortus monophyllus (Lindl.) Lem., Calochortus nudus S.Watson, Calochortus obispoensis Lemmon, Calochortus palmeri S.Watson, Calochortus palmeri var. munzii Ownbey, Calochortus palmeri var. palmeri, Calochortus panamintensis (Ownbey) Reveal, Calochortus persistens Ownbey, Calochortus plummerae Greene, Calochortus pulchellus (Benth.) Alph.Wood, Calochortus raichei Farwig & V.Girard, Calochortus simulans (Hoover) Munz, Calochortus splendens Douglas ex Benth., Calochortus striatus Parish, Calochortus superbus Purdy ex Howell, Calochortus syntrophus Callahan, Calochortus tiburonensis A.J.Hill, Calochortus tolmiei Hook. & Arn., Calochortus umbellatus Alph.Wood, Calochortus uniflorus Hook. & Arn., Calochortus venustus Douglas ex Benth., Calochortus vestae (Purdy) Wallace, Calochortus weedii Alph.Wood, Calochortus weedii var. intermedius Ownbey, Calochortus weedii var. weedii, Calochortus westonii Eastw., Caltha leptosepala DC., Caltha palustris L., Calycadenia fremontii A.Gray, Calycadenia hooveri G.D.Carr, Calycadenia micrantha R.L.Carr & G.D.Carr, Calycadenia mollis A.Gray, Calycadenia multiglandulosa DC., Calycadenia oppositifolia (Greene) Greene, Calycadenia pauciflora A.Gray, Calycadenia spicata (Greene) Greene, Calycadenia truncata DC., Calycadenia villosa DC., Calycanthus occidentalis Hook. & Arn., Calycoseris parryi A.Gray, Calycoseris wrightii A.Gray, Calypso bulbosa var. occidentalis (Holz.) Cockerell, Calystegia collina (Greene) Brummitt, Calystegia longipes (S.Watson) Brummitt, Calystegia macrostegia (Greene) Brummitt, Calystegia malacophylla (Greene) Munz, Calystegia occidentalis (A.Gray) Brummitt, Calystegia peirsonii (Abrams) Brummitt, Calystegia purpurata (Greene) Brummitt, Calystegia sepium (L.) R.Br., Calystegia soldanella (L.) R.Br., Calystegia stebbinsii Brummitt, Calystegia subacaulis Hook. & Arn., Camelina microcarpa Andrz. ex DC., Camissonia benitensis P.H.Raven, Camissonia campestris (Greene) P.H.Raven, Camissonia contorta (Douglas) Kearney, Camissonia integrifolia P.H.Raven, Camissonia kernensis (Munz) P.H.Raven, Camissonia lacustris P.H.Raven, Camissonia parvula (Nutt. ex Torr. & A.Gray) Raven, Camissonia pubens (S.Watson) P.H.Raven, Camissonia pusilla P.H.Raven, Camissonia sierrae P.H.Raven, Camissonia strigulosa (Fisch. & C.A.Mey.) P.H.Raven, Campanula angustiflora Eastw., Campanula californica (Kellogg) A.Heller, Campanula exigua Rattan, Campanula griffinii Morin, Campanula rotundifolia L., Campanula scabrella Engelm., Campanula scouleri Hook. ex A.DC., Campanula sharsmithiae Morin, Campanula shetleri Heckard, Campanula wilkinsiana Greene, Campsis radicans (L.) Seem., Canbya candida Parry ex A.Gray, Cannabis sativa L., Capsella bursa-pastoris (L.) Medik., Cardamine angulata Hook., Cardamine bellidifolia L., Cardamine breweri S.Watson, Cardamine californica (Nutt.) Greene, Cardamine cordifolia A.Gray, Cardamine hirsuta L., Cardamine nuttallii Greene, Cardamine occidentalis (S.Watson) T.J.Howell, Cardamine oligosperma Nutt., Cardamine pachystigma (S.Watson) Rollins, Cardamine pensylvanica Muhl., Carduus nutans L., Carduus tenuiflorus Curtis, Carex abrupta Mack., Carex alma L.H.Bailey, Carex amplifolia Boott, Carex angustata Boott, Carex aquatilis Wahlenb., Carex aquatilis var. aquatilis, Carex aquatilis var. dives (Holm) Kük., Carex arcta Boott, Carex atherodes Spreng., Carex athrostachya Olney, Carex aurea Nutt., Carex barbarae Dewey, Carex bolanderi Olney, Carex brainerdii Mack., Carex brevicaulis Thouars, Carex breweri Boott, Carex buxbaumii Wahlenb., Carex californica L.H.Bailey, Carex capitata Sol., Carex comosa Boott, Carex concinnoides Mack., Carex congdonii L.H.Bailey, Carex cusickii Mack., Carex cyrtostachya Janeway & Zika, Carex davyi Mack., Carex deflexa var. boottii L.H.Bailey, Carex densa (L.H.Bailey) L.H.Bailey, Carex diandra Schrank, Carex disperma Dewey, Carex douglasii Boott, Carex duriuscula C.A.Mey., Carex echinata Murray, Carex exsiccata L.H.Bailey, Carex feta L.H.Bailey, Carex filifolia Nutt., Carex fissuricola Mack., Carex fracta Mack., Carex geyeri Boott, Carex globosa Boott, Carex gracilior Mack., Carex gynodynama Olney, Carex halliana L.H.Bailey, Carex harfordii Mack., Carex hassei L.H.Bailey, Carex haydeniana Olney, Carex helleri Mack., Carex hendersonii L.H.Bailey, Carex heteroneura S.Watson, Carex hirtissima W.Boott, Carex hoodii Boott, Carex hystericina Muhl. ex Willd., Carex idahoa L.H.Bailey, Carex illota L.H.Bailey, Carex incurviformis Mack., Carex infirminervia Naczi, Carex integra Mack., Carex interior L.H.Bailey, Carex jonesii L.H.Bailey, Carex klamathensis B.L.Wilson & Janeway, Carex laeviculmis Meinsh., Carex lasiocarpa Ehrh., Carex leavenworthii Dewey, Carex lemmonii W.Boott, Carex lenticularis Michx., Carex leporina L., Carex leporinella Mack., Carex leptalea Wahlenb., Carex leptopoda Mack., Carex limosa L., Carex livida (Wahlenb.) Willd., Carex longii Mack., Carex luzulifolia W.Boott, Carex luzulina Olney, Carex lyngbyei Hornem., Carex mariposana L.H.Bailey ex Mack., Carex mendocinensis Olney ex Boott, Carex mertensii J.D.Prescott ex Bong., Carex microptera Mack., Carex multicaulis L.H.Bailey, Carex multicostata Mack., Carex nebrascensis Dewey, Carex nervina L.H.Bailey, Carex neurophora Mack., Carex nigricans C.A.Mey., Carex nudata W.Boott, Carex obispoensis Stacey, Carex obnupta L.H.Bailey, Carex occidentalis L.H.Bailey, Carex pachystachya Cham. ex Steud., Carex pansa L.H.Bailey, Carex pellita Muhl. ex Willd., Carex pendula Huds., Carex petasata Dewey, Carex phaeocephala Piper, Carex praeceptorum Mack., Carex praegracilis W.Boott, Carex praticola Rydb., Carex preslii Steud., Carex proposita Mack., Carex raynoldsii Dewey, Carex rossii Boott, Carex sartwelliana Olney, Carex scabriuscula Mack., Carex schottii Dewey, Carex scopulorum var. bracteosa (L.H.Bailey) F.J.Herm., Carex senta Boott, Carex serpenticola Zika, Carex serratodens S.Watson, Carex sheldonii Mack., Carex simulata Mack., Carex specifica L.H.Bailey, Carex spectabilis Dewey, Carex spissa L.H.Bailey ex Hemsl., Carex stipata var. stipata, Carex straminiformis L.H.Bailey, Carex subbracteata Mack., Carex subfusca W.Boott, Carex subnigricans Stacey, Carex tahoensis Smiley, Carex texensis (Torr. ex L.H.Bailey) L.H.Bailey, Carex tompkinsii J.T.Howell, Carex triquetra Boott, Carex tumulicola Mack., Carex unilateralis Mack., Carex utriculata Boott, Carex vallicola Dewey, Carex vernacula L.H.Bailey, Carex vesicaria L., Carex vulpinoidea Michx., Carex whitneyi Olney, Carex xerophila Janeway & Zika, Carlowrightia arizonica A.Gray, Carnegiea gigantea (Engelm.) Britton & Rose, Carpenteria californica Torr., Carpobrotus chilensis (Molina) N.E.Br., Carpobrotus edulis (L.) N.E.Br., Carrichtera annua (L.) DC., Carthamus lanatus L., Carthamus leucocaulos Sibth. & Sm., Carthamus tinctorius L., Carya illinoinensis (Wangenh.) K.Koch, Cascadia nuttallii (Small) A.M.Johnson, Cassiope mertensiana (Bong.) D.Don, Castilleja affinis Hook. & Arn., Castilleja ambigua Hook. & Arn., Castilleja applegatei Fernald, Castilleja arachnoidea Greenm., Castilleja attenuata (A.Gray) T.I.Chuang & Heckard, Castilleja brevistyla (Hoover) T.I.Chuang & Heckard, Castilleja campestris (Benth.) T.I.Chuang & Heckard, Castilleja cinerea A.Gray, Castilleja densiflora (Benth.) T.I.Chuang & Heckard, Castilleja exserta (A.Heller) T.I.Chuang & Heckard, Castilleja foliolosa Hook. & Arn., Castilleja grisea Dunkle, Castilleja lacera (Benth.) T.I.Chuang & Heckard, Castilleja lasiorhyncha (A.Gray) T.I.Chuang & Heckard, Castilleja latifolia Hook. & Arn., Castilleja lemmonii A.Gray, Castilleja linariifolia Benth., Castilleja mendocinensis (Eastw.) Pennell, Castilleja miniata Douglas, Castilleja minor (A.Gray) A.Gray, Castilleja mollis Pennell, Castilleja montigena Heckard, Castilleja nana Eastw., Castilleja pilosa (S.Watson) Rydb., Castilleja plagiotoma A.Gray, Castilleja praeterita Heckard & Bacig., Castilleja pruinosa Fernald, Castilleja rubicundula (Jeps.) T.I.Chuang & Heckard, Castilleja schizotricha Greenm., Castilleja subinclusa Greene, Castilleja tenuis (A.Heller) T.I.Chuang & Heckard, Catalpa bignonioides Walter, Catalpa speciosa (Warder ex Barney) Warder ex Engelm., Catharanthus roseus (L.) G.Don, Ceanothus arboreus Greene, Ceanothus cordulatus Kellogg, Ceanothus crassifolius Torr., Ceanothus cuneatus (Hook.) Nutt., Ceanothus cuneatus var. fascicularis (Mc Minn) Hoover, Ceanothus cyaneus Eastw., Ceanothus decornutus V.T.Parker, Ceanothus dentatus Torr. & A.Gray, Ceanothus divergens Parry, Ceanothus diversifolius Kellogg, Ceanothus ferrisiae Mc Minn, Ceanothus foliosus Parry, Ceanothus foliosus var. medius Mc Minn, Ceanothus foliosus var. vineatus Mc Minn, Ceanothus fresnensis Dudley ex Abrams, Ceanothus gloriosus Howell, Ceanothus gloriosus var. exaltatus J.T.Howell, Ceanothus gloriosus var. porrectus J.T.Howell, Ceanothus hearstiorum Hoover & Roof, Ceanothus impressus Trel., Ceanothus impressus var. nipomensis Mc Minn, Ceanothus incanus Torr. & A.Gray, Ceanothus integerrimus Hook. & Arn., Ceanothus jepsonii Greene, Ceanothus lemmonii Parry, Ceanothus leucodermis Greene, Ceanothus maritimus Hoover, Ceanothus masonii Mc Minn, Ceanothus megacarpus Nutt., Ceanothus megacarpus var. insularis (Eastw.) Munz, Ceanothus oliganthus Nutt., Ceanothus ophiochilus S.Boyd, T.S.Ross & Arnseth, Ceanothus ×otayensis Mc Minn, Ceanothus palmeri Trel., Ceanothus papillosus Torr. & A.Gray, Ceanothus parryi Trel., Ceanothus parvifolius (S.Watson) Trel., Ceanothus pinetorum Coult., Ceanothus prostratus Benth., Ceanothus pumilus Greene, Ceanothus purpureus Jeps., Ceanothus roderickii W.Knight, Ceanothus sanguineus Pursh, Ceanothus sonomensis Howell, Ceanothus spinosus Nutt., Ceanothus thyrsiflorus Eschw., Ceanothus tomentosus Parry, Ceanothus velutinus Douglas, Ceanothus verrucosus Nutt., Celtis reticulata Boorsma, 1907, Cenchrus echinatus L., Cenchrus longispinus (Hack.) Fernald, Centaurea calcitrapa L., Centaurea cineraria L., Centaurea cyanus L., Centaurea diffusa Lam., Centaurea diluta Aiton, Centaurea iberica Trevis. ex Spreng., Centaurea jacea L., Centaurea melitensis L., Centaurea solstitialis L., Centaurea sulphurea Willd., Centaurium erythraea Rafn, Centaurium pulchellum (Sw.) Druce, Centranthus ruber (L.) DC., Centrostegia thurberi A.Gray ex Benth., Cephalanthera austiniae (A.Gray) A.Heller, Cephalanthus occidentalis L., Cerastium beeringianum Cham. & Schltdl., Cerastium dichotomum L., Cerastium diffusum Pers., Cerastium glomeratum Thuill., Ceratophyllum demersum L., Cercocarpus ledifolius Nutt., Cercocarpus traskiae Eastw., Cestrum nocturnum L., Cestrum parqui (Lam.) L'Hér., Chaenactis alpigena Sharsm., Chaenactis artemisiifolia (Harv. & A.Gray) A.Gray, Chaenactis carphoclinia A.Gray, Chaenactis carphoclinia var. carphoclinia, Chaenactis carphoclinia var. peirsonii (Jeps.) Munz, Chaenactis douglasii (Hook.) Hook. & Arn., Chaenactis douglasii var. alpina A.Gray, Chaenactis douglasii var. douglasii, Chaenactis fremontii A.Gray, Chaenactis glabriuscula DC., Chaenactis glabriuscula var. glabriuscula, Chaenactis glabriuscula var. heterocarpha (Torr. & A.Gray) H.M.Hall, Chaenactis glabriuscula var. lanosa (DC.) H.M.Hall, Chaenactis glabriuscula var. megacephala A.Gray, Chaenactis glabriuscula var. orcuttiana (Greene) H.M.Hall, Chaenactis macrantha D.C.Eaton, Chaenactis nevadensis (Kellogg) A.Gray, Chaenactis parishii A.Gray, Chaenactis santolinoides Greene, Chaenactis stevioides Hook. & Arn., Chaenactis suffrutescens A.Gray, Chaenactis xantiana A.Gray, Chaetadelpha wheeleri A.Gray, Chaetopappa ericoides (Torr.) G.L.Nesom, Chamaebatia australis (Brandegee) Abrams, Chamaebatia foliolosa Benth., Chamaebatiaria millefolium (Torr.) Maxim., Chamaecyparis lawsoniana (A.Murray bis) Parl., Chamaemelum fuscatum (Gren. & Godr.) Vasc., Chamaesaracha coronopus (Dunal) A.Gray, Chenopodium album L., Chenopodium atrovirens Rydb., Chenopodium berlandieri Moq., Chenopodium berlandieri var. sinuatum (Murr) Wahl, Chenopodium berlandieri var. zschackei (Murr) Murr, Chenopodium capitatum Linnaeus, 1753, Chenopodium chenopodioides Linnaeus, 1771, Chenopodium desiccatum A.Nelson, Chenopodium foliosum Moench, Chenopodium fremontii S.Watson, Chenopodium hians Standl., Chenopodium incanum var. occidentale D.J.Crawford, Chenopodium leptophyllum (Moq.) Nutt. ex S.Watson, Chenopodium littoreum Benet-Pierce & M.G.Simpson, Chenopodium nevadense Standl., Chenopodium pratericola Rydb., Chenopodium vulvaria L., Chenopodium watsonii A.Nelson, Chimaphila menziesii (R.Br. ex D.Don) Spreng., Chimaphila umbellata (L.) W.P.C.Barton, Chloris gayana Kunth, Chloris truncata R.Br., Chloris verticillata Nutt., Chloris virgata Sw., Chlorogalum angustifolium Kellogg, Chlorogalum grandiflorum Hoover, Chlorogalum parviflorum S.Watson, Chlorogalum pomeridianum (DC.) Kunth, Chlorogalum pomeridianum var. divaricatum (Lindl.) Hoover, Chlorogalum pomeridianum var. minus Hoover, Chlorogalum pomeridianum subsp. pomeridianum, Chlorogalum purpureum Brandegee, Chlorogalum purpureum var. purpureum, Chlorogalum purpureum var. reductum Hoover, Chondrilla juncea L., Chorispora tenella (Pall.) DC., Chorizanthe angustifolia Nutt., Chorizanthe biloba Goodman, Chorizanthe biloba var. immemora Reveal & C.B.Hardham, Chorizanthe blakleyi C.B.Hardham, Chorizanthe brevicornu Torr., Chorizanthe brevicornu var. spathulata (Small ex Rydb.) C.L.Hitchc., Chorizanthe breweri S.Watson, Chorizanthe clevelandii Parry, Chorizanthe corrugata (Torr.) Torr. & A.Gray, Chorizanthe cuspidata S.Watson, Chorizanthe cuspidata var. villosa (Eastw.) Munz, Chorizanthe diffusa Benth., Chorizanthe douglasii Benth., Chorizanthe fimbriata Nutt., Chorizanthe howellii Goodman, Chorizanthe leptotheca Goodman, Chorizanthe membranacea Benth., Chorizanthe minutiflora R.Morgan, Styer & Reveal, Chorizanthe obovata Goodman, Chorizanthe orcuttiana Parry, Chorizanthe palmeri S.Watson, Chorizanthe parryi S.Watson, Chorizanthe parryi var. fernandina (S.Watson) Jeps., Chorizanthe polygonoides A.Gray, Chorizanthe polygonoides var. longispina (Goodman) Munz, Chorizanthe procumbens Nutt., Chorizanthe pungens Benth., Chorizanthe pungens var. hartwegiana Reveal & C.B.Hardham, Chorizanthe rectispina Goodman, Chorizanthe rigida (Torr.) Torr. & A.Gray, Chorizanthe robusta Parry, Chorizanthe robusta var. hartwegii (Benth.) Reveal & R.Morgan, Chorizanthe spinosa S.Watson, Chorizanthe staticoides Benth., Chorizanthe stellulata Benth., Chorizanthe uniaristata Torr. & A.Gray, Chorizanthe valida S.Watson, Chorizanthe ventricosa Goodman, Chorizanthe watsonii A.Gray, Chorizanthe wheeleri S.Watson, Chorizanthe xanti S.Watson, Chorizanthe xanti var. leucotheca Goodman, Chrysolepis chrysophylla (Douglas ex Hook.) Hjelmq., Chrysolepis chrysophylla var. chrysophylla, Chrysolepis chrysophylla var. minor (Benth.) Munz, Chrysolepis sempervirens (Kellogg) Hjelmq., Chrysosplenium glechomifolium Nutt. ex Torr. & A.Gray, Chrysothamnus depressus Nutt., Chrysothamnus greenei (A.Gray) Greene, Chrysothamnus humilis Greene, Chrysothamnus viscidiflorus (Hook.) Nutt., Cichorium intybus L., Cicuta douglasii (DC.) J.M.Coult. & Rose, Cicuta maculata L., Cicuta maculata var. angustifolia Hook., Cicuta maculata var. bolanderi (S.Watson) G.A.Mulligan, Cinna bolanderi Scribn., Cinna latifolia (Trevir. ex Göpp.) Griseb., Cinnamomum camphora (L.) J.Presl, Cirsium andersonii (A.Gray) Petr., Cirsium andrewsii (A.Gray) Jeps., Cirsium arizonicum (A.Gray) Petr., Cirsium arizonicum var. arizonicum, Cirsium arizonicum var. tenuisectum D.J.Keil, Cirsium arvense (L.) Scop., Cirsium brevistylum Cronquist, Cirsium canescens Nutt., Cirsium ciliolatum (L.F.Hend.) J.T.Howell, Cirsium crassicaule (Greene) Jeps., Cirsium cymosum (Greene) J.T.Howell, Cirsium douglasii DC., Cirsium douglasii var. douglasii, Cirsium fontinale (Greene) Jeps., Cirsium fontinale var. campylon (H.Sharsm.) Pilz ex D.J.Keil & C.E.Turner, Cirsium fontinale var. fontinale, Cirsium fontinale var. obispoense J.T.Howell, Cirsium hydrophilum (Greene) Jeps., Cirsium hydrophilum var. hydrophilum, Cirsium hydrophilum var. vaseyi (A.Gray) J.T.Howell, Cirsium mohavense (Greene) Petr., Cirsium neomexicanum A.Gray, Cirsium occidentale (Nutt.) Jeps., Cirsium occidentale var. californicum (A.Gray) D.J.Keil & C.E.Turner, Cirsium occidentale var. candidissimum (Greene) J.F.Macbr., Cirsium occidentale var. compactum Hoover, Cirsium occidentale var. lucianum D.J.Keil, Cirsium occidentale subsp. occidentale, Cirsium occidentale var. occidentale, Cirsium occidentale var. venustum (Greene) Jeps., Cirsium ochrocentrum subsp. ochrocentrum, Cirsium ochrocentrum var. ochrocentrum, Cirsium praeteriens J.F.Macbr., Cirsium quercetorum (A.Gray) Jeps., Cirsium remotifolium (Hook.) DC., Cirsium remotifolium var. remotifolium, Cirsium rhothophilum S.F.Blake, Cirsium scariosum Nutt., Cirsium scariosum var. americanum (A.Gray) D.J.Keil, Cirsium scariosum var. robustum D.J.Keil, Cirsium scariosum var. scariosum, Cirsium undulatum (Nutt.) Spreng., Cirsium vulgare (Savi) Ten., Cistanthe maritima (Nutt.) Carolin ex Hershk., Cistus ×incanus L., Cistus ladanifer L., Clarkia affinis F.H.Lewis & M.E.Lewis, Clarkia amoena (Lehm.) A.Nelson & J.F.Macbr., Clarkia arcuata (Kellogg) A.Nelson & J.F.Macbr., Clarkia biloba (Durand) A.Nelson & J.F.Macbr., Clarkia borealis E.Small, Clarkia bottae (Spach) F.H.Lewis & M.E.Lewis, Clarkia breweri (A.Gray) Greene, Clarkia concinna (Fisch. & C.A.Mey.) Greene, Clarkia cylindrica (Jeps.) F.H.Lewis & M.E.Lewis, Clarkia davyi (Jeps.) F.H.Lewis & M.E.Lewis, Clarkia delicata (Abrams) A.Nelson & J.F.Macbr., Clarkia dudleyana (Abrams) J.F.Macbr., Clarkia epilobioides (Nutt.) A.Nelson & J.F.Macbr., Clarkia exilis F.H.Lewis & Vasek, Clarkia franciscana F.H.Lewis & Raven, Clarkia gracilis (Piper) A.Nelson & J.F.Macbr., Clarkia heterandra (Torr.) F.H.Lewis & P.H.Raven, Clarkia imbricata F.H.Lewis & M.E.Lewis, Clarkia jolonensis D.R.Parn., Clarkia lassenensis (Eastw.) F.H.Lewis & M.E.Lewis, Clarkia lewisii P.H.Raven & D.R.Parn., Clarkia lingulata F.H.Lewis & M.E.Lewis, Clarkia mildrediae (A.Heller) F.H.Lewis & M.E.Lewis, Clarkia modesta Jeps., Clarkia mosquinii E.Small, Clarkia prostrata F.H.Lewis & M.E.Lewis, Clarkia purpurea (Curtis) A.Nelson & J.F.Macbr., Clarkia rhomboidea Douglas, Clarkia rostrata W.S.Davis, Clarkia rubicunda (Lindl.) F.H.Lewis & M.E.Lewis, Clarkia similis F.H.Lewis & W.R.Ernst, Clarkia speciosa F.H. & M.E.Lewis, Clarkia springvillensis Vasek, Clarkia stellata Mosquin, Clarkia tembloriensis Vasek, Clarkia unguiculata Lindl., Clarkia virgata Greene, Clarkia williamsonii (Durand & Hilg.) F.H.Lewis & M.E.Lewis, Clarkia xantiana A.Gray, Claytonia cordifolia S.Watson, Claytonia exigua Douglas ex Torr. & A.Gray, Claytonia gypsophiloides Fisch. & C.A.Mey., Claytonia lanceolata Pursh, Claytonia megarhiza (A.Gray) Parry ex S.Watson, Claytonia nevadensis S.Watson, Claytonia palustris Swanson & Kelley, Claytonia parviflora Douglas ex Hook., Claytonia perfoliata Donn., Claytonia rubra (Howell) Tidestr., Claytonia saxosa Brandegee, Claytonia sibirica L., Claytonia umbellata S.Watson, Claytonia washingtoniana (Suksd.) Suksd., Clematis lasiantha Nutt. ex Torr. & A.Gray, Clematis ligusticifolia Nutt. ex Torr. & A.Gray, Clematis pauciflora Nutt. ex Torr. & A.Gray, Cleomella brevipes S.Watson, Cleomella obtusifolia Torr. & Frém., Cleomella parviflora A.Gray, Cleomella plocasperma S.Watson, Clinopodium chandleri (Brandegee) P.D.Cantino & Wagstaff, Clinopodium mimuloides (Benth.) Kuntze, Clintonia andrewsiana Torr., Clintonia uniflora (Menzies ex Schult. & Schult.f.) Kunth, Cneoridium dumosum (Nutt.) Hook.fil., Cochlearia groenlandica L., Coleogyne ramosissima Torr., Collinsia bartsiifolia Benth., Collinsia bartsiifolia var. stricta Newsom, Collinsia callosa Parish, Collinsia childii Parry ex A.Gray, Collinsia concolor Greene, Collinsia corymbosa Herder, Collinsia grandiflora Douglas ex Lindl., Collinsia greenei A.Gray ex Greene, Collinsia heterophylla Buist ex Graham, Collinsia heterophylla var. austromontana (Newsom) Munz, Collinsia linearis A.Gray, Collinsia multicolor Lindl. & Paxton, Collinsia parryi A.Gray, Collinsia parviflora Douglas ex Lindl., Collinsia rattanii A.Gray, Collinsia sparsiflora Fisch. & C.A.Mey., Collinsia sparsiflora var. collina (Jeps.) Newsom, Collinsia tinctoria Hartw. ex Benth., Collinsia torreyi A.Gray, Collomia diversifolia Greene, Collomia grandiflora Lindl., Collomia heterophylla Douglas ex Hook., Collomia linearis Nutt., Collomia rawsoniana Greene, Collomia tenella A.Gray, Collomia tinctoria Kellogg, Collomia tracyi R.Mason, Colubrina californica I.M.Johnst., Colutea arborescens L., Comarum palustre L., Commelina benghalensis L., Condalia globosa subsp. pubescens (I.M.Johnst.) A.E.Murray, Conium maculatum L., Conringia orientalis (L.) Dumort., Convolvulus althaeoides L., Convolvulus arvensis L., Coprosma repens A.Rich., Coptis laciniata A.Gray, Corallorhiza maculata Raf., Corallorhiza maculata var. maculata, Corallorhiza maculata var. occidentalis (Lindl.) Ames, Corallorhiza mertensiana Bong., Corallorhiza striata Lindl., Corallorhiza trifida Châtel., Cordylanthus capitatus Nutt. ex Benth., Cordylanthus eremicus (Coville & C.V.Morton) Munz, Cordylanthus nevinii A.Gray, Cordylanthus nidularius Howell, Cordylanthus parviflorus (Ferris) Wiggins, Cordylanthus pilosus A.Gray, Cordylanthus pringlei A.Gray, Cordylanthus ramosus Nutt. ex Benth, Cordylanthus rigidus (Benth.) Jeps., Cordylanthus tenuis A.Gray, Coreopsis lanceolata L., Coreopsis tinctoria Nutt., Corethrogyne filaginifolia (Hook. & Arn.) Nutt., Coriandrum sativum L., Corispermum americanum var. americanum, Cornus canadensis L., Cornus glabrata Benth., Cornus nuttallii Audubon ex Torr. & A.Gray, Cornus sericea L., Cornus sessilis Torr., Coronilla varia L., Cortaderia jubata (Lemoine) Stapf, Cortaderia selloana (Schult. & Schult.f.) Asch. & Graebn., Corydalis aurea Willd., Cosmos bipinnatus Cav., Cosmos sulphureus Cav., Cotoneaster franchetii Boiss., Cotoneaster lacteus W.W.Sm., Cotoneaster pannosus Franch., Cotoneaster simonsii Baker, Cotula australis (Sieber ex Spreng.) Hook.fil., Cotula coronopifolia L., Cotyledon orbiculata var. oblonga (Haw.) DC., Crassula aquatica (L.) Schönland, Crassula connata (Ruiz & Pav.) A.Berger, Crassula solieri (Gay) F.Meigen, Crassula tillaea Lest.-Garl., Crataegus castlegarensis J.B.Phipps & O'Kennon, Crataegus douglasii Lindl., Crataegus gaylussacia A.Heller, Crataegus monogyna Jacq., Crepis acuminata Nutt., Crepis bakeri Greene, Crepis bursifolia L., Crepis capillaris (L.) Wallr., Crepis intermedia A.Gray, Crepis modocensis Greene, Crepis monticola Coville, Crepis occidentalis Nutt., Crepis pleurocarpa A.Gray, Crepis runcinata (James) Torr. & A.Gray, Crepis setosa Haller fil., Crepis tectorum L., Cressa truxillensis Kunth, Crocanthemum aldersonii (Greene) Janch., Crocanthemum scoparium Millsp., Crocanthemum scoparium var. scoparium, Crocanthemum scoparium var. vulgare (Jeps.) Sorrie, Crocanthemum suffrutescens (B.Schreib.) Sorrie, Crocidium multicaule Hook., Crossosoma bigelovii S.Watson, Crossosoma californicum Nutt., Croton californicus Müll.Arg., Croton wigginsii L.C.Wheeler, Crucianella angustifolia L., Crupina vulgaris (Pers.) Cass., Cryptantha affinis (A.Gray) Greene, Cryptantha ambigua (A.Gray) Greene, Cryptantha angustifolia (Torr.) Greene, Cryptantha barbigera (A.Gray) Greene, Cryptantha clevelandii Greene, Cryptantha clevelandii var. florosa I.M.Johnst., Cryptantha clokeyi I.M.Johnst., Cryptantha corollata (I.M.Johnst.) I.M.Johnst., Cryptantha crinita Greene, Cryptantha dumetorum (Greene ex A.Gray) Greene, Cryptantha echinella Greene, Cryptantha excavata Brandegee, Cryptantha fendleri (A.Gray) Greene, Cryptantha flaccida (Douglas ex Lehm.) Greene, Cryptantha ganderi I.M.Johnst., Cryptantha glomeriflora Greene, Cryptantha gracilis Osterh., Cryptantha hispidula Greene ex Brand, Cryptantha hooveri I.M.Johnst., Cryptantha incana Greene, Cryptantha intermedia (A.Gray) Greene, Cryptantha leiocarpa (Fisch. & C.A.Mey.) Greene, Cryptantha mariposae I.M.Johnst., Cryptantha maritima (Greene) Greene, Cryptantha microstachys (Greene ex A.Gray) Greene, Cryptantha mohavensis (Greene) Greene, Cryptantha muricata (Hook. & Arn.) A.Nelson & J.F.Macbr., Cryptantha nemaclada Greene, Cryptantha nevadensis A.Nelson & Kenn., Cryptantha nubigena (Greene) Payson, Cryptantha oxygona (A.Gray) Greene, Cryptantha pterocarya (Torr.) Greene, Cryptantha pterocarya var. cycloptera (Greene) J.F.Macbr., Cryptantha rattanii Greene, Cryptantha recurvata Coville, Cryptantha scoparia A.Nelson, Cryptantha simulans Greene, Cryptantha sparsiflora (Greene) Greene, Cryptantha torreyana (A.Gray) Greene, Cryptantha traskiae I.M.Johnst., Cryptantha utahensis (A.Gray) Greene, Cryptantha watsonii (A.Gray) Greene, Cryptogramma acrostichoides R.Br., Cryptogramma cascadensis E.R.Alverson, Cucumis myriocarpus Naudin, Cucurbita digitata A.Gray, Cucurbita foetidissima Kunth, Cucurbita palmata S.Watson, Cucurbita pepo subsp. pepo, Cuscuta approximata Bab., Cuscuta brachycalyx (Yunck.) Yunck., Cuscuta californica Choisy, Cuscuta californica var. apiculata Engelm., Cuscuta californica var. papillosa Yunck., Cuscuta cephalanthi Engelm., Cuscuta denticulata Engelm., Cuscuta howelliana P.Rubtzov, Cuscuta indecora var. indecora, Cuscuta obtusiflora var. glandulosa Engelm., Cuscuta salina Engelm., Cuscuta suaveolens Ser., Cuscuta suksdorfii Yunck., Cusickiella douglasii (A.Gray) Rollins, Cusickiella quadricostata (Rollins) Rollins, Cycladenia humilis var. humilis, Cycladenia humilis var. jonesii (Eastw.) S.L.Welsh & N.D.Atwood, Cycladenia humilis var. venusta (Eastw.) Woods ex Munz, Cycloloma atriplicifolium (Spreng.) J.M.Coult., Cyclospermum leptophyllum (Pers.) Sprague, Cylindropuntia echinocarpa (Engelm. & J.M.Bigelow) F.M.Knuth, Cymbalaria muralis G.Gaertn., B.Mey. & Scherb., Cymopterus deserticola Brandegee, Cymopterus gilmanii C.V.Morton, Cymopterus globosus (S.Watson) S.Watson, Cymopterus ripleyi Barneby, Cynodon dactylon (L.) Pers., Cynoglossum officinale L., Cynosurus cristatus L., Cynosurus echinatus L., Cyperus acuminatus Torr. & Hook., Cyperus bipartitus Torr., Cyperus difformis L., Cyperus eragrostis Lam., Cyperus erythrorhizos Muhl., Cyperus esculentus L., Cyperus flavescens L., Cyperus flavicomus Schltdl., Cyperus fuscus L., Cyperus iria L., Cyperus laevigatus L., Cyperus niger Ruiz & Pav., Cyperus odoratus L., Cyperus parishii Britton, Cyperus rotundus L., Cyperus squarrosus L., Cyperus strigosus L., Cypripedium californicum A.Gray, Cypripedium fasciculatum Kellogg, Cypripedium montanum Douglas ex Lindl., Cypripedium parviflorum var. makasin (Farw.) Sheviak, Cyrtomium falcatum (L.fil.) C.Presl, Cystopteris fragilis (L.) Bernh., Cytisus multiflorus (L'Hér.) Sweet, Cytisus scoparius (L.) Link, Cytisus striatus (Hill) Rothm., Dactylis glomerata L., Dactyloctenium aegyptium (L.) Willd., Dalea mollis Benth., Dalea mollissima (Rydb.) Munz, Dalea ornata (Douglas ex Hook.) Eaton & Wright, Dalea searlsiae (A.Gray) Barneby, Damasonium californicum Torr., Danthonia californica Bol., Danthonia decumbens (L.) DC., Danthonia unispicata (Thurb.) Munro ex Macoun, Darlingtonia californica Torr., Darmera peltata (Torr. ex Benth.) Voss, Dasiphora fruticosa (L.) Rydb., Dasyochloa pulchella Willd., Datisca glomerata (C.Presl) Baill., Datura discolor Bernh., Datura ferox L., Datura stramonium L., Datura wrightii Regel, Daucus carota L., Daucus pusillus Michx., Dedeckera eurekensis Reveal & J.T.Howell, Deinandra bacigalupii B.G.Baldwin, Delairea odorata Lem., Delphinium andersonii A.Gray, Delphinium bakeri Ewan, Delphinium californicum Torr. & A.Gray, Delphinium cardinale Hook., Delphinium decorum Fisch. & C.A.Mey., Delphinium depauperatum Nutt. ex Torr. & A.Gray, Delphinium glaucum S.Watson, Delphinium gracilentum Greene, Delphinium gypsophilum Ewan, Delphinium hansenii (Greene) Greene, Delphinium hesperium A.Gray, Delphinium hutchinsoniae Ewan, Delphinium inopinum (Jeps.) Lewis & Epling, Delphinium luteum A.Heller, Delphinium nudicaule Torr. & A.Gray, Delphinium nuttallianum Pritz. ex Walp., Delphinium parishii A.Gray, Delphinium parryi A.Gray, Delphinium patens Newb., Delphinium polycladon Eastw., Delphinium purpusii Brandegee, Delphinium recurvatum Greene, Delphinium scaposum Greene, Delphinium stachydeum (A.Gray) A.Nelson & J.F.Macbr., Delphinium trolliifolium A.Gray, Delphinium uliginosum Curran, Delphinium umbraculorum H.Lewis & Epling, Delphinium variegatum Torr. & A.Gray, Dendromecon harfordii Kellogg, Dendromecon rigida Benth., Deschampsia cespitosa (L.) P.Beauv., Deschampsia danthonioides (Trin.) Benth., Deschampsia elongata (Hook.) Munro, Descurainia californica (A.Gray) O.E.Schulz, Descurainia incana (Bernh. ex Fisch. & C.A.Mey.) Dorn, Descurainia paradisa (A.Nelson & P.B.Kenn.) O.E.Schulz, Descurainia pinnata (Walter) Britton, Descurainia sophia (L.) Webb ex Prantl, Dicentra formosa (Andrews) Walp., Dicentra nevadensis Eastw., Dicentra pauciflora S.Watson, Dicentra uniflora Kellogg, Dichelostemma congestum (Sm.) Kunth, Dichelostemma ida-maia (Alph.Wood) Greene, Dichelostemma multiflorum (Benth.) A.Heller, Dichelostemma volubile (Kellogg) A.Heller, Dichondra micrantha Urb., Dichondra occidentalis House, Dicoria canescens A.Gray, Digitalis purpurea L., Digitaria ischaemum (Schreb.) Muhl., Digitaria sanguinalis (L.) Scop., Dimeresia howellii A.Gray, Dimorphotheca sinuata DC., Diospyros virginiana L., Diplacus aridus Abrams, Diplacus aurantiacus (Curtis) Jeps., Diplacus brandegeei (Pennell) G.L.Nesom, Diplacus calycinus Eastw., Diplacus clevelandii (Brandegee) Greene, Diplacus cusickioides G.L.Nesom, Diplacus grandiflorus (Lindl.) Groenland, Diplacus linearis (Benth.) Greene, Diplacus longiflorus Nutt., Diplacus parviflorus Greene, Diplacus puniceus Nutt., Diplacus traskiae (A.L.Grant) G.L.Nesom, Diplotaxis muralis (L.) DC., Diplotaxis tenuifolia (L.) DC., Dipsacus fullonum Thore, Dipsacus sativus (L.) Honck., Dirca occidentalis A.Gray, Distichlis spicata (L.) Greene, Dithyrea californica Harv., Dithyrea maritima (Davidson ex B.L.Rob.) Davidson, Dittrichia graveolens (L.) Greuter, Dittrichia viscosa (L.) Greuter, Dodecahema leptoceras (A.Gray) Reveal & C.B.Hardham, Dopatrium junceum (Roxb.) Buch.-Ham. ex Benth., Downingia bacigalupii Weiler, Downingia bella Hoover, Downingia bicornuta A.Gray, Downingia concolor Greene, Downingia concolor subsp. brevior (McVaugh) R.M.Beauch., Downingia concolor subsp. concolor, Downingia cuspidata (Greene) Rattan, Downingia elegans (Douglas ex Lindl.) Torr., Downingia insignis Greene, Downingia laeta (Greene) Greene, Downingia montana Greene, Downingia ornatissima Greene, Downingia pulchella (Lindl.) Torr., Downingia pusilla (G.Don ex A.DC.) Torr., Downingia yina Applegate, Draba albertina Greene, Draba asterophora Payson, Draba aureola S.Watson, Draba breweri S.Watson, Draba californica (Jeps.) Rollins & R.A.Price, Draba cana Rydb., Draba carnosula O.E.Schulz, Draba corrugata S.Watson, Draba cruciata Payson, Draba densifolia Nutt., Draba howellii S.Watson, Draba incrassata (Rollins) Rollins & R.A.Price, Draba lemmonii S.Watson, Draba lonchocarpa Rydb., Draba monoensis Rollins & R.A.Price, Draba nemorosa L., Draba oligosperma Hook., Draba praealta Greene, Draba pterosperma Payson, Draba sharsmithii Rollins & R.A.Price, Draba sierrae Sharsm., Draba subumbellata Rollins & R.A.Price, Draba verna L., Draperia systyla (A.Gray) Torr., Drosanthemum floribundum (Haw.) Schwantes, Drosera capensis L., Drosera capillaris Poir., Drosera filiformis Raf., Drosera intermedia Hayne, Drosera anglica Huds., Drosera rotundifolia L., Drymocallis cuneifolia Rydb., Drymocallis glandulosa (Lindl.) Rydb., Drymocallis glandulosa subsp. glandulosa, Drymocallis glandulosa var. glandulosa, Drymocallis glandulosa subsp. reflexa (Greene) Soják, Drymocallis lactea (Greene) Rydb., Dryopteris arguta (Kaulf.) Watt, Dryopteris expansa (C.Presl) Fraser-Jenk. & Jermy, Dryopteris filix-mas (L.) Schott, Dudleya abramsii Rose, Dudleya blochmaniae (Eastw.) Moran, Dudleya candelabrum Rose, Dudleya cymosa (Lem.) Britton & Rose, Dudleya densiflora (Rose) Moran, Dudleya edulis (Nutt.) Moran, Dudleya farinosa (Lindl.) Britton & Rose, Dudleya gnoma S.Mc Cabe, Dudleya greenei Rose, Dudleya lanceolata (Nutt.) Britton & Rose, Dudleya multicaulis (Rose) Moran, Dudleya nesiotica (Moran) Moran, Dudleya palmeri (S.Watson) Britton & Rose, Dudleya pulverulenta (Nutt.) Britton & Rose, Dudleya saxosa (M.E.Jones) Britton & Rose, Dudleya stolonifera Moran, Dudleya variegata (S.Watson) Moran, Dudleya verityi K.M.Nakai, Dudleya virens (Rose) Moran, Dudleya viscida (S.Watson) Moran, Dulichium arundinaceum var. arundinaceum, Dyssodia papposa (Vent.) A.Hitchc., Eastwoodia elegans Brandegee, Eatonella nivea (D.C.Eaton) A.Gray, Echinocactus polycephalus subsp. polycephalus, Echinocereus engelmannii (Parry ex Engelm.) Rümpler, Echinochloa colona (L.) Link, Echinochloa crus-galli (L.) P.Beauv., Echinochloa oryzoides (Ard.) Fritsch, Echinodorus berteroi (Spreng.) Fassett, Echinops sphaerocephalus L., Echium pininana Webb & Berthel., Echium plantagineum L., Eclipta prostrata (L.) L., Egeria densa Planch., Ehrharta calycina Sm., Ehrharta erecta Lam., Eichhornia crassipes (Mart.) Solms, Elaeagnus angustifolia L., Elatine ambigua Wight, Elatine brachysperma A.Gray, Elatine californica A.Gray, Elatine heterandra H.Mason, Elatine rubella Rydb., Eleocharis acicularis (L.) Roem. & Schult., Eleocharis acicularis var. acicularis, Eleocharis atropurpurea (Retz.) J.Presl & C.Presl, Eleocharis bella (Piper) Svenson, Eleocharis bolanderi A.Gray, Eleocharis coloradoensis (Britton) Gilly, Eleocharis decumbens C.B.Clarke, Eleocharis engelmannii Steud., Eleocharis flavescens var. flavescens, Eleocharis geniculata (L.) Roem. & Schult., Eleocharis macrostachya Britton, Eleocharis montevidensis Kunth, Eleocharis obtusa (Willd.) Schult., Eleocharis ovata (Roth) Roem. & Schult., Eleocharis pachycarpa É.Desv., Eleocharis palustris (L.) Roem. & Schult., Eleocharis parishii Britton, Eleocharis parvula (Roem. & Schult.) Link ex Bluff, Nees & Schauer, Eleocharis quadrangulata (Michx.) Roem. & Schult., Eleocharis quinqueflora (Hartmann) O.Schwarz, Eleocharis rostellata (Torr.) Torr., Eleocharis suksdorfiana Beauverd, Eleocharis tenuis var. tenuis, Eleocharis torticulmis S.G.Sm., Eleusine indica (L.) Gaertn., Eleusine tristachya (Lam.) Lam., Elodea bifoliata H.St.John, Elodea canadensis Michx., Elodea nuttallii (Planch.) H.St.John, Elymus californicus (Bol. ex Thurb.) Gould, Elymus elymoides (Raf.) Swezey, Elymus glaucus Buckley, Elymus multisetus (J.G.Sm.) Burtt Davy, Elymus repens (L.) Gould, Elymus scribneri (Vasey) M.E.Jones, Elymus stebbinsii Gould, Emex spinosa Linnaeus, 1753, Emmenanthe penduliflora var. rosea Brand, Empetrum nigrum L., Encelia californica Nutt., Encelia farinosa A.Gray ex Torr., Encelia frutescens (A.Gray) A.Gray, Encelia virginensis A.Nelson, Enceliopsis covillei (A.Nelson) S.F.Blake, Enceliopsis nudicaulis (A.Gray) A.Nelson, Enemion occidentale (Hook. & Arn.) J.R.Drumm. & Hutch., Enemion stipitatum (A.Gray) J.R.Drumm. & Hutch., Enneapogon desvauxii P.Beauv., Ephedra californica S.Watson, Ephedra funerea Coville & C.V.Morton, Ephedra nevadensis S.Watson, Ephedra trifurca Torr. ex S.Watson, Ephedra viridis Coville, Epilobium anagallidifolium Lam., Epilobium brachycarpum C.Presl, Epilobium canum (Greene) P.H.Raven, Epilobium ciliatum Raf., Epilobium clavatum Trel., Epilobium cleistogamum (Curran) Hoch & P.H.Raven, Epilobium densiflorum (Lindl.) Hoch & P.H.Raven, Epilobium ×foliosum Dalla Torre & Sarnth., Epilobium glaberrimum Barbey, Epilobium howellii Hoch, Epilobium lactiflorum Hausskn., Epilobium leptophyllum Raf., Epilobium luteum Pursh, Epilobium minutum Lindl., Epilobium nivium Brandegee, Epilobium obcordatum A.Gray, Epilobium oreganum Greene, Epilobium oregonense Hausskn., Epilobium pallidum (Eastw.) Hoch & P.H.Raven, Epilobium palustre L., Epilobium rigidum Hausskn., Epilobium saximontanum Hausskn., Epilobium septentrionale (D.D.Keck) R.N.Bowman & Hoch, Epilobium siskiyouense (Munz) Hoch & P.H.Raven, Epilobium torreyi (S.Watson) Hoch & P.H.Raven, Epipactis gigantea Dougl. ex Hook., Epipactis helleborine (L.) Crantz, Equisetum arvense L., Equisetum laevigatum A.Braun & Engelm., Equisetum palustre L., Eragrostis barrelieri Daveau, Eragrostis cilianensis (All.) Janch., Eragrostis curvula (Schrad.) Nees, Eragrostis hypnoides (Lam.) Britton, Sterns & Poggenb., Eragrostis lehmanniana Nees, Eragrostis lutescens Scribn., Eragrostis mexicana (Hornem.) Link, Eragrostis minor Host, Eragrostis pectinacea (Michx.) Nees, Eremalche exilis (A.Gray) Greene, Eremalche parryi (Greene) Greene, Eremalche rotundifolia (A.Gray) Greene, Eremogone aculeata (S.Watson) Ikonn., Eremogone cliftonii Rabeler & R.L.Hartm., Eremogone congesta (Nutt. ex Torr. & A.Gray) Ikonn., Eremogone congesta var. charlestonensis (Maguire) R.L.Hartm. & Rabeler, Eremogone congesta var. crassula (Maguire) R.L.Hartm. & Rabeler, Eremogone congesta var. simulans (Maguire) R.L.Hartm. & Rabeler, Eremogone congesta var. subcongesta (S.Watson) R.L.Hartm. & Rabeler, Eremogone congesta var. suffrutescens (A.Gray) R.L.Hartm. & Rabeler, Eremogone ferrisiae (Abrams) R.L.Hartm. & Rabeler, Eremogone kingii var. glabrescens (S.Watson) Dorn, Eremogone macradenia (S.Watson) Ikonn., Eremogone macradenia var. arcuifolia (Maguire) R.L.Hartm. & Rabeler, Eremogone ursina (B.L.Rob.) Ikonn., Eriastrum abramsii (Elmer) H.Mason, Eriastrum densifolium (Benth.) H.Mason, Eriastrum diffusum (A.Gray) H.Mason, Eriastrum ertterae D.Gowen, Eriastrum filifolium (Nutt.) Wooton & Standl., Eriastrum hooveri (Jeps.) H.Mason, Eriastrum luteum (Benth.) H.Mason, Eriastrum pluriflorum (A.Heller) H.Mason, Eriastrum rosamondense D.Gowen, Eriastrum sapphirinum (Eastw.) Mason, Eriastrum sparsiflorum (Eastw.) H.Mason, Eriastrum virgatum (Benth.) H.Mason, Eriastrum wilcoxii (A.Nelson) H.Mason, Erica lusitanica Rudolphi, Ericameria arborescens (A.Gray) Greene, Ericameria bloomeri (A.Gray) J.F.Macbr., Ericameria brachylepis (A.Gray) H.M.Hall, Ericameria cuneata (A.Gray) Mc Clatchie, Ericameria cuneata var. macrocephala Urbatsch, Ericameria cuneata var. spathulata (A.Gray) Mc Clatchie, Ericameria discoidea (Nutt.) G.L.Nesom, Ericameria ericoides (Less.) Jeps., Ericameria fasciculata (Eastw.) J.F.Macbr., Ericameria gilmanii (S.F.Blake) G.L.Nesom, Ericameria greenei (A.Gray) G.L.Nesom, Ericameria laricifolia (A.Gray) Shinners, Ericameria linearifolia (DC.) Urbatsch & Wussow, Ericameria nana Nutt., Ericameria nauseosa (Pall. ex Pursh) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. bernardina (H.M.Hall) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. ceruminosa (Durand & Hilg.) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. hololeuca (A.Gray) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. leiosperma (A.Gray) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. mohavensis (Greene) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. oreophila (A.Nelson) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. speciosa (Nutt.) G.L.Nesom & G.I.Baird, Ericameria nauseosa var. washoensis (L.C.Anderson) G.L.Nesom & G.I.Baird, Ericameria ophitidis (J.T.Howell) G.L.Nesom, Ericameria palmeri (A.Gray) H.M.Hall, Ericameria palmeri var. pachylepis (H.M.Hall) G.L.Nesom ex M.A.Lane & R.L.Hartm., Ericameria palmeri var. palmeri, Ericameria paniculata (A.Gray) Rydb., Ericameria parryi (A.Gray) G.L.Nesom & G.I.Baird, Ericameria parryi var. aspera (Greene) G.L.Nesom & G.I.Baird, Ericameria parryi var. imula (H.M.Hall & Clem.) G.L.Nesom & G.I.Baird, Ericameria parryi var. latior (H.M.Hall & Clem.) G.L.Nesom & G.I.Baird, Ericameria parryi var. nevadensis (A.Gray) G.L.Nesom & G.I.Baird, Ericameria parryi var. vulcanica (Greene) G.L.Nesom & G.I.Baird, Ericameria pinifolia (A.Gray) H.M.Hall, Ericameria suffruticosa (Nutt.) G.L.Nesom, Ericameria teretifolia (Durand & Hilg.) Jeps., Erigeron aequifolius H.M.Hall, Erigeron algidus Jeps., Erigeron aliceae Howell, Erigeron annuus (L.) Pers., Erigeron aphanactis (A.Gray) Greene, Erigeron aphanactis var. congestus (Greene) Cronquist, Erigeron argentatus A.Gray, Erigeron barbellulatus Greene, Erigeron biolettii Greene, Erigeron blochmaniae Greene, Erigeron bloomeri A.Gray, Erigeron bloomeri var. bloomeri, Erigeron bloomeri var. nudatus (A.Gray) Cronquist, Erigeron breweri A.Gray, Erigeron breweri var. bisanctus G.L.Nesom, Erigeron breweri var. breweri, Erigeron breweri var. covillei (Greene) G.L.Nesom, Erigeron breweri var. jacinteus (H.M.Hall) Cronquist, Erigeron breweri var. porphyreticus (M.E.Jones) Cronquist, Erigeron calvus Coville, Erigeron cervinus Greene, Erigeron clokeyi var. pinzliae G.L.Nesom, Erigeron compactus S.F.Blake, Erigeron compositus Pursh, Erigeron concinnus var. concinnus, Erigeron coulteri Porter & Coult., Erigeron divergens Torr. & A.Gray, Erigeron eatonii A.Gray, Erigeron eatonii var. nevadincola (S.F.Blake) G.L.Nesom, Erigeron eatonii var. plantagineus (Greene) Cronquist, Erigeron eatonii var. sonnei (Greene) G.L.Nesom, Erigeron elegantulus Greene, Erigeron elmeri (Greene) Greene, Erigeron filifolius (Hook.) Nutt., Erigeron flagellaris A.Gray, Erigeron foliosus (Phil.), Erigeron foliosus var. confinis (Howell) Jeps., Erigeron foliosus var. foliosus, Erigeron foliosus var. franciscensis G.L.Nesom, Erigeron foliosus var. hartwegii (Greene) Jeps., Erigeron glaucus Ker Gawl., Erigeron inornatus (A.Gray) A.Gray, Erigeron inornatus var. calidipetris G.L.Nesom, Erigeron inornatus var. inornatus, Erigeron inornatus var. keilii G.L.Nesom, Erigeron karvinskianus DC., Erigeron lassenianus Greene, Erigeron lassenianus var. deficiens Cronquist, Erigeron lassenianus var. lassenianus, Erigeron linearis (Hook.) Piper, Erigeron lonchophyllus Hook., Erigeron maniopotamicus G.L.Nesom & T.W.Nelson, Erigeron mariposanus Congdon, Erigeron miser A.Gray, Erigeron multiceps Greene, Erigeron nivalis Nutt., Erigeron oxyphyllus Greene, Erigeron parishii A.Gray, Erigeron petrophilus Greene, Erigeron petrophilus var. petrophilus, Erigeron petrophilus var. sierrensis G.L.Nesom, Erigeron petrophilus var. viscidulus (A.Gray) G.L.Nesom, Erigeron philadelphicus var. philadelphicus, Erigeron pumilus var. intermedius Cronquist, Erigeron pygmaeus (A.Gray) Greene, Erigeron reductus (Cronquist) G.L.Nesom, Erigeron reductus var. angustatus (A.Gray) G.L.Nesom, Erigeron reductus var. reductus, Erigeron sanctarum S.Watson ex Brandegee, Erigeron serpentinus G.L.Nesom, Erigeron strigosus var. strigosus, Erigeron supplex A.Gray, Erigeron tener (A.Gray) A.Gray, Erigeron utahensis A.Gray, Erigeron vagus Payson, Eriochloa contracta Hitchc., Eriodictyon altissimum P.V.Wells, Eriodictyon angustifolium Nutt., Eriodictyon californicum (Hook. & Arn.) Greene, Eriodictyon capitatum Eastw., Eriodictyon crassifolium Benth., Eriodictyon crassifolium var. nigrescens Brand, Eriodictyon sessilifolium Greene, Eriodictyon tomentosum Benth., Eriodictyon traskiae Eastw., Eriodictyon trichocalyx A.Heller, Eriogonum alpinum Engelm., Eriogonum ampullaceum Howell, Eriogonum angulosum Benth., Eriogonum apiculatum S.Watson, Eriogonum apricum J.T.Howell, Eriogonum apricum var. prostratum Myatt, Eriogonum arborescens Greene, Eriogonum argillosum Howell, Eriogonum baileyi S.Watson, Eriogonum baileyi var. praebens (Gand.) Reveal, Eriogonum bifurcatum Reveal, Eriogonum brachyanthum Coville, Eriogonum brachypodum Torr. & A.Gray, Eriogonum breedlovei (J.T.Howell) Reveal, Eriogonum breedlovei var. shevockii J.T.Howell, Eriogonum butterworthianum Howell, Eriogonum caespitosum Nutt., Eriogonum callistum Reveal, Eriogonum cedrorum Reveal & Raiche, Eriogonum cernuum Nutt., Eriogonum cinereum Benth., Eriogonum cithariforme S.Watson, Eriogonum cithariforme var. agninum (Greene) Reveal, Eriogonum collinum S.Stokes ex M.E.Jones, Eriogonum congdonii (S.Stokes) Reveal, Eriogonum contiguum (Reveal) Reveal, Eriogonum covilleanum Eastw., Eriogonum crocatum Davidson, Eriogonum dasyanthemum Torr. & A.Gray, Eriogonum davidsonii Greene, Eriogonum deflexum Torr., Eriogonum deflexum var. baratum (Elmer) Reveal, Eriogonum deflexum var. nevadense Reveal, Eriogonum deserticola S.Watson, Eriogonum diclinum Reveal, Eriogonum douglasii var. meridionale Reveal, Eriogonum eastwoodianum Howell, Eriogonum elatum Douglas ex Benth., Eriogonum elatum var. villosum Jeps., Eriogonum elegans Greene, Eriogonum eremicola Howell & Reveal, Eriogonum evanidum Reveal, Eriogonum fasciculatum Benth., Eriogonum fasciculatum var. flavoviride Munz & I.M.Johnst., Eriogonum fasciculatum var. foliolosum (Nutt.) S.Stokes ex Abrams, Eriogonum fasciculatum var. polifolium (Benth.) Torr. & A.Gray, Eriogonum giganteum S.Watson, Eriogonum giganteum var. compactum Dunkle, Eriogonum giganteum var. formosum K.Brandegee, Eriogonum gilmanii S.Stokes, Eriogonum glandulosum (Nutt.) Nutt. ex Benth., Eriogonum gossypinum Curran, Eriogonum gracile Benth., Eriogonum gracile var. incultum Reveal, Eriogonum gracilipes S.Watson, Eriogonum gracillimum S.Watson, Eriogonum grande Greene, Eriogonum grande var. rubescens (Greene) Munz, Eriogonum grande var. timorum Reveal, Eriogonum heermannii Durand & Hilg., Eriogonum heermannii var. argense (M.E.Jones) Munz, Eriogonum heermannii var. floccosum Munz, Eriogonum heermannii var. humilius (S.Stokes) Reveal, Eriogonum heermannii var. occidentale S.Stokes, Eriogonum heermannii var. sulcatum (S.Watson) Munz & Reveal, Eriogonum heracleoides var. heracleoides, Eriogonum hirtellum Howell & Bacig., Eriogonum hirtiflorum A.Gray ex S.Watson, Eriogonum hoffmannii S.Stokes, Eriogonum hoffmannii var. robustius S.Stokes, Eriogonum hookeri S.Watson, Eriogonum incanum Torr. & A.Gray, Eriogonum inerme (S.Watson) Jeps., Eriogonum inerme var. hispidulum Goodman, Eriogonum inflatum Torr., Eriogonum intrafractum Coville & Morton, Eriogonum kelloggii A.Gray, Eriogonum kennedyi Porter ex S.Watson, Eriogonum kennedyi var. alpigenum (Munz & I.M.Johnst.) Munz & I.M.Johnst., Eriogonum kennedyi var. austromontanum Munz & I.M.Johnst., Eriogonum kennedyi var. pinicola Reveal, Eriogonum kennedyi var. purpusii (Brandegee) Reveal, Eriogonum latens Jeps., Eriogonum latifolium Sm., Eriogonum libertini Reveal, Eriogonum lobbii Torr. & A.Gray, Eriogonum luteolum Greene, Eriogonum luteolum var. caninum (Greene) Reveal, Eriogonum luteolum var. pedunculatum (S.Stokes) Reveal, Eriogonum luteolum var. saltuarium Reveal, Eriogonum maculatum A.Heller, Eriogonum marifolium A.Gray, Eriogonum mensicola S.Stokes, Eriogonum mohavense S.Watson, Eriogonum molestum S.Watson, Eriogonum nervulosum (S.Stokes) Reveal, Eriogonum nidularium Coville, Eriogonum nortonii Greene, Eriogonum nudum Douglas ex Benth., Eriogonum nudum var. auriculatum (Benth.) J.P.Tracy ex Jeps., Eriogonum nudum var. decurrens (S.Stokes) M.L.Bowerman, Eriogonum nudum var. deductum (Greene) Jeps., Eriogonum nudum var. indictum (Jeps.) Reveal, Eriogonum nudum var. murinum Reveal, Eriogonum nudum var. oblongifolium S.Watson, Eriogonum nudum var. paralinum Reveal, Eriogonum nudum var. pauciflorum S.Watson, Eriogonum nudum var. psychicola Reveal, Eriogonum nudum var. pubiflorum Benth., Eriogonum nudum var. regirivum Reveal & J.C.Stebbins, Eriogonum nudum var. scapigerum (Eastw.) Jeps., Eriogonum nudum var. westonii (S.Stokes) J.T.Howell, Eriogonum nummulare M.E.Jones, Eriogonum nutans Torr. & A.Gray, Eriogonum nutans var. glabratum Reveal, Eriogonum ordii S.Watson, Eriogonum ovalifolium Nutt., Eriogonum ovalifolium var. caelestinum Reveal, Eriogonum ovalifolium var. depressum Blank., Eriogonum ovalifolium var. eximium (Tidestr.) J.T.Howell, Eriogonum ovalifolium var. monarchense D.A.York, Eriogonum ovalifolium var. nivale (Canby ex Coville) M.E.Jones, Eriogonum ovalifolium var. purpureum (Nutt.) Durand, Eriogonum ovalifolium var. vineum (Small) A.Nelson, Eriogonum palmerianum Reveal, Eriogonum panamintense Morton, Eriogonum parishii S.Watson, Eriogonum parvifolium Sm., Eriogonum pendulum S.Watson, Eriogonum plumatella Durand & Hilg., Eriogonum polycladon Benth., Eriogonum polypodum Small, Eriogonum prattenianum Durand, Eriogonum prattenianum var. avium Reveal & Shevock, Eriogonum pusillum Torr. & A.Gray, Eriogonum pyrolifolium Hook. ex A.E.Murray, Eriogonum pyrolifolium var. coryphaeum Torr. & A.Gray, Eriogonum reniforme Torr. & Frém., Eriogonum rixfordii S.Stokes, Eriogonum roseum Durand & Hilg., Eriogonum rupinum Reveal, Eriogonum saxatile S.Watson, Eriogonum siskiyouense Small, Eriogonum spectabile B.L.Corbin, Reveal & R.Barron, Eriogonum spergulinum A.Gray, Eriogonum spergulinum var. pratense (S.Stokes) J.T.Howell, Eriogonum spergulinum var. reddingianum (M.E.Jones) J.T.Howell, Eriogonum sphaerocephalum Douglas ex Benth., Eriogonum sphaerocephalum var. halimioides (Gand.) S.Stokes, Eriogonum strictum Benth., Eriogonum strictum var. anserinum (Greene) S.Stokes, Eriogonum strictum var. proliferum (Torr. & A.Gray) C.L.Hitchc., Eriogonum temblorense J.T.Howell & Twisselm., Eriogonum ternatum Howell, Eriogonum thomasii Torr., Eriogonum thurberi Torr., Eriogonum trichopes Torr., Eriogonum tripodum Greene, Eriogonum truncatum A.Gray, Eriogonum umbellatum Torr., Eriogonum umbellatum var. ahartii Reveal, Eriogonum umbellatum var. argus Reveal, Eriogonum umbellatum var. bahiiforme (Torr. & A.Gray) Jeps., Eriogonum umbellatum var. chlorothamnus Reveal, Eriogonum umbellatum var. covillei (Small) Munz & Reveal, Eriogonum umbellatum var. dichrocephalum Gand., Eriogonum umbellatum var. furcosum Reveal, Eriogonum umbellatum var. glaberrimum (Gand.) Reveal, Eriogonum umbellatum var. goodmanii Reveal, Eriogonum umbellatum var. humistratum Reveal, Eriogonum umbellatum var. juniporinum Reveal, Eriogonum umbellatum var. lautum Reveal, Eriogonum umbellatum var. minus I.M.Johnst., Eriogonum umbellatum var. munzii Reveal, Eriogonum umbellatum var. nevadense Gand., Eriogonum umbellatum var. polyanthum (Benth.) M.E.Jones, Eriogonum umbellatum var. speciosum (Drew) S.Stokes, Eriogonum umbellatum var. subaridum S.Stokes, Eriogonum umbellatum var. torreyanum (A.Gray) M.E.Jones, Eriogonum umbellatum var. versicolor S.Stokes, Eriogonum ursinum S.Watson, Eriogonum ursinum var. erubescens Reveal & J.D.Knorr, Eriogonum vestitum Howell, Eriogonum vimineum Douglas ex Benth., Eriogonum viridescens A.Heller, Eriogonum wrightii Torr. ex Benth., Eriogonum wrightii var. membranaceum S.Stokes ex Jeps., Eriogonum wrightii var. nodosum (Small) Reveal, Eriogonum wrightii var. olanchense (J.T.Howell) Reveal, Eriogonum wrightii var. subscaposum S.Watson, Eriogonum wrightii var. trachygonum (Torr. ex Benth.) Jeps., Erioneuron pilosum (Buckley) Nash, Eriophorum gracile W.D.J.Koch, Eriophyllum ambiguum (A.Gray) A.Gray, Eriophyllum ambiguum var. ambiguum, Eriophyllum ambiguum var. paleaceum (Brandegee) Ferris, Eriophyllum confertiflorum (DC.) A.Gray, Eriophyllum congdonii Brandegee, Eriophyllum jepsonii Greene, Eriophyllum lanatum (Pursh) Forbes, Eriophyllum lanatum var. arachnoideum (Fisch. & Avé-Lall.) Jeps., Eriophyllum lanatum var. croceum (Greene) Jeps., Eriophyllum lanatum var. grandiflorum (A.Gray) Jeps., Eriophyllum lanatum var. hallii Constance, Eriophyllum lanatum var. integrifolium (Hook.) Bailey, Eriophyllum lanatum var. lanceolatum (Howell) Jeps., Eriophyllum lanatum var. obovatum (Greene) H.M.Hall, Eriophyllum latilobum Rydb., Eriophyllum mohavense (I.M.Johnst.) Jeps., Eriophyllum multicaule (DC.) A.Gray, Eriophyllum nubigenum Greene ex A.Gray, Eriophyllum pringlei A.Gray, Erodium botrys (Cav.) Bertol., Erodium brachycarpum (Godr.) Thell., Erodium cicutarium (L.) L'Hér., Erodium cygnorum Nees, Erodium malacoides (L.) L'Hér., Erodium moschatum (L.) L'Hér., Erodium texanum A.Gray, Erucastrum gallicum (Willd.) O.E.Schulz, Eryngium alismifolium Greene, Eryngium aristulatum Jeps., Eryngium aristulatum var. hooveri M.Y.Sheikh, Eryngium aristulatum subsp. parishii (J.M.Coult. & Rose) R.M.Beauch., Eryngium armatum (S.Watson) J.M.Coult. & Rose, Eryngium articulatum Hook., Eryngium castrense Jeps., Eryngium constancei M.Y.Sheikh, Eryngium mathiasiae M.Y.Sheikh, Eryngium pendletonense K.L.Marsden & M.G.Simpson, Eryngium pinnatisectum Jeps., Eryngium racemosum Jeps., Eryngium spinosepalum Mathias, Eryngium vaseyi J.M.Coult. & Rose, Erysimum ammophilum A.Heller, Erysimum capitatum (Douglas ex Hook.) Greene, Erysimum capitatum var. purshii (Durand) R.C.Rollins, Erysimum cheiranthoides L., Erysimum cheiri (L.) Crantz, Erysimum concinnum Eastw., Erysimum franciscanum Rossbach, Erysimum insulare Greene, Erysimum menziesii (Benth. & Hook.f.) Wettst., Erysimum perenne (S.Watson ex Coville) Abrams, Erysimum repandum L., Erysimum suffrutescens (Abrams) Rossbach, Erysimum teretifolium Eastw., Erythranthe arvensis (Greene) G.L.Nesom, Erythranthe barbata (Greene) N.S.Fraga, Erythranthe calcicola N.S.Fraga & D.A.York, Erythranthe carsonensis N.S.Fraga, Erythranthe discolor (A.L.Grant) N.S.Fraga, Erythranthe filicifolia (Sexton, K.G.Ferris & Schoenig) G.L.Nesom, Erythranthe floribunda (Lindl.) G.L.Nesom, Erythranthe hardhamiae N.S.Fraga, Erythranthe marmorata (Greene) G.L.Nesom, Erythranthe microphylla (Benth.) G.L.Nesom, Erythranthe montioides (A.Gray) N.S.Fraga, Erythranthe moschata (Douglas ex Lindl.) G.L.Nesom, Erythranthe percaulis G.L.Nesom, Erythranthe rhodopetra N.S.Fraga, Erythranthe sierrae N.S.Fraga, Erythranthe taylorii G.L.Nesom, Erythranthe trinitiensis G.L.Nesom, Erythranthe utahensis (Pennell) G.L.Nesom, Erythronium californicum Purdy, Erythronium citrinum S.Watson, Erythronium helenae Applegate, Erythronium hendersonii S.Watson, Erythronium klamathense Applegate, Erythronium oregonum Applegate, Erythronium pluriflorum Shevock, Bartel & G.A.Allen, Erythronium purpurascens S.Watson, Erythronium pusaterii (Munz & J.T.Howell) Shevock, Bartel & G.A.Allen, Erythronium revolutum Sm., Erythronium shastense D.A.York, J.K.Nelson & D.W.Taylor, Erythronium taylorii Shevock & G.A.Allen, Erythronium tuolumnense Applegate, Eschscholzia caespitosa Benth., Eschscholzia californica Cham., Eschscholzia glyptosperma Greene, Eschscholzia hypecoides Benth., Eschscholzia lemmonii Greene, Eschscholzia lobbii Greene, Eschscholzia minutiflora S.Watson, Eschscholzia parishii Greene, Eschscholzia ramosa (Greene) Greene, Eschscholzia rhombipetala Greene, Eucalyptus camaldulensis Dehn., Eucalyptus cladocalyx F.Muell., Eucalyptus globulus Labill., Eucalyptus polyanthemos Schauer, Eucalyptus sideroxylon A.Cunn. ex Woolls, Eucalyptus tereticornis Sm., Eucalyptus viminalis Labill., Euchiton gymnocephalus (DC.) Holub, Euchiton involucratus (G.Forst.) Holub, Euchiton sphaericus (Willd.) Holub, Euclidium syriacum (L.) W.T.Aiton, Eucnide rupestris (Baill.) H.J.Thomps. & W.R.Ernst, Eucnide urens (Parry ex A.Gray) Parry, Eucrypta chrysanthemifolia (Benth.) Greene, Eucrypta chrysanthemifolia var. bipinnatifida (Torr.) Constance, Eucrypta micrantha (Torr.) A.Heller, Euonymus occidentalis subsp. occidentalis, Euonymus occidentalis var. occidentalis, Euonymus occidentalis subsp. parishii (Trel.) R.M.Beauch., Euphorbia crenulata Engelm., Euphorbia davidii Subils, Euphorbia dentata Michx., Euphorbia eriantha Benth., Euphorbia helioscopia L., Euphorbia jaegeri V.W.Steinm. & J.M.André, Euphorbia lathyris L., Euphorbia misera Benth., Euphorbia myrsinites L., Euphorbia oblongata Griseb., Euphorbia peplus L., Euphorbia spathulata Lam., Euphorbia terracina L., Eurybia integrifolia (Nutt.) G.L.Nesom, Eurybia merita (A.Nelson) G.L.Nesom, Eurybia radulina (A.Gray) G.L.Nesom, Euthamia occidentalis Nutt., Fagonia laevis Standl., Fagonia pachyacantha Rydb., Fallopia baldschuanica (Regel) Holub, Fallopia convolvulus (L.) Á.Löve, Fallugia paradoxa Endl., Fendlerella utahensis (S.Watson) A.Heller, Ferocactus cylindraceus (Engelm.) Orcutt, Ferocactus viridescens (Torr. & A.Gray) Britton & Rose, Festuca californica Vasey, Festuca elmeri Scribn. & Merr., Festuca idahoensis Elmer, Festuca kingii (S.Watson) Cassidy, Festuca minutiflora Rydb., Festuca occidentalis Hook., Festuca rubra L., Festuca saximontana Rydb., Festuca subulata Trin., Festuca subuliflora Scribn., Festuca trachyphylla (Hack.) Hack., Festuca viridula Vasey, Ficus carica L., Fimbristylis autumnalis (L.) Roem. & Schult., Fimbristylis thermalis S.Watson, Fimbristylis vahlii (Lam.) Link, Flaveria trinervia (Spreng.) C.Mohr, Floerkea proserpinacoides Willd., Foeniculum vulgare Mill., Forestiera pubescens Nutt., Fragaria chiloensis (L.) Duchesne, Fragaria vesca L., Fragaria virginiana Duchesne, Frangula californica (Eschsch.) A.Gray, Frangula purshiana (DC.) J.G.Cooper, Frangula rubra (Greene) Grubov, Frankenia palmeri S.Watson, Frankenia pulverulenta L., Frankenia salina (Molina) I.M.Johnst., Frasera albicaulis Douglas ex Griseb., Frasera albicaulis var. modocensis (H.St.John) Holmgren, Frasera albicaulis var. nitida (Benth.) C.L.Hitchc., Frasera albomarginata S.Watson, Frasera neglecta H.M.Hall, Frasera parryi Torr., Frasera puberulenta Davidson, Frasera speciosa Douglas ex Hook., Frasera tubulosa Coville, Fraxinus anomala Torr. ex S.Watson, Fraxinus dipetala Hook. & Arn., Fraxinus latifolia Benth., Fraxinus velutina Torr., Fremontodendron californicum (Torr.) Coult., Fremontodendron decumbens R.M.Lloyd, Fremontodendron mexicanum Davidson, Fritillaria affinis (Schult. & Schult.f.) Sealy, Fritillaria agrestis Greene, Fritillaria atropurpurea Nutt., Fritillaria biflora Lindl., Fritillaria biflora var. biflora, Fritillaria biflora var. ineziana Jeps., Fritillaria brandegeei Eastw., Fritillaria eastwoodiae R.M.Macfarl., Fritillaria falcata (Jeps.) D.E.Beetle, Fritillaria gentneri Gilkey, Fritillaria glauca Greene, Fritillaria liliacea Lindl., Fritillaria micrantha A.Heller, Fritillaria ojaiensis Davidson, Fritillaria pinetorum Davidson, Fritillaria pluriflora Torr. ex Benth., Fritillaria pudica (Pursh) Spreng., Fritillaria purdyi Eastw., Fritillaria recurva Benth., Fritillaria striata Eastw., Fritillaria viridea Kellogg, Fumaria capreolata L., Fumaria officinalis L., Fumaria parviflora Lam., Gaillardia aristata Pursh, Gaillardia pulchella Foug., Galinsoga parviflora var. parviflora, Galium andrewsii A.Gray, Galium angustifolium Nutt., Galium aparine L., Galium argense Dempster & Ehrend., Galium bifolium S.Watson, Galium bolanderi A.Gray, Galium boreale L., Galium buxifolium Greene, Galium californicum Hook. & Arn., Galium catalinense A.Gray, Galium clementis Eastw., Galium cliftonsmithii (Dempster) Dempster & Stebbins, Galium divaricatum Pourr. ex Lam., Galium glabrescens (Ehrend.) Dempster & Ehrend., Galium grande McClatchie, Galium grayanum Ehrend., Galium grayanum var. grayanum, Galium grayanum var. nanum Dempster & Ehrend., Galium hallii Munz & I.M.Johnst., Galium hardhamiae Dempster, Galium hilendiae Dempster & Ehrend., Galium hypotrichium A.Gray, Galium jepsonii Hilend & J.T.Howell, Galium johnstonii Dempster & Stebbins, Galium magnifolium (Dempster) Dempster, Galium matthewsii A.Gray, Galium mollugo L., Galium multiflorum Kellogg, Galium munzii Hilend & J.T.Howell, Galium murale (L.) All., Galium muricatum W.Wight, Galium nuttallii A.Gray, Galium oreganum Britton, Galium parishii Hilend & J.T.Howell, Galium parisiense L., Galium porrigens Dempster, Galium porrigens var. porrigens, Galium porrigens var. tenue (Dempster) Dempster, Galium proliferum A.Gray, Galium serpenticum Dempster, Galium sparsiflorum W.Wight, Galium stellatum Kellogg, Galium tricornutum Dandy, Galium trifidum L., Galium triflorum Michx., Galium wrightii A.Gray, Gambelia speciosa Nutt., Gamochaeta argyrinea G.L.Nesom, Gamochaeta pensylvanica (Willd.) Cabrera, Gamochaeta ustulata (Nutt.) Holub, Garrya buxifolia A.Gray, Garrya congdonii Eastw., Garrya elliptica Douglas ex Lindl., Garrya flavescens S.Watson, Garrya fremontii Torr., Garrya veatchii Kellogg, Gaultheria humifusa (Graham) Rydb., Gaultheria ovatifolia A.Gray, Gaultheria shallon Pursh, Gayophytum decipiens F.H.Lewis & Szweyk., Gayophytum diffusum Torr. & A.Gray, Gayophytum eriospermum Coville, Gayophytum heterozygum F.H.Lewis & Szweyk., Gayophytum humile Juss., Gayophytum oligospermum F.H.Lewis & Szweyk., Gayophytum racemosum Nutt. ex Torr. & A.Gray, Gayophytum ramosissimum Torr. & A.Gray, Gazania linearis (Thunb.) Druce, Genista canariensis L., Genista linifolia L., Genista monspessulana (L.) L.A.S.Johnson, Gentiana calycosa Griseb., Gentiana fremontii Torr., Gentiana newberryi A.Gray, Gentiana newberryi var. tiogana (A.Heller) J.S.Pringle, Gentiana plurisetosa C.T.Mason, Gentiana prostrata Haenke, Gentiana sceptrum Griseb., Gentiana setigera A.Gray, Gentianopsis holopetala (A.Gray) Iltis, Gentianopsis simplex (A.Gray) Iltis, Geraea canescens Torr. & A.Gray, Geraea viscida (A.Gray) S.F.Blake, Geranium aequale (Bab.) Aedo, Geranium bicknellii Britton, Geranium californicum G.N.Jones & F.F.Jones, Geranium carolinianum L., Geranium columbinum L., Geranium dissectum L., Geranium lucidum L., Geranium molle L., Geranium oreganum Howell, Geranium palmatum Cav., Geranium potentilloides L'Hér. ex DC., Geranium pusillum L., Geranium pyrenaicum Burm.f., Geranium richardsonii Fisch. & Trautv., Geranium robertianum L., Geranium rotundifolium L., Geranium solanderi Carolin, Geranium texanum (Trel.) A.Heller, Geranium viscosissimum Fisch. & C.A.Mey., Geum aleppicum Jacq., Geum macrophyllum Willd., Geum macrophyllum subsp. macrophyllum, Geum macrophyllum var. macrophyllum, Geum macrophyllum subsp. perincisum Scheutz, Geum macrophyllum var. perincisum (Rydb.) Raup, Geum triflorum var. ciliatum (Pursh) Fassett, Gilia achilleifolia Benth., Gilia aliquanta A.D.Grant & V.E.Grant, Gilia angelensis V.E.Grant, Gilia brecciarum M.E.Jones, Gilia cana (M.E.Jones) A.Heller, Gilia capitata Sims, Gilia clivorum (Jeps.) V.E.Grant, Gilia clokeyi H.Mason, Gilia diegensis (Munz) A.D.Grant & V.E.Grant, Gilia inconspicua (Sm.) Sweet, Gilia interior (H.Mason & A.D.Grant) A.D.Grant, Gilia latiflora (A.Gray) A.Gray, Gilia leptantha Parish, Gilia malior Day & V.E.Grant, Gilia millefoliata Fisch. & C.A.Mey., Gilia minor A.D.Grant & V.E.Grant, Gilia modocensis Eastw., Gilia nevinii A.Gray ex Lyon, Gilia ochroleuca M.E.Jones, Gilia ophthalmoides Brand, Gilia salticola Eastw., Gilia scopulorum M.E.Jones, Gilia sinuata Douglas ex Benth., Gilia stellata A.Heller, Gilia tenuiflora Benth., Gilia transmontana (H.Mason & A.D.Grant) A.D.Grant & V.E.Grant, Gilia tricolor Benth., Gilia yorkii Shevock & A.G.Day, Gilmania luteola (Coville) Coville, Githopsis diffusa A.Gray, Githopsis pulchella Vatke, Githopsis pulchella subsp. pulchella, Githopsis pulchella var. pulchella, Githopsis specularioides Nutt., Githopsis tenella Morin, Glaucium flavum Crantz, Glechoma hederacea L., Gleditsia triacanthos L., Glinus lotoides L., Glinus radiatus (Ruiz & Pav.) Rohrb., Glossopetalon pungens Brandegee, Glossopetalon spinescens var. aridum M.E.Jones, Glyceria borealis (Nash) Batch., Glyceria declinata Bréb., Glyceria elata (Nash) M.E.Jones, Glyceria fluitans (L.) R.Br., Glyceria grandis S.Watson, Glyceria leptostachya Buckley, Glyceria striata (Lam.) Hitchc., Glycyrrhiza glabra L., Glycyrrhiza lepidota Pursh, Glyptopleura marginata Eaton, Glyptopleura setulosa A.Gray, Gnaphalium palustre Nutt., Goodmania luteola (Parry) Reveal & Ertter, Goodyera oblongifolia Raf., Gossypium hirsutum L., Gratiola ebracteata Benth. ex A.DC., Gratiola heterosepala H.Mason & Bacigalupo, Gratiola neglecta Torr., Grayia spinosa (Hook.) Moq., Grevillea robusta A.Cunn. ex R.Br., Grindelia fraxinipratensis Reveal & Beatley, Grindelia hirsutula Hook. & Arn., Grindelia stricta var. stricta, Guilleminea densa var. aggregata Uline & W.L.Bray, Gunnera tinctoria (Molina) Mirb., Gutierrezia californica (DC.) Torr. & A.Gray, Gutierrezia microcephala (DC.) A.Gray, Gutierrezia sarothrae (Pursh) Britton & Rusby, Gymnosteris parvula (Rydb.) A.Heller, Gypsophila elegans M.Bieb., Gypsophila paniculata L., Gypsophila scorzonerifolia Ser., Hackelia amethystina J.T.Howell, Hackelia bella (J.F.Macbr.) I.M.Johnst., Hackelia brevicula (Jeps.) J.L.Gentry, Hackelia californica (A.Gray) I.M.Johnst., Hackelia cusickii (Piper) Brand, Hackelia floribunda (Lehm.) I.M.Johnst., Hackelia micrantha (Eastw.) J.L.Gentry, Hackelia mundula (Jeps.) Ferris, Hackelia nervosa (Kellogg) I.M.Johnst., Hackelia setosa (Piper) I.M.Johnst., Hackelia sharsmithii I.M.Johnst., Hackelia velutina (Piper) I.M.Johnst., Hainardia cylindrica (Willd.) Greuter, Halogeton glomeratus (M.Bieb.) C.A.Mey., Harmonia guggolziorum B.G.Baldwin, Harpagonella palmeri A.Gray, Hastingsia alba (Durand) S.Watson, Hazardia brickellioides (S.F.Blake) W.D.Clark, Hazardia cana (A.Gray) Greene, Hazardia detonsa (Greene) Greene, Hazardia orcuttii (A.Gray) Greene, Hazardia squarrosa (Hook. & Arn.) Greene, Hazardia squarrosa var. grindelioides (DC.) W.D.Clark, Hazardia squarrosa var. obtusa (Greene) Jeps., Hazardia squarrosa var. squarrosa, Hazardia stenolepis (H.M.Hall) Hoover, Hazardia whitneyi (A.Gray) Greene, Hazardia whitneyi var. discoidea (J.T.Howell) W.D.Clark, Hazardia whitneyi var. whitneyi, Hecastocleis shockleyi A.Gray, Hedeoma drummondii Benth., Hedera helix L., Hedychium flavescens Carey ex Roscoe, Helenium amarum var. amarum, Helenium autumnale L., Helenium bigelovii A.Gray, Helenium bolanderi A.Gray, Helenium puberulum DC., Helianthella californica A.Gray, Helianthella californica subsp. californica, Helianthella californica subsp. nevadensis (Greene) W.A.Weber, Helianthella californica subsp. shastensis (W.A.Weber) W.A.Weber, Helianthella castanea Greene, Helianthus annuus L., Helianthus bolanderi A.Gray, Helianthus californicus DC., Helianthus ciliaris DC., Helianthus cusickii A.Gray, Helianthus gracilentus A.Gray, Helianthus inexpectatus D.J.Keil & Elvin, Helianthus nuttallii Torr. & A.Gray, Helianthus petiolaris Nutt., Helianthus winteri J.C.Stebbins, Heliomeris multiflora var. nevadensis (A.Nelson) Yates, Heliotropium amplexicaule Vahl, Heliotropium curassavicum var. oculatum (A.Heller) I.M.Johnst. ex Tidestr., Heliotropium europaeum L., Hemitomes congestum A.Gray, Herissantia crispa (L.) Brizicky, Hesperevax acaulis (Kellogg) Greene, Hesperevax acaulis var. acaulis, Hesperevax acaulis var. ambusticola Morefield, Hesperevax acaulis var. robustior Morefield, Hesperevax caulescens (Benth.) A.Gray, Hesperevax sparsiflora (A.Gray) Greene, Hesperevax sparsiflora var. brevifolia (A.Gray) Morefield, Hesperevax sparsiflora var. sparsiflora, Hesperis matronalis L., Hesperocallis undulata A.Gray, Hesperochiron californicus (Benth.) S.Watson, Hesperochiron pumilus (Griseb.) Porter, Hesperocnide tenella Torr., Hesperolinon adenophyllum (A.Gray) Small, Hesperolinon bicarpellatum (H.Sharsm.) H.Sharsm., Hesperolinon breweri (A.Gray) Small, Hesperolinon californicum (Benth.) Small, Hesperolinon clevelandii (Greene) Small, Hesperolinon congestum (A.Gray) Small, Hesperolinon didymocarpum H.Sharsm., Hesperolinon disjunctum H.Sharsm., Hesperolinon drymarioides (Curran) Small, Hesperolinon micranthum (A.Gray) Small, Hesperolinon spergulinum (A.Gray) Small, Hesperolinon tehamense H.Sharsm., Heteranthera dubia (Jacq.) MacMill., Heteranthera limosa (Sw.) Willd., Heterocodon rariflorum Nutt., Heteromeles arbutifolia (Lindl.) M.Roem., Heteropogon contortus (L.) P.Beauv. ex Roem. & Schult., Heterotheca grandiflora Nutt., Heterotheca monarchensis D.A.York, Shevock & Semple, Heterotheca oregona (Nutt.) Shinners, Heterotheca oregona var. compacta (D.D.Keck) Semple, Heterotheca sessiliflora (Nutt.) Shinners, Heterotheca shevockii (Semple) Semple, Heterotheca villosa (Pursh) Shinners, Heuchera abramsii Rydb., Heuchera brevistaminea Wiggins, Heuchera caespitosa Eastw., Heuchera cylindrica Douglas, Heuchera hirsutissima Rosend. & Lakela, Heuchera maxima Greene, Heuchera merriamii Eastw., Heuchera micrantha Douglas, Heuchera parishii Rydb., Heuchera parvifolia Nutt. ex Torr. & A.Gray, Heuchera pilosissima Fisch. & C.A.Mey., Heuchera rubescens Torr., Hibiscus denudatus Benth., Hibiscus trionum L., Hieracium albiflorum Hook., Hieracium argutum Nutt., Hieracium bolanderi A.Gray, Hieracium greenei A.Gray, Hieracium horridum Fr., Hieracium parryi Zahn, Hieracium scouleri Hook., Hieracium triste Willd. ex Spreng., Hippuris vulgaris L., Hirschfeldia incana (L.) Lagr.-Foss., Hoffmannseggia glauca (Ortega) Eifert, Hoffmannseggia microphylla Torr., Hoita macrostachya (DC.) Rydb., Hoita orbicularis (Lindl.) Rydb., Hoita strobilina (Hook. & Arn.) Rydb., Holcus lanatus L., Holcus mollis L., Hollisteria lanata S.Watson, Holmgrenanthe petrophila (Coville & C.V.Morton) Elisens, Holocarpha heermannii (Greene) D.D.Keck, Holocarpha macradenia (DC.) Greene, Holocarpha obconica (J.C.Clausen & D.D.Keck) D.D.Keck, Holocarpha virgata (A.Gray) D.D.Keck, Holodiscus discolor (Pursh) Maxim., Holozonia filipes (Hook. & Arn.) Greene, Hordeum arizonicum Covas, Hordeum brachyantherum Nevski, Hordeum depressum (Scribn. & J.G.Sm.) Rydb., Hordeum murinum L., Hordeum vulgare L., Horkelia bolanderi A.Gray, Horkelia californica Cham. & Schltdl., Horkelia cuneata Lindl., Horkelia daucifolia (Greene) Rydb., Horkelia daucifolia var. indicta (Jeps.) Ertter & Reveal, Horkelia fusca Lindl., Horkelia hendersonii Howell, Horkelia hispidula Rydb., Horkelia marinensis (Elmer) Crum ex D.D.Keck, Horkelia parryi Greene, Horkelia rydbergii Elmer, Horkelia sericata S.Watson, Horkelia tenuiloba (Torr.) A.Gray, Horkelia tridentata Torr., Horkelia truncata Rydb., Horkelia tularensis (Howell) Munz, Horkelia wilderae Parish, Horkelia yadonii Ertter, Horkeliella congdonis (Rydb.) Rydb., Horkeliella purpurascens (S.Watson) Rydb., Horsfordia alata (S.Watson) A.Gray, Horsfordia newberryi (S.Watson) A.Gray, Howellia aquatilis A.Gray, Hulsea algida A.Gray, Hulsea brevifolia A.Gray, Hulsea californica A.Gray, Hulsea heterochroma A.Gray, Hulsea mexicana Rydb., Hulsea nana A.Gray, Hulsea vestita A.Gray, Humulus lupulus L., Hydrilla verticillata (L.f.) Royle, Hydrocotyle ranunculoides L.fil., Hydrocotyle umbellata L., Hydrocotyle verticillata Thunb., Hydrophyllum fendleri var. albifrons (A.Heller) J.F.Macbr., Hydrophyllum occidentale (S.Watson) A.Gray, Hydrophyllum tenuipes A.Heller, Hymenopappus filifolius var. eriopodus (A.Nelson) B.L.Turner, Hymenopappus filifolius var. lugens (Greene) Jeps., Hymenopappus filifolius var. megacephalus B.L.Turner, Hymenopappus filifolius var. nanus (Rydb.) B.L.Turner, Hymenothrix loomisii S.F.Blake, Hymenothrix wrightii A.Gray, Hymenoxys cooperi (A.Gray) Cockerell, Hymenoxys lemmonii (Greene) Cockerell, Hymenoxys odorata DC., Hyparrhenia hirta (L.) Stapf, Hypericum anagalloides Cham. & Schltdl., Hypericum calycinum L., Hypericum canariense L., Hypericum concinnum Benth., Hypericum scouleri Hook., Hypochaeris glabra L., Hypochaeris radicata L., Iberis umbellata L., Idahoa scapigera (Hook.) A.Nelson & J.F.Macbr., Ilex aquifolium L., Iliamna bakeri (Jeps.) Wiggins, Iliamna latibracteata Wiggins, Iliamna rivularis (Douglas ex Hook.) Greene, Impatiens balfourii Hook.fil., Impatiens capensis Meerb., Impatiens glandulifera Royle, Imperata brevifolia Vasey, Ionactis alpina (Nutt.) Greene, Ipheion uniflorum (Graham) Raf., Ipomoea cairica (L.) Sweet, Ipomoea hederacea Jacq., Ipomoea indica (Burm.) Merr., Ipomoea purpurea (L.) Roth, Ipomoea triloba L., Ipomopsis aggregata (Pursh) V.E.Grant, Ipomopsis arizonica (Greene) Wherry, Ipomopsis congesta (Hook.) V.E.Grant, Ipomopsis effusa (A.Gray) Moran, Ipomopsis polycladon (Torr.) V.E.Grant, Ipomopsis tenuifolia (A.Gray) V.E.Grant, Ipomopsis tenuituba (Rydb.) V.E.Grant, Iris bracteata S.Watson, Iris chrysophylla Howell, Iris douglasiana Herb., Iris fernaldii R.C.Foster, Iris ×germanica L., Iris hartwegii Baker, Iris innominata L.F.Hend., Iris longipetala Herb., Iris macrosiphon Torr., Iris missouriensis Nutt., Iris munzii R.C.Foster, Iris pseudacorus L., Iris purdyi Eastw., Iris tenuissima Dykes, Iris ×thompsonii R.C.Foster, Isatis tinctoria L., Isocoma acradenia (Greene) Greene, Isocoma acradenia var. acradenia, Isocoma acradenia var. bracteosa (Greene) G.L.Nesom, Isocoma acradenia var. eremophila (Greene) G.L.Nesom, Isocoma arguta Greene, Isocoma menziesii (Hook. & Arn.) G.L.Nesom, Isocoma menziesii var. decumbens (Greene) G.L.Nesom, Isocoma menziesii var. diabolica G.L.Nesom, Isocoma menziesii var. menziesii, Isocoma menziesii var. sedoides (Greene) G.L.Nesom, Isocoma menziesii var. vernonioides (Nutt.) G.L.Nesom, Isoetes bolanderi Engelm., Isoetes echinospora Durand, Isoetes howellii Engelm., Isoetes nuttallii A.Braun ex Engelm., Isoetes occidentalis Hend., Isoetes orcuttii Eaton, Isolepis carinata Hook. & Arn. ex Torr., Isolepis cernua (Vahl) Roem. & Schult., Isolepis setacea (L.) R.Br., Iva axillaris Pursh, Iva hayesiana A.Gray, Ivesia aperta (Howell) Munz, Ivesia aperta var. canina Ertter, Ivesia argyrocoma var. argyrocoma, Ivesia baileyi S.Watson, Ivesia baileyi var. beneolens (A.Nelson & J.F.Macbr.) Ertter, Ivesia callida (H.M.Hall) Rydb., Ivesia campestris (M.E.Jones) Rydb., Ivesia gordonii (Hook.) Torr. & A.Gray, Ivesia gordonii var. alpicola (Rydb. ex Howell) Ertter & Reveal, Ivesia gordonii var. ursinorum (Jeps.) Ertter & Reveal, Ivesia jaegeri Munz & I.M.Johnst., Ivesia longibracteata Ertter, Ivesia lycopodioides A.Gray, Ivesia muirii A.Gray, Ivesia paniculata T.W.Nelson & J.P.Nelson, Ivesia patellifera (J.T.Howell) Ertter, Ivesia pickeringii Torr., Ivesia pygmaea A.Gray, Ivesia santolinoides A.Gray, Ivesia saxosa (Lemmon & S.A.Lemmon ex Greene) Ertter, Ivesia sericoleuca (Rydb.) Rydb., Ivesia shockleyi var. shockleyi, Ivesia unguiculata A.Gray, Ivesia webberi A.Gray, Ixia maculata L., Jacaranda mimosifolia D.Don, Jamesia americana var. rosea J.A.Purpus ex C.K.Schneid., Jaumea carnosa (Less.) A.Gray, Jepsonia heterandra Eastw., Jepsonia malvifolia (Greene) Small, Jepsonia parryi (Torr.) Small, Johanneshowellia puberula (S.Watson) Reveal, Juglans californica S.Watson, Juglans hindsii (Jeps.) Jeps. ex R.E.Sm., Juglans regia L., Juncus acuminatus Michx., Juncus bolanderi Engelm., Juncus breweri Engelm., Juncus bryoides F.J.Herm., Juncus bufonius L., Juncus bufonius var. occidentalis F.J.Herm., Juncus bulbosus L., Juncus capillaris F.J.Herm., Juncus capitatus Weigel, Juncus chlorocephalus Engelm., Juncus confusus Coville, Juncus cooperi Engelm., Juncus covillei Piper, Juncus cyperoides Laharpe, Juncus dichotomus Elliott, Juncus diffusissimus Buckley, Juncus digitatus C.W.Witham & Zika, Juncus drummondii E.Mey., Juncus dubius Engelm., Juncus dudleyi Wiegand, Juncus duranii Ewan, Juncus effusus L., Juncus elliottii Chapm., Juncus ensifolius Wikstr., Juncus falcatus E.Mey., Juncus hemiendytus F.J.Herm., Juncus hemiendytus var. abjectus (F.J.Herm.) Ertter, Juncus hemiendytus var. hemiendytus, Juncus howellii F.J.Herm., Juncus interior Wiegand, Juncus kelloggii Engelm., Juncus laccatus Zika, Juncus leiospermus F.J.Herm., Juncus leiospermus var. ahartii Ertter, Juncus leiospermus var. leiospermus, Juncus longistylis Torr., Juncus luciensis Ertter, Juncus macrandrus Coville, Juncus macrophyllus Coville, Juncus marginatus Rostk., Juncus mertensianus Bong., Juncus nevadensis S.Watson, Juncus nevadensis var. inventus (L.F.Hend.) C.L.Hitchc., Juncus nodosus L., Juncus occidentalis Wiegand, Juncus orthophyllus Coville, Juncus oxymeris Engelm., Juncus parryi Engelm., Juncus patens E.Mey., Juncus phaeocephalus Engelm., Juncus phaeocephalus var. paniculatus Engelm., Juncus phaeocephalus var. phaeocephalus, Juncus planifolius R.Br., Juncus regelii Buchenau, Juncus rugulosus Engelm., Juncus saximontanus A.Nelson, Juncus supiniformis Engelm., Juncus tenuis Willd., Juncus textilis Buchenau, Juncus tiehmii Ertter, Juncus torreyi Coville, Juncus triformis Engelm., Juncus trilocularis Zika, Juncus uncialis Greene, Juncus xiphioides E.Mey., Juniperus californica Carrière, Juniperus communis L., Juniperus communis var. depressa Pursh, Juniperus occidentalis Hook., Juniperus osteosperma (Torr.) Little, Justicia californica (Benth.) D.N.Gibson, Kallstroemia californica (S.Watson) Vail, Kallstroemia grandiflora Torr. ex A.Gray, Kallstroemia parviflora Norton, Kalmia polifolia Wangenh., Keckiella antirrhinoides (Benth.) Straw, Keckiella breviflora (Lindl.) Straw, Keckiella cordifolia (Benth.) Straw, Keckiella corymbosa (Benth.) Straw, Keckiella lemmonii (A.Gray) Straw, Keckiella rothrockii (A.Gray) Straw, Keckiella ternata (Torr. ex A.Gray) Straw, Kelloggia galioides Torr., Kickxia elatine (L.) Dumort., Kickxia spuria (L.) Dumort., Kniphofia uvaria (L.) Oken, Koeberlinia spinosa var. tenuispina Kearney & Peebles, Koeleria macrantha (Ledeb.) Schult., Krameria erecta Willd. ex Schult., Lactuca biennis (Moench) Fernald, Lactuca canadensis L., Lactuca ludoviciana (Nutt.) Riddell, Lactuca saligna L., Lactuca serriola L., Lactuca virosa L., Laennecia coulteri (A.Gray) G.L.Nesom, Lagophylla diabolensis B.G.Baldwin, Lagophylla dichotoma Benth., Lagophylla glandulosa A.Gray, Lagophylla minor (D.D.Keck) D.D.Keck, Lagophylla ramosissima Nutt., Lagurus ovatus L., Lamarckia aurea (L.) Moench, Lamium amplexicaule L., Lamium purpureum L., Lantana camara L., Lantana montevidensis (Spreng.) Briq., Lappula squarrosa (Retz.) Dumort., Lapsana communis L., Larrea tridentata (DC.) Coult., Lastarriaea coriacea (Goodman) Hoover, Lasthenia burkei (Greene) Greene, Lasthenia californica DC. ex Lindl., Lasthenia chrysantha (Greene ex A.Gray) Greene, Lasthenia conjugens Greene, Lasthenia coronaria (Nutt.) Ornduff, Lasthenia debilis (Greene ex A.Gray) Ornduff, Lasthenia ferrisiae Ornduff, Lasthenia fremontii (Torr. ex A.Gray) Greene, Lasthenia glaberrima DC., Lasthenia glabrata Lindl., Lasthenia gracilis (DC.) Greene, Lasthenia leptalea (A.Gray) Ornduff, Lasthenia maritima (A.Gray) M.C.Vasey & Madroño., Lasthenia microglossa (DC.) Greene, Lasthenia minor (DC.) Ornduff, Lasthenia platycarpha (A.Gray) Greene, Lathyrus angulatus L., Lathyrus aphaca L., Lathyrus biflorus T.W.Nelson & J.P.Nelson, Lathyrus cicera L., Lathyrus delnorticus C.L.Hitchc., Lathyrus glandulosus Broich, Lathyrus hirsutus L., Lathyrus hitchcockianus Barneby & Reveal, Lathyrus japonicus Willd., Lathyrus jepsonii Greene, Lathyrus lanszwertii Kellogg, Lathyrus lanszwertii var. aridus (Piper) Jeps., Lathyrus lanszwertii var. lanszwertii, Lathyrus latifolius L., Lathyrus littoralis (Nutt.) Endl. ex Walp., Lathyrus odoratus L., Lathyrus palustris L., Lathyrus polyphyllus Nutt., Lathyrus rigidus T.G.White, Lathyrus sphaericus Retz., Lathyrus splendens Kellogg, Lathyrus sulphureus W.H.Brewer ex A.Gray, Lathyrus tingitanus L., Lathyrus torreyi A.Gray, Lathyrus vestitus Nutt., Laurus nobilis L., Layia carnosa (Nutt.) Torr. & A.Gray, Layia chrysanthemoides (DC.) A.Gray, Layia discoidea D.D.Keck, Layia fremontii (Torr. & A.Gray) A.Gray, Layia gaillardioides Hook. & Arn., Layia glandulosa (Hook.) Hook. & Arn., Layia heterotricha (DC.) Hook. & Arn., Layia hieracioides (DC.) Hook. & Arn., Layia jonesii A.Gray, Layia leucopappa D.D.Keck, Layia munzii D.D.Keck, Layia pentachaeta A.Gray, Layia platyglossa (Fisch. & C.A.Mey.) A.Gray, Layia septentrionalis D.D.Keck, Leersia oryzoides (L.) Sw., Lemna aequinoctialis Welw., Lemna gibba L., Lemna minor L., Lemna minuta Kunth, Lemna trisulca L., Lemna turionifera Landolt, Lemna valdiviana Phil., Lepechinia calycina (Benth.) Epling, Lepechinia cardiophylla Epling, Lepechinia fragrans (Greene) Epling, Lepechinia ganderi Epling, Lepechinia rossii S.Boyd & Mistretta, Lepidium campestre (L.) W.T.Aiton, Lepidium densiflorum Schrad., Lepidium dictyotum A.Gray, Lepidium flavum Torr., Lepidium fremontii S.Watson, Lepidium heterophyllum Benth., Lepidium jaredii Brandegee, Lepidium latifolium L., Lepidium latipes Hook., Lepidium montanum Nutt., Lepidium nitidum Nutt., Lepidium oblongum Small, Lepidium oxycarpum Torr. & A.Gray, Lepidium perfoliatum L., Lepidium pinnatifidum Ledeb., Lepidium ramosissimum A.Nelson, Lepidium strictum (S.Watson) Rattan, Lepidium thurberi Wooton, Lepidium virginicum L., Lepidospartum latisquamum S.Watson, Lepidospartum squamatum (A.Gray) A.Gray, Leptochloa fusca Linnaeus, 1753, Leptochloa viscida (Scribn.) Beal, Lessingia arachnoidea Greene, Lessingia germanorum Cham., Lessingia glandulifera A.Gray, Lessingia glandulifera var. glandulifera, Lessingia glandulifera var. tomentosa (Greene) Ferris, Lessingia hololeuca Greene, Lessingia leptoclada A.Gray, Lessingia micradenia Greene, Lessingia micradenia var. glabrata (D.D.Keck) Ferris, Lessingia micradenia var. micradenia, Lessingia nana A.Gray, Lessingia nemaclada Greene, Lessingia ramulosa A.Gray, Lessingia tenuis (A.Gray) Coville, Lessingia virgata A.Gray, Leucanthemum lacustre (Brot.) Samp., Leucanthemum maximum (Ramond) DC., Leucanthemum vulgare Lam., Leucocrinum montanum Nutt. ex A.Gray, Leucojum aestivum L., Leucosyris arida (B.L.Turner & D.B.Horne) Pruski & R.L.Hartm., Leucosyris carnosa (A.Gray) Pruski & R.L.Hartm., Leucothoe davisiae Torr. ex A.Gray, Lewisia brachycalyx Engelm. ex A.Gray, Lewisia cantelovii Howell, Lewisia congdonii (Rydb.) S.Clay, Lewisia cotyledon (S.Watson) B.L.Rob., Lewisia cotyledon var. heckneri (C.V.Morton) Munz, Lewisia cotyledon var. howellii (S.Watson) Jeps., Lewisia disepala Rydb., Lewisia kelloggii K.Brandegee, Lewisia leeana (Porter) B.L.Rob., Lewisia longipetala (Piper) Clay, Lewisia nevadensis (A.Gray) B.L.Rob., Lewisia oppositifolia (S.Watson) B.L.Rob., Lewisia pygmaea (A.Gray) B.L.Rob., Lewisia rediviva Pursh, Lewisia rediviva var. minor (Rydb.) Munz, Lewisia rediviva var. rediviva, Lewisia stebbinsii Gankin & W.R.Hildreth, Lewisia triphylla (S.Watson) B.L.Rob., Ligusticum californicum J.M.Coult. & Rose, Ligusticum grayi J.M.Coult. & Rose, Ligustrum japonicum Thunb., Ligustrum lucidum W.T.Aiton, Ligustrum ovalifolium Hassk., Lilaeopsis masonii Mathias & Constance, Lilaeopsis occidentalis J.M.Coult. & Rose, Lilium bolanderi S.Watson, Lilium columbianum Leichtlin, Lilium humboldtii Bull., 1871, Lilium kelleyanum Lemmon, Lilium kelloggii Purdy, Lilium maritimum Kellogg, Lilium occidentale Purdy, Lilium pardalinum Kellogg, Lilium parryi S.Watson, Lilium parvum Kellogg, Lilium rubescens S.Watson, Lilium washingtonianum Kellogg, Limnanthes alba Hartw. ex Benth., Limnanthes bakeri Howell, Limnanthes douglasii R.Br., Limnanthes floccosa Howell, Limnanthes montana Jeps., Limnanthes vinculans Ornduff, Limnobium spongia (Bosc) Steud., Limonium californicum (Boiss.) A.Heller, Limonium perezii (Stapf) F.T.Hubb. ex L.H.Bailey, Limonium sinuatum (L.) Mill., Limosella acaulis Sessé & Moc., Limosella aquatica L., Limosella australis R.Br., Linanthus arenicola (M.E.Jones) Jeps. & V.L.Bailey, Linanthus bellus (A.Gray) Greene, Linanthus bernardinus N.S.Fraga & D.S.Bell, Linanthus bigelovii (A.Gray) Greene, Linanthus concinnus Milliken, Linanthus demissus (A.Gray) Greene, Linanthus dianthiflorus (Benth.) Greene, Linanthus dichotomus Benth., Linanthus jonesii (A.Gray) Greene, Linanthus killipii H.Mason, Linanthus orcuttii (Parry & A.Gray) Jeps., Linanthus parryae (A.Gray) Greene, Linaria bipartita (Vent.) Willd., Linaria maroccana Hook.fil., Linaria pinifolia (Poir.) Thell., Linaria purpurea (L.) Mill., Linaria vulgaris Mill., Lindernia dubia (L.) Pennell, Linum bienne Mill., Linum grandiflorum Desf., Linum lewisii var. lewisii, Linum puberulum (Engelm.) Heller, Linum trigynum L., Linum usitatissimum L., Lithophragma affine A.Gray, Lithophragma bolanderi A.Gray, Lithophragma campanulatum Howell, Lithophragma cymbalaria Torr. & A.Gray, Lithophragma glabrum Nutt. ex Torr. & A.Gray, Lithophragma heterophyllum (Hook. & Arn.) Torr. & A.Gray, Lithophragma parviflorum (Hook.) Nutt. ex Torr. & A.Gray, Lithophragma parviflorum var. trifoliatum (Eastw.) Jeps., Lithospermum californicum A.Gray, Lithospermum incisum Lehm., Lithospermum ruderale Douglas ex Lehm., Lobelia erinus L., Lobularia maritima (L.) Desv., Loeflingia squarrosa Nutt. ex Torr. & A.Gray, Loeseliastrum matthewsii (A.Gray) Timbrook, Loeseliastrum schottii (Torr.) Timbrook, Logfia gallica (L.) Coss. & Germ., Lomatium austiniae (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium bicolor var. leptocarpum (Nutt. ex Torr. & A.Gray) Schlessman, Lomatium californicum (Nutt. ex Torr. & A.Gray) Mathias & Constance, Lomatium canbyi (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium caruifolium (Hook. & Arn.) J.M.Coult. & Rose, Lomatium caruifolium var. denticulatum (Jeps.) Jeps., Lomatium ciliolatum Jeps., Lomatium congdonii J.M.Coult. & Rose, Lomatium dasycarpum (Torr. & A.Gray) J.M.Coult. & Rose, Lomatium dissectum (Nutt. ex Torr. & A.Gray) Mathias & Constance, Lomatium engelmannii Mathias, Lomatium foeniculaceum (Nutt.) J.M.Coult. & Rose, Lomatium grayi (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium hallii (S.Watson) J.M.Coult. & Rose, Lomatium hendersonii (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium hooveri (Mathias & Constance) Constance & B.Ertter, Lomatium howellii (S.Watson) Jeps., Lomatium insulare (Eastw.) Munz, Lomatium lucidum (Nutt.) Jeps., Lomatium macrocarpum (Hook. & Arn.) J.M.Coult. & Rose, Lomatium marginatum (Benth.) J.M.Coult. & Rose, Lomatium marginatum var. purpureum Jeps., Lomatium martindalei (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium mohavense (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium nevadense (S.Watson) J.M.Coult. & Rose, Lomatium nevadense var. parishii (J.M.Coult. & Rose) Jeps., Lomatium nudicaule (Nutt.) J.M.Coult. & Rose, Lomatium observatorium Constance & B.Ertter, Lomatium parryi (S.Watson) J.F.Macbr., Lomatium parvifolium (Hook. & Arn.) Jeps., Lomatium peckianum Mathias & Constance, Lomatium piperi J.M.Coult. & Rose, Lomatium ravenii Mathias & Constance, Lomatium ravenii var. paiutense K.M.Carlson & Mansfield, Lomatium ravenii var. ravenii, Lomatium repostum (Jeps.) Mathias, Lomatium rigidum (M.E.Jones) Jeps., Lomatium shevockii R.L.Hartm. & Constance, Lomatium stebbinsii Schlessman & Constance, Lomatium torreyi (J.M.Coult. & Rose) J.M.Coult. & Rose, Lomatium tracyi Mathias & Constance, Lomatium triternatum (Pursh) J.M.Coult. & Rose, Lomatium triternatum var. macrocarpum (J.M.Coult. & Rose) Mathias, Lomatium utriculatum (Nutt. ex Torr. & A.Gray) J.M.Coult. & Rose, Lomatium vaginatum J.M.Coult. & Rose, Lonicera ciliosa (Pursh) Poir., Lonicera conjugialis Kellogg, Lonicera etrusca Santi, Lonicera hispidula (Lindl.) Douglas ex Lindl., Lonicera interrupta Benth., Lonicera involucrata (Richards.) Banks ex Spreng., Lonicera involucrata var. involucrata, Lonicera involucrata var. ledebourii (Eschsch.) Jeps., Lonicera japonica Thunb., Lonicera subspicata Hook. & Arn., Lonicera subspicata var. denudata Rehder, Lonicera tatarica L., Lotus angustissimus L., Lotus corniculatus L., Lotus tenuis Waldst. & Kit. ex Willd., Ludwigia grandiflora (Michx.) Greuter & Burdet, Ludwigia palustris (L.) Elliott, Ludwigia peploides (Kunth) P.H.Raven, Ludwigia repens J.R.Forst., Luetkea pectinata (Pursh) Kuntze, Luina hypoleuca Benth., Lunaria annua L., Lupinus adsurgens Drew, Lupinus affinis J.Agardh, Lupinus albicaulis Douglas, Lupinus albifrons Benth., Lupinus albifrons var. albifrons, Lupinus albifrons var. collinus Greene, Lupinus albifrons var. douglasii (J.Agardh) C.P.Sm., Lupinus andersonii S.Watson, Lupinus angustiflorus Eastw., Lupinus antoninus Eastw., Lupinus apertus A.Heller, Lupinus arboreus Sims, Lupinus arbustus Douglas, Lupinus argenteus Pursh, Lupinus argenteus subsp. argenteus, Lupinus argenteus var. argenteus, Lupinus arizonicus (S.Watson) S.Watson, Lupinus benthamii A.Heller, Lupinus bicolor Lindl., Lupinus brevicaulis S.Watson, Lupinus breweri A.Gray, Lupinus breweri var. breweri, Lupinus breweri var. bryoides C.P.Sm., Lupinus breweri var. grandiflorus C.P.Sm., Lupinus cervinus Kellogg, Lupinus chamissonis Eschsch., Lupinus citrinus Kellogg, Lupinus concinnus J.Agardh, Lupinus constancei T.W.Nelson & J.P.Nelson, Lupinus covillei Greene, Lupinus croceus Eastw., Lupinus dalesiae Eastw., Lupinus duranii Eastw., Lupinus elatus I.M.Johnst., Lupinus elmeri Greene, Lupinus excubitus M.E.Jones, Lupinus excubitus var. austromontanus C.P.Sm., Lupinus excubitus var. excubitus, Lupinus excubitus var. hallii (Abrams) C.P.Sm., Lupinus excubitus var. johnstonii C.P.Sm., Lupinus excubitus var. medius (Jeps.) Munz, Lupinus flavoculatus A.Heller, Lupinus formosus Greene, Lupinus formosus var. formosus, Lupinus formosus var. robustus C.P.Sm., Lupinus fulcratus Greene, Lupinus gracilentus Greene, Lupinus grayi S.Watson, Lupinus guadalupensis Greene, Lupinus hirsutissimus Benth., Lupinus holmgrenianus C.P.Sm., Lupinus hyacinthinus Greene, Lupinus lapidicola A.Heller, Lupinus latifolius Lindl. ex J.Agardh, Lupinus latifolius var. barbatus (L.F.Hend.) Munz, Lupinus latifolius subsp. viridifolius (A.Heller) Kenny & D.B.Dunn, Lupinus lepidus Douglas ex Lindl., Lupinus leucophyllus Douglas ex Lindl., Lupinus littoralis Douglas ex Lindl., Lupinus longifolius (S.Watson) Abrams, Lupinus ludovicianus Greene, Lupinus luteolus Kellogg, Lupinus magnificus M.E.Jones, Lupinus magnificus var. glarecola M.E.Jones, Lupinus magnificus var. magnificus, Lupinus nanus Douglas ex Benth., Lupinus nevadensis A.Heller, Lupinus nipomensis Eastw., Lupinus obtusilobus A.Heller, Lupinus odoratus A.Heller, Lupinus onustus S.Watson, Lupinus pachylobus Greene, Lupinus padre-crowleyi C.P.Sm., Lupinus peirsonii H.Mason, Lupinus polyphyllus Lindl., Lupinus polyphyllus var. pallidipes (A.Heller) C.P.Sm., Lupinus polyphyllus subsp. polyphyllus, Lupinus polyphyllus var. polyphyllus, Lupinus pratensis A.Heller, Lupinus pratensis var. eriostachyus C.P.Sm., Lupinus pratensis var. pratensis, Lupinus rivularis Douglas ex Lindl., Lupinus saxosus Howell, Lupinus sericatus Kellogg, Lupinus shockleyi S.Watson, Lupinus sparsiflorus Benth., Lupinus spectabilis Hoover, Lupinus stiversii Kellogg, Lupinus succulentus Douglas ex K.Koch, Lupinus tidestromii Greene, Lupinus tracyi Eastw., Lupinus truncatus Nutt. ex Hook. & Arn., Lupinus uncialis S.Watson, Luzula comosa E.Mey., Luzula comosa var. comosa, Luzula divaricata S.Watson, Luzula orestera Sharsm., Luzula parviflora (Ehrh.) Desv., Luzula piperi (Coville) M.E.Jones, Luzula spicata (L.) DC., Luzula subcongesta (S.Watson) Jeps., Lycium andersonii A.Gray, Lycium barbarum L., Lycium californicum Nutt. ex A.Gray, Lycium cooperi A.Gray, Lycium fremontii A.Gray, Lycium pallidum var. oligospermum C.L.Hitchc., Lycium parishii A.Gray, Lycium torreyi A.Gray, Lycopodiella inundata (L.) Holub, Lycopodium clavatum L., Lycopus americanus Muhl. ex W.P.C.Barton, Lycopus asper Greene, Lycopus uniflorus Michx., Lyrocarpa coulteri Hook. & Harv., Lysichiton americanus Hultén & H.St.John, Lysimachia nummularia L., Lysimachia thyrsiflora L., Lythrum californicum Torr. & A.Gray, Lythrum hyssopifolia L., Lythrum portula (L.) D.A.Webb, Lythrum salicaria L., Lythrum tribracteatum Spreng., Machaeranthera tanacetifolia (Kunth) Nees, Maclura pomifera (Raf. ex Sarg.) C.K.Schneid., Madia anomala Greene, Madia citrigracilis D.D.Keck, Madia citriodora Greene, Madia elegans D.Don, Madia exigua (Sm.) Greene, Madia glomerata Hook., Madia gracilis (Sm.) D.D.Keck & J.C.Clausen ex Applegate, Madia radiata Kellogg, Madia sativa Molina, Madia subspicata D.D.Keck, Maianthemum dilatatum (Alph.Wood) A.Nelson & J.F.Macbr., Maianthemum racemosum (L.) Link, Maianthemum stellatum (L.) Link, Malacothamnus abbottii (Eastw.) Kearney, Malacothamnus aboriginum (B.L.Rob.) Greene, Malacothamnus clementinus (Munz & I.M.Johnst.) Kearney, Malacothamnus davidsonii (B.L.Rob.) Greene, Malacothamnus densiflorus (S.Watson) Greene, Malacothamnus fasciculatus (Nutt. ex Torr. & A.Gray) Greene, Malacothamnus fremontii (A.Gray) Greene, Malacothamnus jonesii (Munz) Kearney, Malacothamnus marrubioides (Durand & Hilg.) Greene, Malacothamnus palmeri (S.Watson) Greene, Malacothrix californica DC., Malacothrix clevelandii A.Gray, Malacothrix coulteri Harv. & A.Gray ex A.Gray, Malacothrix floccifera (DC.) S.F.Blake, Malacothrix foliosa A.Gray ex Lyon, Malacothrix glabrata (D.C.Eaton ex A.Gray) A.Gray, Malacothrix incana (Nutt.) Torr. & A.Gray, Malacothrix indecora Greene, Malacothrix junakii W.S.Davis, Malacothrix phaeocarpa W.S.Davis, Malacothrix saxatilis (Nutt.) Torr. & A.Gray, Malacothrix saxatilis var. arachnoidea (E.A.Mc Gregor) E.W.Williams, Malacothrix saxatilis var. commutata (Torr. & A.Gray) Ferris, Malacothrix saxatilis var. implicata (Eastw.) H.M.Hall, Malacothrix saxatilis var. saxatilis, Malacothrix saxatilis var. tenuifolia (Nutt.) A.Gray, Malacothrix similis W.S.Davis & P.H.Raven, Malacothrix sonchoides (Nutt.) Torr. & A.Gray, Malacothrix squalida Greene, Malacothrix stebbinsii W.S.Davis & P.H.Raven, Malacothrix torreyi A.Gray, Malaxis monophyllos var. brachypoda (A.Gray) P.Morris & Eames, Malephora crocea (Jacq.) Schwantes, Malosma laurina (Nutt. ex Torr. & A.Gray) Engl., Malperia tenuis S.Watson, Malus pumila Kitam., Malva neglecta Wallr., Malva nicaeensis All., Malva parviflora L., Malva sylvestris L., Malvella leprosa (Ortega) Krapov., Mammillaria dioica K.Brandegee, Mammillaria grahamii subsp. grahamii, Mammillaria tetrancistra Engelm., Marah watsonii (Cogn.) Greene, Marina parryi (Torr. & A.Gray) Barneby, Marrubium vulgare L., Marsilea oligospora Goodd., Matelea parvifolia (Torr.) Woodson, Matricaria discoidea DC., Matricaria occidentalis Greene, Matthiola incana (L.) W.T.Aiton, Maurandella antirrhiniflora (Humb. & Bonpl. ex Willd.) Rothm., Meconella californica Torr. & Frém., Meconella denticulata Greene, Meconella oregana Nutt. ex Torr. & A.Gray, Medicago arabica (L.) Huds., Medicago lupulina L., Medicago minima (L.) Bartal., Medicago orbicularis (L.) Bartal., Medicago polymorpha L., Medicago praecox DC., Medicago sativa L., Melia azedarach L., Melica aristata Thurb. ex Bol., Melica bulbosa Porter & J.M.Coult., Melica californica Scribn., Melica frutescens Scribn., Melica fugax Bol., Melica geyeri Munro ex Bol., Melica harfordii Bol., Melica imperfecta Trin., Melica spectabilis Scribn., Melica stricta Bol., Melica subulata (Griseb.) Scribn., Melica torreyana Scribn., Melilotus indicus (L.) All., Melilotus officinalis (L.) Lam., Melissa officinalis L., Menodora scabra Engelm. ex A.Gray, Menodora spinescens A.Gray, Mentha aquatica L., Mentha arvensis L., Mentha canadensis L., Mentha pulegium L., Mentha spicata L., Mentha suaveolens Ehrh., Mentzelia affinis Greene, Mentzelia albicaulis (Douglas ex Hook.) Douglas ex Hook., Mentzelia congesta (Nutt.) Torr. & A.Gray, Mentzelia crocea Kellogg, Mentzelia desertorum (Davidson) H.J.Thomps. & J.E.Roberts, Mentzelia dispersa S.Watson, Mentzelia eremophila (Jeps.) H.J.Thomps. & J.E.Roberts, Mentzelia gracilenta (Nutt.) Torr. & A.Gray, Mentzelia hirsutissima S.Watson, Mentzelia involucrata S.Watson, Mentzelia inyoensis H.J.Thomps. & Prigge, Mentzelia jonesii (Urb. & Gilg) H.J.Thomps. & Roberts, Mentzelia laevicaulis (Douglas ex Hook.) Torr. & A.Gray, Mentzelia lindleyi Torr. & A.Gray, Mentzelia longiloba J.Darl., Mentzelia micrantha (Hook. & Arn.) Torr. & A.Gray, Mentzelia montana (A.Davidson) A.Davidson, Mentzelia nitens Greene, Mentzelia obscura H.J.Thomps. & J.E.Roberts, Mentzelia oreophila J.Darl., Mentzelia pectinata Kellogg, Mentzelia polita A.Nelson, Mentzelia pterosperma Eastw., Mentzelia reflexa Coville, Mentzelia torreyi A.Gray, Mentzelia tricuspis A.Gray, Mentzelia tridentata (Davidson) H.J.Thomps. & J.E.Roberts, Mentzelia veatchiana Kellogg, Menyanthes trifoliata L., Mercurialis annua L., Mertensia bella Piper, Mertensia ciliata var. stomatechoides (Kellogg) Jeps., Mertensia longiflora Greene, Mertensia oblongifolia (Nutt.) G.Don, Mesembryanthemum crystallinum L., Mesembryanthemum nodiflorum L., Micranthes aprica (Greene) Small, Micranthes bryophora (A.Gray) Brouillet & Gornall, Micranthes californica (Greene) Small, Micranthes ferruginea (Graham) Brouillet & Gornall, Micranthes fragosa (Suksd. ex Small) Small, Micranthes howellii (Greene) Small, Micranthes integrifolia (Hook.) Small, Micranthes marshallii (Greene) Small, Micranthes nidifica (Greene) Small, Micranthes odontoloma (Piper) A.Heller, Micranthes oregana (Howell) Small, Micranthes tolmiei (Torr. & A.Gray) Brouillet & Gornall, Microseris acuminata Greene, Microseris bigelovii (A.Gray) Sch.Bip., Microseris borealis (Bong.) Sch.Bip., Microseris campestris Greene, Microseris douglasii (DC.) Sch.Bip., Microseris elegans Greene ex A.Gray, Microseris laciniata (Hook.) Sch.Bip., Microseris nutans (Hook.) Sch.Bip., Microseris paludosa (Greene) Howell, Microseris sylvatica (Benth.) Sch.Bip., Mimetanthe pilosa (Benth.) Greene, Mimulus ringens L., Minuartia rubella Graebn., Mirabilis albida (Walter) Heimerl, Mirabilis alipes (S.Watson) Pilz, Mirabilis coccinea (Torr.) Benth. & Hook.fil., Mirabilis greenei S.Watson, Mirabilis laevis (Benth.) Curran, Mirabilis laevis var. villosa (Kellogg) Spellenb., Mirabilis linearis var. linearis, Mirabilis multiflora (Torr.) A.Gray, Mirabilis multiflora var. glandulosa (Standl.) J.F.Macbr., Mirabilis multiflora subsp. pubescens Munz, 1935, Mirabilis multiflora var. pubescens S.Watson, Mirabilis nyctaginea (Michx.) Mac Mill., Mirabilis tenuiloba S.Watson, Modiola caroliniana (L.) G.Don, Moehringia macrophylla (Hook.) Fenzl, Mohavea breviflora Coville, Mohavea confertiflora (Benth. ex A.DC.) A.Heller, Mollugo cerviana Linnaeus, 1753, Mollugo verticillata L., Moluccella laevis L., Monarda pectinata Nutt., Monardella australis Abrams, Monardella beneolens Shevock, Ertter & Jokerst, Monardella boydii A.C.Sanders & Elvin, Monardella breweri A.Gray, Monardella candicans Benth., Monardella douglasii Benth., Monardella eremicola A.C.Sanders & Elvin, Monardella exilis (A.Gray) Greene, Monardella follettii (Jeps.) Jokerst, Monardella hypoleuca A.Gray, Monardella leucocephala A.Gray, Monardella linoides A.Gray, Monardella macrantha A.Gray, Monardella nana A.Gray, Monardella odoratissima Benth., Monardella palmeri A.Gray, Monardella pringlei A.Gray, Monardella purpurea Howell, Monardella robisonii Epling ex Munz, Monardella sinuata Elvin & A.C.Sanders, Monardella stebbinsii Hardham & Bartel, Monardella stoneana Elvin & A.C.Sanders, Monardella undulata Benth., Monardella villosa Benth., Monardella viminea Greene, Monardella viridis Jeps., Moneses uniflora (L.) A.Gray, Monochoria vaginalis (Burm.f.) C.Presl, Monolopia gracilens A.Gray, Monolopia lanceolata Nutt., Monolopia major DC., Monolopia stricta Crum, Monoptilon bellidiforme Torr. & A.Gray ex A.Gray, Monoptilon bellioides (A.Gray) H.M.Hall, Monotropa uniflora L., Montia chamissoi (Ledeb. ex Spreng.) Greene, Montia dichotoma (Nutt.) J.T.Howell, Montia diffusa (Nutt.) Greene, Montia fontana L., Montia howellii S.Watson, Montia linearis (Douglas ex Hook.) Greene, Montia parvifolia (Moc. ex DC.) Greene, Morella californica (Cham. & Schltdl.) Wilbur, Mortonia utahensis (Coville ex A.Gray) J.Nelson, Morus alba L., Mucronea californica Benth., Mucronea perfoliata (A.Gray) A.Heller, Muehlenbeckia complexa (A.Cunn.) Meisn., Muhlenbergia andina (Nutt.) Hitchc., Muhlenbergia appressa Goodd., Muhlenbergia arsenei Hitchc., Muhlenbergia asperifolia (Nees & Meyen ex Trin.) Parodi, Muhlenbergia californica Vasey, Muhlenbergia filiformis (Thurb.) Rydb., Muhlenbergia fragilis Swallen, Muhlenbergia jonesii (Vasey) Hitchc., Muhlenbergia mexicana (L.) Trin., Muhlenbergia microsperma (DC.) Kunth, Muhlenbergia minutissima (Steud.) Swallen, Muhlenbergia montana (Nutt.) Hitchc., Muhlenbergia pauciflora Buckley, Muhlenbergia porteri Scribn., Muhlenbergia richardsonis (Trin.) Rydb., Muhlenbergia rigens (Benth.) Hitchc., Muhlenbergia schreberi J.F.Gmel., Muhlenbergia utilis (Torr.) Hitchc., Muilla coronata Greene, Muilla maritima (Torr.) S.Watson ex Benth., Muilla transmontana Greene, Munroa squarrosa (Nutt.) Torr., Myoporum laetum G.Forst., Myosotis discolor Pers., Myosotis latifolia Poir., Myosotis laxa Lehm., Myosotis scorpioides L., Myosotis verna Nutt., Myosurus apetalus Gay, Myosurus apetalus var. borealis Whittem., Myosurus apetalus var. montanus (G.R.Campb.) Whittem., Myosurus cupulatus S.Watson, Myosurus minimus L., Myosurus sessilis S.Watson, Myrica hartwegii S.Watson, Myriophyllum aquaticum (Vell.) Verdc., Myriophyllum hippuroides Nutt. ex Torr. & A.Gray, Myriophyllum quitense Kunth, Myriophyllum sibiricum Kom., Myriophyllum spicatum L., Myriophyllum verticillatum L., Najas flexilis (Willd.) Rostk. & W.L.E.Schmidt, Najas gracillima (A.Braun ex Engelm.) Magnus, Najas graminea Delile, Najas marina L., Nama aretioides (Hook. & Arn.) Brand, Nama demissa var. covillei Brand, Nama rothrockii A.Gray, Narcissus pseudonarcissus L., Narcissus tazetta L., Narthecium californicum Baker, Navarretia atractyloides (Benth.) Hook. & Arn., Navarretia breweri (A.Gray) Greene, Navarretia cotulifolia (Benth.) Hook. & Arn., Navarretia divaricata (Torr. ex A.Gray) Greene, Navarretia eriocephala H.Mason, Navarretia filicaulis (Torr.) Greene, Navarretia fossalis Moran, Navarretia gowenii L.A.Johnson, Navarretia hamata Greene, Navarretia heterandra H.Mason, Navarretia heterodoxa (Greene) Greene, Navarretia intertexta (Benth.) Hook., Navarretia jepsonii V.L.Bailey, Navarretia leucocephala Benth., Navarretia linearifolia (Howell) L.A.Johnson, Navarretia mellita (Greene) Greene, Navarretia myersii P.S.Allen & A.G.Day, Navarretia nigelliformis Greene, Navarretia ojaiensis Elvin, J.M.Porter & L.A.Johnson, Navarretia paradoxiclara L.A.Johnson & D.Gowen, Navarretia paradoxinota L.A.Johnson & D.Gowen, Navarretia peninsularis Greene, Navarretia prolifera Greene, Navarretia prostrata (A.Gray) Greene, Navarretia pubescens (Benth.) Hook. & Arn., Navarretia rosulata Brand, Navarretia setiloba Coville, Navarretia squarrosa (Eschsch.) Hook. & Arn., Navarretia subuligera Greene, Navarretia tagetina Greene, Navarretia viscidula Benth., Nemacaulis denudata var. gracilis Goodman & L.D.Benson, Nemacladus calcaratus Morin, Nemacladus capillaris Greene, Nemacladus glanduliferus Jeps., Nemacladus gracilis Eastw., Nemacladus interior (Munz) G.T.Robbins, Nemacladus longiflorus A.Gray, Nemacladus montanus Greene, Nemacladus pinnatifidus Greene, Nemacladus ramosissimus Nutt., Nemacladus rigidus Curran, Nemacladus rubescens Greene, Nemacladus secundiflorus G.T.Robbins, Nemacladus secundiflorus var. robbinsii Morin, Nemacladus secundiflorus var. secundiflorus, Nemacladus sigmoideus G.T.Robbins, Nemacladus twisselmannii J.T.Howell, Nemophila breviflora A.Gray, Nemophila heterophylla Fisch. & C.A.Mey., Nemophila maculata Benth. ex Lindl., Nemophila menziesii Hook. & Arn., Nemophila menziesii var. atomaria (Fisch. & C.A.Mey.) Voss, Nemophila menziesii var. integrifolia Brand, Nemophila parviflora Douglas ex Benth., Nemophila parviflora var. austiniae (Eastw.) Brand, Nemophila parviflora var. parviflora, Nemophila parviflora var. quercifolia (Eastw.) H.P.Chandler, Nemophila pedunculata Douglas ex Benth., Nemophila pulchella Eastw., Nemophila pulchella var. fremontii (Elmer) Constance, Nemophila pulchella var. gracilis (Eastw.) Constance, Nemophila spatulata Coville, Neostapfia colusana (Burtt Davy) Burtt Davy, Nepeta cataria L., Nerium oleander L., Nestotus stenophyllus (A.Gray) Urbatsch, R.P.Roberts & Neubig, Neviusia cliftonii Shevock, Ertter & D.W.Taylor, Nicandra physalodes (L.) Gaertn., Nicolletia occidentalis A.Gray, Nicotiana acuminata var. multiflora (Phil.) Reiche, Nicotiana attenuata Torr. ex S.Watson, Nicotiana clevelandii A.Gray, Nicotiana glauca Graham, Nicotiana quadrivalvis Pursh, Nicotiana sylvestris Speg., Nitrophila mohavensis Munz & J.C.Roos, Nitrophila occidentalis (Moq.) S.Watson, Noccaea fendleri (A.Gray) Holub, Nolina bigelovii (Torr.) S.Watson, Nolina cismontana Dice, Nolina interrata Gentry, Nolina parryi S.Watson, Nothochelone nemorosa (Douglas ex Lindl.) Straw, Notholaena californica D.C.Eaton, Nothoscordum gracile (Aiton) Stearn, Nuttallanthus texanus (Scheele) D.A.Sutton, Nymphaea mexicana Zucc., Nymphaea odorata Sol. ex Aiton, Nymphoides peltata (S.G.Gmel.) Kuntze, Odontostomum hartwegii Torr., Oemleria cerasiformis (Torr. & A.Gray ex Hook. & Arn.) J.W.Landon, Oenanthe sarmentosa C.Presl ex DC., Oenothera biennis L., Oenothera californica (S.Watson) S.Watson, Oenothera cavernae Munz, Oenothera deltoides Torr. & Frém., Oenothera elata Kunth, Oenothera flava (A.Nelson) Garrett, Oenothera glazioviana Micheli, Oenothera laciniata Hill, Oenothera longissima Rydb., Oenothera primiveris A.Gray, Oenothera pubescens Willd. ex Spreng., Oenothera rosea Aiton, Oenothera speciosa Nutt., Oenothera wolfii (Munz) P.H.Raven, W.Dietr. & W.Stubbe, Oenothera xylocarpa Coville, Olea europaea L., Oligomeris linifolia (Vahl ex Hornem.) J.F.Macbr., Olneya tesota A.Gray, Olsynium douglasii var. douglasii, Onobrychis viciifolia Scop., Onopordum illyricum L., Onopordum tauricum Willd., Ophioglossum californicum Prantl, Ophioglossum pusillum Raf., Opuntia basilaris Engelm. & J.M.Bigelow, Opuntia basilaris var. brachyclada (Griffiths) Munz, Opuntia basilaris var. treleasei (J.M.Coult.) J.M.Coult. ex Toumey, Opuntia chlorotica Engelm. & J.M.Bigelow, Opuntia engelmannii subsp. engelmannii, Opuntia ficus-indica (L.) Mill., Opuntia fragilis (Nutt.) Haw., Opuntia leucotricha DC., Opuntia littoralis (Engelm.) Cockerell, Opuntia oricola Philbrick, Opuntia phaeacantha Engelm., Opuntia polyacantha Haw., Orcuttia californica Vasey, Orcuttia inaequalis Hoover, Orcuttia pilosa Hoover, Orcuttia tenuis Hitchc., Orcuttia viscida (Hoover) Reeder, Oreonana clementis (M.E.Jones) Jeps., Oreonana purpurascens Shevock & Constance, Oreonana vestita (S.Watson) Jeps., Oreostemma alpigenum var. andersonii (A.Gray) G.L.Nesom, Oreostemma elatum (Greene) Greene, Oreostemma peirsonii (Sharsm.) G.L.Nesom, Ornithopus pinnatus (Mill.) Druce, Ornithopus sativus Brot., Ornithostaphylos oppositifolia (Parry) Small, Orochaenactis thysanocarpha (A.Gray) Coville, Orthilia secunda (L.) House, Orthocarpus bracteosus Benth., Orthocarpus cuspidatus Greene, Orthocarpus imbricatus Torr. ex S.Watson, Orthocarpus luteus Nutt., Orthocarpus pachystachyus A.Gray, Oryctes nevadensis S.Watson, Oryza sativa L., Osmadenia tenella Nutt., Osmorhiza berteroi DC., Osmorhiza brachypoda Torr. ex Durand, Osmorhiza depauperata Phil., Osmorhiza occidentalis (Nutt. ex Torr. & A.Gray) Torr., Osmorhiza purpurea (J.M.Coult. & Rose) Suksd., Ottelia alismoides (L.) Pers., Oxalis corniculata L., Oxalis incarnata L., Oxalis oregana Nutt. ex Torr. & A.Gray, Oxalis pes-caprae L., Oxalis purpurea L., Oxalis suksdorfii Trel., Oxalis trilliifolia Hook., Oxypolis occidentalis J.M.Coult. & Rose, Oxyria digyna (L.) Hill, Oxytheca perfoliata Torr. & A.Gray, Oxytheca watsonii Torr. & A.Gray, Oxytropis borealis DC., Oxytropis borealis var. australis S.L.Welsh, Oxytropis borealis var. viscida (Nutt.) S.L.Welsh, Oxytropis deflexa var. sericea Torr. & A.Gray, Oxytropis oreophila var. oreophila, Oxytropis parryi A.Gray, Packera bernardina (Greene) W.A.Weber & Á.Löve, Packera bolanderi var. bolanderi, Packera breweri (Burtt Davy) W.A.Weber & Á.Löve, Packera cana (Hook.) W.A.Weber & Á.Löve, Packera clevelandii (Greene) W.A.Weber & Á.Löve, Packera eurycephala (Torr. & A.Gray) W.A.Weber & Á.Löve, Packera eurycephala var. eurycephala, Packera eurycephala var. lewisrosei (J.T.Howell) J.F.Bain, Packera ganderi (T.M.Barkley & Beauch.) W.A.Weber & Á.Löve, Packera greenei (A.Gray) W.A.Weber & Á.Löve, Packera hesperia (Greene) W.A.Weber & Á.Löve, Packera indecora (Greenm.) Á.Löve & D.Löve, Packera ionophylla (Greene) W.A.Weber & Á.Löve, Packera layneae (Greene) W.A.Weber & Á.Löve, Packera macounii (Greene) W.A.Weber & Á.Löve, Packera multilobata (Torr. & A.Gray ex A.Gray) W.A.Weber & Á.Löve, Packera pauciflora (Pursh) Á.Löve & D.Löve, Packera pseudaurea subsp. pseudaurea, Packera pseudaurea var. pseudaurea, Packera werneriifolia (A.Gray) W.A.Weber & Á.Löve, Paeonia brownii Douglas, Paeonia californica Nutt. ex Torr. & A.Gray, Panicum antidotale Retz., Panicum capillare L., Panicum hillmanii Chase, Panicum urvilleanum Kunth, Papaver argemone L., Papaver californicum A.Gray, Papaver hybridum L., Papaver rhoeas L., Papaver somniferum L., Parapholis incurva (L.) C.E.Hubb., Parentucellia latifolia (L.) Caruel, Parentucellia viscosa Edwall, Parietaria hespera Hinton, Parietaria hespera var. californica Hinton, Parietaria judaica L., Parietaria pensylvanica Muhl. ex Willd., Parkinsonia aculeata L., Parkinsonia florida (Benth. ex A.Gray) S.Watson, Parkinsonia microphylla Torr., Parnassia cirrata Piper, Parnassia fimbriata Banks, Parnassia palustris L., Paronychia ahartii Ertter, Paronychia franciscana Eastw., Parthenium hysterophorus L., Paspalum dilatatum Poir., Paspalum distichum L., Paspalum urvillei Steud., Paspalum vaginatum Sw., Passiflora caerulea L., Pastinaca sativa L., Paxistima myrsinites (Pursh) Raf., Pectis papposa var. papposa, Pectocarya heterocarpa (I.M.Johnst.) I.M.Johnst., Pectocarya penicillata (Hook. & Arn.) A.DC., Pectocarya platycarpa (Munz & Johnst.) Munz & I.M.Johnst., Pectocarya pusilla (A.DC.) A.Gray, Pectocarya recurvata I.M.Johnst., Pectocarya setosa A.Gray, Pedicularis attollens A.Gray, Pedicularis bracteosa var. flavida (Pennell) Cronquist, Pedicularis centranthera A.Gray, Pedicularis contorta Benth., Pedicularis crenulata Benth., Pedicularis densiflora Benth., Pedicularis dudleyi Elmer, Pedicularis groenlandica Retz., Pedicularis howellii A.Gray, Pedicularis racemosa Douglas ex Hook., Pedicularis semibarbata A.Gray, Pediomelum californicum (S.Watson) Rydb., Pediomelum castoreum (S.Watson) Rydb., Peganum harmala L., Pelargonium capitatum (L.) L'Hér., Pelargonium grossularioides (L.) L'Hér., Pelargonium inquinans (L.) L'Hér., Pelargonium peltatum (L.) L'Hér., Pelargonium vitifolium (L.) L'Hér., Pelargonium zonale (L.) L'Hér., Pellaea andromedifolia (Kaulf.) Fée, Pellaea brachyptera (T.Moore) Baker, Pellaea breweri D.C.Eaton, Pellaea bridgesii Hook., Pellaea mucronata (D.C.Eaton) D.C.Eaton, Pellaea truncata Goodd., Peltandra virginica (L.) Schott, Penstemon albomarginatus M.E.Jones, Penstemon anguineus Eastw., Penstemon azureus Benth., Penstemon barnebyi N.H.Holmgren, Penstemon bicolor (Brandegee) Clokey & D.D.Keck, Penstemon caesius A.Gray, Penstemon calcareus Brandegee, Penstemon californicus (Munz & L M.Johnst.) D.D.Keck, Penstemon centranthifolius (Benth.) Benth., Penstemon cinicola D.D.Keck, Penstemon clevelandii A.Gray, Penstemon davidsonii var. davidsonii, Penstemon deustus Douglas, Penstemon deustus var. pedicellatus M.E.Jones, Penstemon eatonii A.Gray, Penstemon filiformis (D.D.Keck) D.D.Keck, Penstemon floridus Brandegee, Penstemon floridus var. austini (Eastw.) N.H.Holmgren, Penstemon fruticiformis Coville, Penstemon gracilentus A.Gray, Penstemon grinnellii Eastw., Penstemon heterodoxus A.Gray, Penstemon heterophyllus Lindl., Penstemon incertus Brandegee, Penstemon janishiae N.H.Holmgren, Penstemon labrosus (A.Gray) Mast. ex Hook.fil., Penstemon laetus A.Gray, Penstemon monoensis A.Heller, Penstemon neotericus D.D.Keck, Penstemon newberryi A.Gray, Penstemon pahutensis N.H.Holmgren, Penstemon papillatus J.T.Howell, Penstemon patens (M.E.Jones) N.H.Holmgren, Penstemon personatus D.D.Keck, Penstemon procerus Douglas ex Graham, Penstemon procerus var. brachyanthus (Pennell) Cronquist, Penstemon procerus var. formosus (A.Nelson) Cronquist, Penstemon pseudospectabilis M.E.Jones, Penstemon purpusii Brandegee, Penstemon rattanii A.Gray, Penstemon rostriflorus Kellogg, Penstemon rupicola (Piper) Howell, Penstemon rydbergii var. oreocharis (Greene) N.H.Holmgren, Penstemon scapoides D.D.Keck, Penstemon speciosus Douglas, Penstemon spectabilis Thurb. ex Torr. & A.Gray, Penstemon stephensii Brandegee, Penstemon sudans M.E.Jones, Penstemon thompsoniae (A.Gray) Rydb., Penstemon thurberi Torr., Penstemon tracyi D.D.Keck, Penstemon utahensis Eastw., Penstemon venustus Douglas, Pentachaeta alsinoides Greene, Pentachaeta aurea Nutt., Pentachaeta bellidiflora Greene, Pentachaeta exilis A.Gray, Pentachaeta fragilis Brandegee, Pentachaeta lyonii A.Gray, Pentagramma pallida (Weath.) Yatsk., Windham & Wollenw., Pentagramma triangularis (Kaulf.) Yatsk., Windham & Wollenw., Peraphyllum ramosissimum Nutt. ex Torr. & A.Gray, Pericome caudata A.Gray, Perideridia bacigalupii T.I.Chuang & Constance, Perideridia bolanderi (A.Gray) A.Nelson & J.F.Macbr., Perideridia californica (Torr.) A.Nelson & J.F.Macbr., Perideridia gairdneri (Hook. & Arn.) Mathias, Perideridia howellii (J.M.Coult. & Rose) Mathias, Perideridia kelloggii (A.Gray) Mathias, Perideridia lemmonii (J.M.Coult. & Rose) T.I.Chuang & Constance, Perideridia leptocarpa T.I.Chuang & Constance, Perideridia oregana (Nutt. ex Torr. & A.Gray) Mathias, Perideridia parishii (J.M.Coult. & Rose) A.Nelson & J.F.Macbr., Perideridia pringlei (J.M.Coult. & Rose) A.Nelson & J.F.Macbr., Perityle emoryi Torr., Perityle inyoensis (Ferris) A.M.Powell, Perityle megalocephala (S.Watson) J.F.Macbr., Perityle megalocephala var. megalocephala, Perityle megalocephala var. oligophylla A.M.Powell, Perityle villosa (S.F.Blake) Shinners, Persea americana Mill., Persicaria hydropiper (L.) Spach, Persicaria hydropiperoides (Michx.) Small, Persicaria maculosa Gray, Persicaria orientalis (L.) Spach, Petalonyx linearis Greene, Petalonyx nitidus S.Watson, Petalonyx thurberi A.Gray, Petasites frigidus var. palmatus (Aiton) Cronquist, Peteria thompsoniae S.Watson, Petrophytum caespitosum (Nutt.) Rydb., Petrorhagia dubia (Raf.) G.López & Romo, Petrorhagia nanteuilii (Burnat) P.W.Ball & Heywood, Petrorhagia prolifera (L.) P.W.Ball & Heywood, Petroselinum crispum (Mill.) Fuss, Peucephyllum schottii A.Gray, Phacelia adenophora J.T.Howell, Phacelia affinis A.Gray, Phacelia amabilis Constance, Phacelia anelsonii J.F.Macbr., Phacelia argentea A.Nelson & J.F.Macbr., Phacelia austromontana J.T.Howell, Phacelia barnebyana J.T.Howell, Phacelia bicolor Torr. ex S.Watson, Phacelia bolanderi A.Gray, Phacelia brachyloba (Benth.) A.Gray, Phacelia breweri A.Gray, Phacelia californica Cham., Phacelia calthifolia Brand, Phacelia campanularia A.Gray, Phacelia cicutaria Greene, Phacelia cicutaria var. hispida (A.Gray) J.T.Howell, Phacelia ciliata Benth., Phacelia coerulea Greene, Phacelia congdonii Greene, Phacelia cookei Constance & Heckard, Phacelia corymbosa Jeps., Phacelia crenulata Torr. ex S.Watson, Phacelia cryptantha Greene, Phacelia curvipes Torr. ex S.Watson, Phacelia davidsonii A.Gray, Phacelia distans Benth., Phacelia divaricata A.Gray, Phacelia douglasii (Benth.) Torr., Phacelia egena (Greene) J.T.Howell, Phacelia eisenii Brandegee, Phacelia exilis (A.Gray) G.J.Lee, Phacelia floribunda Greene, Phacelia fremontii Torr., Phacelia grandiflora (Benth.) A.Gray, Phacelia greenei J.T.Howell, Phacelia grisea A.Gray, Phacelia gymnoclada Torr. ex S.Watson, Phacelia hastata Douglas ex Lehm., Phacelia hastata var. compacta (Brand) Cronquist, Phacelia hastata var. hastata, Phacelia humilis Torr. & A.Gray, Phacelia humilis var. dudleyi J.T.Howell, Phacelia hydrophylloides Torr. ex A.Gray, Phacelia imbricata Greene, Phacelia insularis Munz, Phacelia insularis var. continentis J.T.Howell, Phacelia inundata J.T.Howell, Phacelia inyoensis (J.F.Macbr.) J.T.Howell, Phacelia ivesiana Torr., Phacelia lemmonii A.Gray, Phacelia leonis J.T.Howell, Phacelia linearis (Pursh) Holz., Phacelia longipes Torr. ex A.Gray, Phacelia lyonii A.Gray, Phacelia malvifolia Cham. & Schltdl., Phacelia marcescens Eastw. ex J.F.Macbr., Phacelia minor (Harv.) Thell., Phacelia mohavensis A.Gray, Phacelia monoensis Halse, Phacelia mustelina Coville, Phacelia mutabilis Greene, Phacelia nashiana Jeps., Phacelia neglecta M.E.Jones, Phacelia nemoralis Greene, Phacelia novenmillensis Munz, Phacelia orogenes Brand, Phacelia pachyphylla A.Gray, Phacelia parishii A.Gray, Phacelia parryi Torr., Phacelia pedicellata A.Gray, Phacelia peirsoniana J.T.Howell, Phacelia perityloides Coville, Phacelia phacelioides (Benth.) Brand, Phacelia platyloba A.Gray, Phacelia pringlei A.Gray, Phacelia procera A.Gray, Phacelia pulchella var. gooddingii (Brand) J.T.Howell, Phacelia purpusii Brandegee, Phacelia quickii J.T.Howell, Phacelia racemosa (Kellogg) A.Heller, Phacelia ramosissima Douglas ex Lehm., Phacelia rattanii A.Gray, Phacelia rotundifolia Torr. ex S.Watson, Phacelia saxicola A.Gray, Phacelia stebbinsii Constance & Heckard, Phacelia stellaris Brand, Phacelia suaveolens Greene, Phacelia tanacetifolia Benth., Phacelia tetramera J.T.Howell, Phacelia thermalis Greene, Phacelia umbrosa Greene, Phacelia vallicola Congdon ex Brand, Phacelia vallis-mortae J.W.Voss, Phacelia viscida (Benth. ex Lindl.) Torr., Phalacroseris bolanderi A.Gray, Phalaris angusta Nees ex Trin., Phalaris aquatica L., Phalaris arundinacea L., Phalaris brachystachys Link, Phalaris californica Hook. & Arn., Phalaris canariensis L., Phalaris caroliniana Walter, Phalaris lemmonii Vasey, Phalaris minor Retz., Phalaris paradoxa L., Phaseolus filiformis Benth., Philadelphus lewisii Pursh, Philadelphus microphyllus A.Gray, Phleum alpinum L., Phleum pratense L., Phlox adsurgens Torr. ex A.Gray, Phlox austromontana Coville, Phlox condensata (A.Gray) E.E.Nelson, Phlox diffusa Benth., Phlox dispersa Sharsm., Phlox dolichantha A.Gray, Phlox hirsuta E.E.Nelson, Phlox pulvinata (Wherry) Cronquist, Phlox speciosa Pursh, Phlox stansburyi (Torr.) A.Heller, Phoenicaulis cheiranthoides Nutt., Phoenix canariensis H.Wildpret, Phoenix dactylifera L., Pholisma arenarium Nutt., Pholisma sonorae (Torr. ex A.Gray) Yatsk., Pholistoma auritum (Lindl.) Lilja ex Lindl., Pholistoma auritum var. arizonicum (M.E.Jones) Constance, Pholistoma membranaceum (Benth.) Constance, Pholistoma racemosum (Nutt. ex A.Gray) Constance, Phoradendron bolleanum (Seem.) Eichler, Phoradendron californicum Nutt., Phoradendron juniperinum Engelm. ex A.Gray, Phoradendron leucarpum (Raf.) Reveal & M.C.Johnst., Phragmites australis (Cav.) Trin. ex Steud., Phyla lanceolata (Michx.) Greene, Phyla nodiflora (L.) Greene, Phyllodoce breweri (A.Gray) A.Heller, Phyllodoce empetriformis (Sm.) D.Don, Phyllospadix scouleri Hook., Phyllospadix torreyi S.Watson, Phyllostachys aurea (André) Rivière & C.Rivière, Physalis acutifolia (Miers) Sandwith, Physalis crassifolia Benth., Physalis hederifolia A.Gray, Physalis hederifolia var. fendleri (A.Gray) Cronquist, Physalis hederifolia var. palmeri (A.Gray) C.L.Hitchc., Physalis longifolia Nutt., Physalis philadelphica Lam., Physalis pubescens L., Physalis pubescens var. integrifolia (Dunal) Waterf., Physalis viscosa L., Physaria chambersii Rollins, Physaria kingii (S.Watson) O'Kane & Al-Shehbaz, Physocarpus alternans (M.E.Jones) J.T.Howell, Physocarpus capitatus (Pursh) Kuntze, Phytolacca americana var. americana, Picea breweriana S.Watson, Picea engelmannii Parry ex Engelm., Picea sitchensis (Bong.) Carrière, Pickeringia montana var. montana, Pickeringia montana var. tomentosa (Greene) I.M.Johnst., Pilostyles thurberi A.Gray, Pilularia americana A.Braun, Pinguicula macroceras Pall. ex Link, Pinus albicaulis Engelm., Pinus attenuata Lemmon, Pinus balfouriana Balf., Pinus contorta Douglas ex Loudon, Pinus coulteri D.Don, Pinus edulis Engelm., Pinus flexilis E.James, Pinus jeffreyi Balf., Pinus lambertiana Douglas, Pinus longaeva D.K.Bailey, Pinus monophylla Torr. & Frém., Pinus monticola Douglas ex D.Don, Pinus muricata D.Don, Pinus ponderosa Douglas ex C.Lawson, Pinus ponderosa var. ponderosa, Pinus quadrifolia Parl. ex Sudw., Pinus radiata D.Don, Pinus sabiniana Douglas ex D.Don, Pinus torreyana Parry ex Carrière, Pistacia atlantica Desf., Pistia stratiotes L., Pittosporum crassifolium Banks & Sol. ex A.Cunn., Pittosporum tobira (Murray) Aiton fil., Pittosporum undulatum Vent., Plagiobothrys acanthocarpus (Piper) I.M.Johnst., Plagiobothrys arizonicus (A.Gray) Greene ex A.Gray, Plagiobothrys austiniae (Greene) I.M.Johnst., Plagiobothrys bracteatus (J.T.Howell) I.M.Johnst., Plagiobothrys canescens Benth., Plagiobothrys canescens var. canescens, Plagiobothrys canescens var. catalinensis (A.Gray) Jeps., Plagiobothrys chorisianus (Cham.) I.M.Johnst., Plagiobothrys chorisianus var. hickmanii (Greene) I.M.Johnst., Plagiobothrys collinus (Phil.) I.M.Johnst., Plagiobothrys collinus var. californicus (A.Gray) L.C.Higgins, Plagiobothrys collinus var. fulvescens (I.M.Johnst.) L.C.Higgins, Plagiobothrys collinus var. gracilis (I.M.Johnst.) L.C.Higgins, Plagiobothrys collinus var. ursinus (A.Gray) L.C.Higgins, Plagiobothrys distantiflorus (Piper) I.M.Johnst., Plagiobothrys fulvus var. campestris (Greene) I.M.Johnst., Plagiobothrys glaber (A.Gray) I.M.Johnst., Plagiobothrys glyptocarpus (Piper) I.M.Johnst., Plagiobothrys glyptocarpus var. modestus I.M.Johnst., Plagiobothrys greenei (A.Gray) I.M.Johnst., Plagiobothrys humistratus (Greene) I.M.Johnst., Plagiobothrys hystriculus (Piper) I.M.Johnst., Plagiobothrys infectivus I.M.Johnst., Plagiobothrys leptocladus (Greene) I.M.Johnst., Plagiobothrys lithocaryus (Greene ex A.Gray) I.M.Johnst., Plagiobothrys mollis (A.Gray) I.M.Johnst., Plagiobothrys mollis var. vestitus (Greene) I.M.Johnst., Plagiobothrys nothofulvus (A.Gray) A.Gray, Plagiobothrys parishii I.M.Johnst., Plagiobothrys reticulatus (Piper) I.M.Johnst., Plagiobothrys salsus (Brandegee) I.M.Johnst., Plagiobothrys scriptus (Greene) I.M.Johnst., Plagiobothrys shastensis Greene ex A.Gray, Plagiobothrys stipitatus (Greene) I.M.Johnst., Plagiobothrys stipitatus var. micranthus (Piper) I.M.Johnst., Plagiobothrys strictus (Greene) I.M.Johnst., Plagiobothrys tenellus (Nutt. ex Hook.) A.Gray, Plagiobothrys tener (Greene) I.M.Johnst., Plagiobothrys tener var. subglaber I.M.Johnst., Plagiobothrys tener var. tener, Plagiobothrys torreyi (A.Gray) A.Gray, Plagiobothrys torreyi var. diffusus I.M.Johnst., Plagiobothrys trachycarpus (A.Gray) I.M.Johnst., Plagiobothrys uncinatus J.T.Howell, Plagiobothrys verrucosus (Phil.) I.M.Johnst., Plantago aristata Michx., Plantago coronopus L., Plantago elongata Pursh, Plantago erecta E.Morris, Plantago eriopoda Torr., Plantago lanceolata L., Plantago major L., Plantago maritima L., Plantago ovata Forssk., Plantago patagonica Jacq., Plantago pusilla Nutt., Plantago rhodosperma Decne., Plantago subnuda Pilg., Plantago virginica L., Platanthera dilatata var. leucostachys (Lindl.) Hultén, Platanthera sparsiflora (S.Watson) Schltr., Platanthera stricta Lindl., Platanthera tescamnis Sheviak & W.F.Jenn., Platanthera yosemitensis Colwell, Sheviak & P.E.Moore, Platanus racemosa Nutt. ex Audubon, Platystemon californicus Benth., Pleuricospora fimbriolata A.Gray, Pleurocoronis pluriseta (A.Gray) R.M.King & H.Rob., Pleuropogon hooverianus (G.T.Benson) Howell, Pleuropogon refractus (A.Gray) Benth. ex Vasey, Pluchea odorata var. odorata, Pluchea sericea (Nutt.) Coville, Plumbago auriculata Lam., Poa abbreviata R.Br., Poa annua L., Poa atropurpurea Scribn., Poa bigelovii Vasey ex Scribn., Poa bolanderi Vasey, Poa bulbosa L., Poa compressa L., Poa confinis Vasey, Poa cusickii Vasey, Poa diaboli Soreng & Keil, Poa douglasii Nees, Poa fendleriana (Steud.) Vasey, Poa howellii Vasey & Scribn., Poa infirma Kunth, Poa kelloggii Vasey, Poa lettermanii Vasey, Poa macrantha Vasey, Poa napensis Beetle, Poa nemoralis L., Poa palustris L., Poa pringlei Scribn., Poa rhizomata Hitchc., Poa secunda J.Presl, Poa sierrae J.T.Howell, Poa trivialis L., Poa wheeleri Vasey, Podistera nevadensis (A.Gray) S.Watson, Pogogyne abramsii J.T.Howell, Pogogyne clareana J.T.Howell, Pogogyne douglasii Benth., Pogogyne floribunda Jokerst, Pogogyne nudiuscula A.Gray, Pogogyne serpylloides (Torr.) A.Gray, Polemonium californicum Eastw., Polemonium carneum A.Gray, Polemonium chartaceum H.Mason, Polemonium eddyense Stubbs, Polemonium eximium Greene, Polemonium micranthum Benth., Polemonium occidentale Greene, Polemonium pulcherrimum Hook., Polemonium pulcherrimum var. shastense (Eastw.) Stubbs, Poliomintha incana (Torr.) A.Gray, Polyctenium fremontii (S.Watson) Greene, Polygonum aviculare L., Polygonum bidwelliae S.Watson, Polygonum bolanderi W.H.Brewer ex A.Gray, Polygonum californicum Meisn., Polygonum douglasii Greene, Polygonum hickmanii H.R.Hinds & Rand.Morgan, Polygonum marinense T.R.Mert. & P.H.Raven, Polygonum minimum S.Watson, Polygonum paronychia Cham. & Schltdl., Polygonum parryi Greene, Polygonum polygaloides Meisn., Polygonum ramosissimum Michx., Polygonum sawatchense Small, Polygonum shastense W.H.Brewer ex A.Gray, Polypodium californicum Kaulf., Polypodium calirhiza S.A.Whitmore & A.R.Sm., Polypodium glycyrrhiza D.C.Eaton, Polypodium hesperium Maxon, Polypodium scouleri Hook. & Grev., Polypogon australis Brongn., Polypogon interruptus Kunth, Polypogon maritimus Willd., Polypogon monspeliensis (L.) Desf., Polypogon viridis (Gouan) Breistr., Polystichum californicum (D.C.Eaton) Diels, Polystichum dudleyi Maxon, Polystichum imbricans (D.C.Eaton) D.H.Wagner, Polystichum kruckebergii W.H.Wagner, Polystichum lemmonii Underw., Polystichum lonchitis (L.) Roth, Polystichum munitum (Kaulf.) C.Presl, Polystichum scopulinum (D.C.Eaton) Maxon, Populus alba L., Populus angustifolia E.James, Populus nigra L., Populus tremuloides Michx., Porophyllum gracile Benth., Porterella carnosula (Hook. & Arn.) Torr., Portulaca halimoides L., Portulaca oleracea L., Potamogeton alpinus Balb., Potamogeton amplifolius Tuck., Potamogeton berchtoldii Fieber, Potamogeton crispus L., Potamogeton diversifolius Raf., Potamogeton epihydrus Raf., Potamogeton foliosus Raf., Potamogeton gramineus L., Potamogeton illinoensis Morong, Potamogeton natans L., Potamogeton nodosus Poir., Potamogeton praelongus Wulfen, Potamogeton pusillus L., Potamogeton richardsonii (A.Benn.) Rydb., Potamogeton robbinsii Oakes, Potamogeton zosteriformis Fernald, Potentilla anglica Laich., Potentilla anserina Jeps., Potentilla basaltica Tiehm & Ertter, Potentilla biennis Greene, Potentilla concinna var. proxima (Rydb.) S.L.Welsh & B.C.Johnst., Potentilla cristae Ferlatte & Strother, Potentilla drummondii Lehm., Potentilla flabellifolia Hook. ex Torr. & A.Gray, Potentilla gracilis Douglas, Potentilla gracilis var. fastigiata (Nutt.) S.Watson, Potentilla gracilis var. flabelliformis (Lehm.) Nutt., Potentilla grayi S.Watson, Potentilla hickmanii Eastw., Potentilla jepsonii Ertter, Potentilla millefolia Rydb., Potentilla morefieldii Ertter, Potentilla multijuga Lehm., Potentilla newberryi A.Gray, Potentilla norvegica L., Potentilla pensylvanica L., Potentilla pseudosericea Rydb., Potentilla pulcherrima Lehm., Potentilla recta L., Potentilla rimicola (Munz & I.M.Johnst.) Ertter, Potentilla rivalis Nutt. ex Torr. & A.Gray, Potentilla uliginosa B.C.Johnst. & Ertter, Potentilla wheeleri S.Watson, Poteridium annuum (Nutt. ex Hook.) Spach, Poterium sanguisorba L., Primula suffrutescens A.Gray, Proboscidea althaeifolia (Benth.) Decne., Prosartes hookeri Torr., Prosartes smithii (Hook.) Utech, Shinwari & Kawano, Prosopis glandulosa var. torreyana (L.D.Benson) M.C.Johnst., Prosopis pubescens Benth., Prosopis strombulifera (Lam.) Benth., Prosopis velutina Wooton, Prunus andersonii A.Gray, Prunus cerasifera Ehrh., Prunus dulcis (Mill.) D.A.Webb, Prunus emarginata (Douglas ex Hook.) Walp., Prunus eremophila Prigge, Prunus fasciculata (Torr.) A.Gray, Prunus fasciculata subsp. fasciculata, Prunus fasciculata subsp. punctata (Jeps.) A.E.Murray, Prunus fremontii S.Watson, Prunus ilicifolia (Nutt. ex Hook. & Arn.) D.Dietr., Prunus persica (L.) Stokes, Prunus subcordata Benth., Prunus virginiana var. demissa (Nutt.) Torr., Psathyrotes annua (Nutt.) A.Gray, Psathyrotes ramosissima (Torr.) A.Gray, Pseudobahia bahiifolia (Benth.) Rydb., Pseudobahia heermannii (Durand) Rydb., Pseudobahia peirsonii Munz, Pseudognaphalium californicum (DC.) Anderb., Pseudognaphalium canescens (DC.) Anderb., Pseudognaphalium leucocephalum (A.Gray) Anderb., Pseudognaphalium macounii (Greene) Kartesz, Pseudognaphalium ramosissimum (Nutt.) Anderb., Pseudognaphalium roseum (Kunth) Anderb., Pseudognaphalium stramineum (Kunth) Anderb., Pseudorontium cyathiferum (Benth.) Rothm., Pseudostellaria jamesiana (Torr.) W.A.Weber & R.L.Hartm., Pseudotrillium rivale (S.Watson) S.B.Farmer, Pseudotsuga macrocarpa (Vasey) Mayr, Pseudotsuga menziesii subsp. menziesii, Pseudotsuga menziesii var. menziesii, Psilocarphus brevissimus Nutt., Psilocarphus brevissimus var. brevissimus, Psilocarphus brevissimus var. multiflorus Cronquist, Psilocarphus elatior A.Gray, Psilocarphus oregonus Nutt., Psilocarphus tenellus Nutt., Psilostrophe cooperi (A.Gray) Greene, Psorothamnus arborescens (Torr. ex A.Gray) Barneby, Psorothamnus arborescens var. arborescens, Psorothamnus arborescens var. minutifolius (Parish) Barneby, Psorothamnus emoryi (A.Gray) Rydb., Psorothamnus fremontii (Torr. ex A.Gray) Barneby, Psorothamnus fremontii var. attenuatus Barneby, Psorothamnus fremontii var. fremontii, Psorothamnus polydenius (Torr.) Rydb., Psorothamnus schottii (Torr.) Barneby, Psorothamnus spinosus (A.Gray) Barneby, Ptelea crenulata Greene, Pteridium aquilinum subsp. pubescens (Underw.) J.A.Thomson, Mickel & Mehltr., Pteris cretica L., Pteris vittata L., Pterocarya stenoptera C.DC., Pterospora andromedea Nutt., Pterostegia drymarioides Fisch. & C.A.Mey., Puccinellia distans (Jacq.) Parl., Puccinellia howellii J.I.Davis, Puccinellia lemmonii (Vasey) Scribn., Puccinellia nutkaensis (J.Presl) Fernald & Weath., Puccinellia nuttalliana (Schult.) Hitchc., Puccinellia parishii Hitchc., Puccinellia pumila (Macoun ex Vasey) Hitchc., Puccinellia simplex Scribn., Pulicaria paludosa Steud., 1841, Punica granatum L., Purshia tridentata (Pursh) DC., Pycnanthemum californicum Torr. ex Durand, Pyracantha angustifolia (Franch.) C.K.Schneid., Pyracantha coccinea M.Roem., Pyracantha fortuneana (Maxim.) H.L.Li, Pyracantha koidzumii (Hayata) Rehder, Pyrola asarifolia Michx., Pyrola crypta Jolles, Pyrola minor L., Pyrola picta Sm., Pyrrocoma apargioides (A.Gray) Greene, Pyrrocoma carthamoides var. cusickii (A.Gray) Kartesz & Gandhi, Pyrrocoma hirta (A.Gray) Greene, Pyrrocoma hirta var. hirta, Pyrrocoma hirta var. lanulosa (Greene) Mayes ex G.K.Br. & D.J.Keil, Pyrrocoma lanceolata (Hook.) Greene, Pyrrocoma lanceolata var. lanceolata, Pyrrocoma lanceolata var. subviscosa (Greene) Mayes ex G.K.Br. & D.J.Keil, Pyrrocoma lucida (D.D.Keck) Kartesz & Gandhi, Pyrrocoma racemosa (Nutt.) Torr. & A.Gray, Pyrrocoma racemosa var. congesta (Greene) Mayes ex G.K.Br. & D.J.Keil, Pyrrocoma racemosa var. paniculata (Nutt.) Kartesz & Gandhi, Pyrrocoma racemosa var. pinetorum (D.D.Keck) Kartesz & Gandhi, Pyrrocoma racemosa var. racemosa, Pyrrocoma racemosa var. sessiliflora (Greene) Mayes ex G.K.Br. & D.J.Keil, Pyrrocoma uniflora (Hook.) Greene, Pyrrocoma uniflora var. gossypina (Greene) Kartesz & Gandhi, Pyrrocoma uniflora var. uniflora, Pyrus communis L., Quercus agrifolia Née, Quercus berberidifolia Liebm., Quercus cedrosensis C.H.Mull., Quercus chrysolepis Liebm., Quercus cornelius-mulleri Nixon & K.P.Steele, Quercus douglasii Hook. & Arn., Quercus dumosa Nutt., Quercus durata Jeps., Quercus durata var. durata, Quercus durata var. gabrielensis Nixon & C.H.Müll., Quercus engelmannii Greene, Quercus garryana Douglas ex Hook., Quercus garryana var. garryana, Quercus garryana var. semota Jeps., Quercus john-tuckeri Nixon & C.H.Müll., Quercus kelloggii Newb., Quercus lobata Née, Quercus pacifica Nixon & C.H.Müll., Quercus palmeri (Engelm.) Engelm., Quercus parvula Greene, Quercus parvula var. parvula, Quercus parvula var. shrevei (C.H.Mull.) Nixon, Quercus parvula var. tamalpaisensis S.K.Langer, Quercus robur L., Quercus sadleriana R.Br.ter, Quercus tomentella Engelm., Quercus turbinella Greene, Quercus vacciniifolia Kellogg, Quercus wislizeni A.DC., Quercus wislizeni var. frutescens Engelm., Quercus wislizeni var. wislizeni, Rafinesquia californica Nutt., Rafinesquia neomexicana A.Gray, Raillardella argentea (A.Gray) A.Gray, Raillardella pringlei Greene, Raillardella scaposa (A.Gray) A.Gray, Ranunculus acris L., Ranunculus alismifolius Geyer ex Benth., Ranunculus alismifolius var. alismellus A.Gray, Ranunculus alismifolius var. alismifolius, Ranunculus aquatilis L., Ranunculus arvensis L., Ranunculus bonariensis subsp. trisepalus (Gillies ex Hook. & Arn.) Molero, Ranunculus bulbosus L., Ranunculus californicus Benth., Ranunculus canus Benth., Ranunculus eschscholtzii Schltdl., Ranunculus eschscholtzii var. eschscholtzii, Ranunculus eschscholtzii var. oxynotus (A.Gray) Jeps., Ranunculus flabellaris Raf. ex Bigelow, Ranunculus flammula L., Ranunculus flammula f. flammula, Ranunculus flammula subsp. flammula, Ranunculus flammula var. flammula, Ranunculus glaberrimus Hook., Ranunculus glaberrimus var. ellipticus (Greene) Greene, Ranunculus glaberrimus var. glaberrimus, Ranunculus gormanii Greene, Ranunculus hebecarpus Hook. & Arn., Ranunculus hydrocharoides A.Gray, Ranunculus lobbii (Hiern) A.Gray, Ranunculus macounii Britton, Ranunculus muricatus L., Ranunculus occidentalis Nutt., Ranunculus occidentalis var. occidentalis, Ranunculus orthorhynchus Hook., Ranunculus orthorhynchus var. bloomeri (S.Watson) Benson, Ranunculus orthorhynchus var. orthorhynchus, Ranunculus parviflorus L., Ranunculus populago Greene, Ranunculus pusillus Poir., Ranunculus repens L., Ranunculus sardous Crantz, Ranunculus sceleratus L., Ranunculus sceleratus var. multifidus Nutt. ex Torr. & A.Gray, Ranunculus sceleratus subsp. sceleratus, Ranunculus sceleratus var. sceleratus, Ranunculus trilobus Desf., Ranunculus uncinatus D.Don ex G.Don, Raphanus raphanistrum L., Raphanus sativus L., Rapistrum rugosum (L.) All., Ratibida columnifera (Nutt.) Wooton & Standl., Reseda alba L., Reseda lutea L., Reseda luteola L., Reseda odorata L., Rhagadiolus stellatus (L.) Gaertn., Rhododendron macrophyllum D.Don ex G.Don, Rhododendron occidentale (Torr. & A.Gray) A.Gray, Rhus aromatica Aiton, Rhus integrifolia (Nutt.) Benth. & Hook.fil. ex Brewer & S.Watson, Rhus ovata S.Watson, Rhynchospora alba (L.) Vahl, Rhynchospora californica Gale, Rhynchospora capitellata (Michx.) Vahl, Rhynchospora globularis (Chapm.) Small, Ribes amarum Mc Clatchie, Ribes aureum Pursh, Ribes aureum var. aureum, Ribes aureum var. gracillimum (Coville & Britton) Jeps., Ribes binominatum A.Heller, Ribes bracteosum Douglas ex Hook., Ribes californicum Hook. & Arn., Ribes californicum subsp. californicum, Ribes californicum subsp. hesperium (Mc Clatchie) Thorne, Ribes canthariforme Wiggins, Ribes cereum Douglas, Ribes cereum var. cereum, Ribes divaricatum Douglas, Ribes divaricatum var. parishii (A.Heller) Jeps., Ribes divaricatum var. pubiflorum Koehne, Ribes hudsonianum var. petiolare (Douglas) Jancz., Ribes indecorum Eastw., Ribes inerme Rydb., Ribes inerme var. inerme, Ribes inerme var. klamathense (Coville) Jeps., Ribes lacustre (Pers.) Poir., Ribes lasianthum Greene, Ribes laxiflorum Pursh, Ribes lobbii A.Gray, Ribes malvaceum Sm., Ribes malvaceum var. viridifolium Abrams, Ribes marshallii Greene, Ribes menziesii Pursh, Ribes menziesii var. ixoderme Quick, Ribes montigenum Mc Clatchie, Ribes nevadense Kellogg, Ribes quercetorum Greene, Ribes roezlii Regel, Ribes roezlii var. amictum (Greene) Jeps., Ribes sanguineum Pursh, Ribes sanguineum var. glutinosum (Benth.) Loudon, Ribes sanguineum var. sanguineum, Ribes sericeum Eastw., Ribes speciosum Pursh, Ribes tularense (Coville) Standl., Ribes velutinum Greene, Ribes viburnifolium A.Gray, Ribes victoris Greene, Ribes viscosissimum Pursh, Ricinus communis L., Rigiopappus leptocladus A.Gray, Robinia neomexicana A.Gray, Robinia pseudoacacia L., Romanzoffia californica Greene, Romanzoffia sitchensis Bong., Romanzoffia tracyi Jeps., Romneya coulteri Harv., Romneya trichocalyx Eastw., Romulea rosea var. australis (Ewart) M.P.de Vos, Rorippa austriaca (Crantz) Besser, Rorippa columbiae (Suksd. ex B.L.Rob.) Suksd. ex Howell, Rorippa curvipes Greene, Rorippa curvisiliqua (Hook.) Bessey ex Britton, Rorippa palustris (L.) Besser, Rorippa sinuata (Nutt.) Hitchc., Rorippa sphaerocarpa (A.Gray) Britton, Rorippa subumbellata Rollins, Rorippa tenerrima Greene, Rosa bridgesii Crép. ex Rydb., Rosa californica Cham. & Schltdl., Rosa canina L., Rosa gymnocarpa Nutt. ex Torr. & A.Gray, Rosa gymnocarpa subsp. gymnocarpa, Rosa gymnocarpa var. gymnocarpa, Rosa gymnocarpa var. serpentina Ertter & W.H.Lewis, Rosa minutifolia Parry, Rosa multiflora Thunb., Rosa nutkana C.Presl, Rosa pinetorum A.Heller, Rosa pisocarpa A.Gray, Rosa rubiginosa L., Rosa spithamea A.Gray, Rosa woodsii Lindl., Rosa woodsii var. glabrata (Parish) D.Cole, Rosa woodsii subsp. gratissima (Greene) W.H.Lewis & Ertter, Rotala indica (Willd.) Koehne, Rotala ramosior (L.) Koehne, Rubus glaucifolius Kellogg, Rubus laciniatus Willd., Rubus lasiococcus A.Gray, Rubus leucodermis Douglas ex Hook., Rubus nivalis Douglas ex Hook., Rubus parviflorus Figert ex Sprib., Rubus ×pensilvanicus Poir., Rubus spectabilis Pursh, Rubus ulmifolius Schott, Rubus ursinus Cham. & Schltdl., Rudbeckia californica A.Gray, Rudbeckia hirta var. pulcherrima Farw., Rudbeckia occidentalis Nutt., Rumex acetosella L., Rumex conglomeratus Murray, Rumex crispus L., Rumex dentatus L., Rumex hymenosepalus Torr., Rumex kerneri Borbás, Rumex obtusifolius L., Rumex paucifolius Nutt., Rumex persicarioides L., Rumex pulcher L., Rumex salicifolius Weinm., Rumex stenophyllus Ledeb., Rumex triangulivalvis (Danser) Rech.fil., Rumex venosus Pursh, Rumex violascens Rech.fil., Rupertia hallii (Rydb.) J.W.Grimes, Rupertia physodes (Douglas) J.W.Grimes, Rupertia rigida (Parish) J.W.Grimes, Ruppia cirrhosa (Petagna) Grande, Ruppia maritima L., Ruta chalepensis L., Saccharum ravennae (L.) L., Sagina apetala Ard., Sagina procumbens L., Sagina saginoides (L.) Karst., Sagina subulata Hillebr., 1888, Sagittaria cuneata E.Sheld., Sagittaria latifolia Willd., Sagittaria longiloba Engelm. ex J.G.Sm., Sagittaria rigida Pursh, Sagittaria sanfordii Greene, Salicornia bigelovii Torr., Salicornia depressa Standl., Salicornia rubra A.Nelson, Salix alba L., Salix babylonica L., Salix bebbiana Sarg., Salix boothii Dorn, Salix brachycarpa var. brachycarpa, Salix breweri Bebb, Salix delnortensis C.K.Schneid., Salix drummondiana Barratt, Salix eastwoodiae Cockerell ex A.Heller, Salix geyeriana Andersson, Salix gooddingii C.R.Ball, Salix hookeriana Barratt, Salix jepsonii C.K.Schneid., Salix laevigata Bebb, Salix lasiolepis Benth., Salix lemmonii Bebb, Salix ligulifolia (C.R.Ball) C.R.Ball ex C.K.Schneid., Salix lutea Nutt., Salix melanopsis Nutt., Salix nivalis Hook., Salix orestera C.K.Schneid., Salix petrophila Rydb., Salix planifolia Pursh, Salix prolixa Andersson, Salix purpurea L., Salix scouleriana Barratt, Salix sitchensis Sanson ex Bong., Salix tracyi C.R.Ball, Salpichroa origanifolia (Lam.) Baill., Salsola soda L., Saltugilia australis (H.Mason & A.D.Grant) L.A.Johnson, Saltugilia latimeri T.L.Weese & L.A.Johnson, Salvia aethiopis L., Salvia apiana Jeps., Salvia brandegeei Munz, Salvia carduacea Benth., Salvia clevelandii (A.Gray) Greene, Salvia columbariae Benth., Salvia dorrii (Kellogg) Abrams, Salvia dorrii subsp. dorrii, Salvia dorrii var. incana (Benth.) Strachan, Salvia dorrii var. pilosa (A.Gray) Strachan & Reveal, Salvia eremostachya Jeps., Salvia funerea M.E.Jones, Salvia greatae Brandegee, Salvia leucophylla Greene, Salvia mellifera Greene, Salvia mohavensis Greene, Salvia munzii Epling, Salvia pachyphylla Epling ex Munz, Salvia sonomensis Greene, Salvia spathacea Greene, Salvia vaseyi (Porter) Parish, Salvia virgata Jacq., Salvinia minima Baker, Salvinia ×molesta D.S.Mitch., Sambucus racemosa L., Sambucus racemosa var. melanocarpa (A.Gray) Mc Minn, Sambucus racemosa f. racemosa, Sambucus racemosa subsp. racemosa, Sambucus racemosa var. racemosa, Sanguisorba officinalis L., Sanicula arctopoides Hook. & Arn., Sanicula arguta Greene ex J.M.Coult. & Rose, Sanicula bipinnata Hook. & Arn., Sanicula bipinnatifida Douglas, Sanicula crassicaulis Poepp. ex DC., Sanicula graveolens Poepp. ex DC., Sanicula hoffmannii (R.H.Shan & Constance) Bell, Sanicula laciniata Hook. & Arn., Sanicula maritima Kellogg ex S.Watson, Sanicula peckiana J.F.Macbr., Sanicula saxatilis Greene, Sanicula tracyi R.H.Shan & Constance, Sanicula tuberosa Torr., Santolina chamaecyparissus L., Sanvitalia abertii A.Gray, Saponaria officinalis L., Sarcobatus baileyi Coville, Sarcobatus vermiculatus (Hook.) Torr., Sarcodes sanguinea Torr., Sarracenia purpurea L., Saussurea americana D.C.Eaton, Saxifraga cespitosa L., Saxifraga hyperborea R.Br., Saxifraga mertensiana Bong., Saxifragopsis fragarioides (Greene) Small, Scandix pecten-veneris L., Scheuchzeria palustris L., Schinus molle L., Schismus arabicus Nees, Schismus barbatus (L.) Thell., Schoenoplectus acutus var. occidentalis (S.Watson) S.G.Sm., Schoenoplectus americanus (Pers.) Volkart, Schoenoplectus californicus (C.A.Mey.) Soják, Schoenoplectus heterochaetus (Chase) Soják, Schoenoplectus pungens var. longispicatus (Britton) S.G.Sm., Schoenoplectus subterminalis (Torr.) Soják, Schoenoplectus tabernaemontani (C.C.Gmel.) Palla, Schoenoplectus triqueter (L.) Palla, Schoenus nigricans L., Scirpus congdonii Britton, Scirpus cyperinus (L.) Kunth, Scirpus diffusus Schuyler, Scirpus microcarpus J.Presl & C.Presl, Scirpus pendulus Muhl., Sclerocactus polyancistrus (Engelm. & J.M.Bigelow) Britton & Rose, Sclerochloa dura (L.) P.Beauv., Sclerolinon digynum (A.Gray) C.M.Rogers, Scleropogon brevifolius Phil., Scoliopus bigelovii Torr., Scolymus hispanicus L., Scopulophila rixfordii (Brandegee) Munz & I.M.Johnst., Scribneria bolanderi (Thurb.) Hack., Scrophularia atrata Pennell, Scrophularia californica Cham. & Schltdl., Scrophularia desertorum (Munz) R.J.Shaw, Scrophularia lanceolata Pursh, Scrophularia villosa Pennell ex Millsp. & Nuttall, 1923, Scutellaria antirrhinoides Benth., Scutellaria bolanderi A.Gray, Scutellaria californica A.Gray, Scutellaria galericulata L., Scutellaria lateriflora L., Scutellaria nana A.Gray, Scutellaria tuberosa Benth., Searsia lancea (L.fil.) F.A.Barkley, Secale cereale L., Sedella leiocarpa Sharsm., Sedella pentandra Sharsm., Sedella pumila (Benth.) Britton & Rose, Sedum albomarginatum R.T.Clausen, Sedum album L., Sedum citrinum Zika, Sedum divergens S.Watson, Sedum lanceolatum Torr., Sedum laxum (Britton) A.Berger, Sedum niveum Davidson, Sedum oblanceolatum R.T.Clausen, Sedum obtusatum A.Gray, Sedum oreganum Nutt. ex Torr. & A.Gray, Sedum oregonense (S.Watson) M.Peck, Sedum praealtum A.DC., Sedum radiatum S.Watson, Sedum spathulifolium Hook., Sedum stenopetalum Pursh, Selaginella asprella Maxon, Selaginella bigelovii Underw., Selaginella cinerascens A.A.Eaton, Selaginella eremophila Maxon, Selaginella hansenii Hieron., Selaginella kraussiana (Kunze) A.Braun, Selaginella leucobryoides Maxon, Selaginella oregana D.C.Eaton, Selaginella wallacei Hieron., Selaginella watsonii Underw., Senecio aphanactis Greene, Senecio aronicoides DC., Senecio astephanus Greene, Senecio blochmaniae Greene, Senecio californicus DC., Senecio clarkianus A.Gray, Senecio elegans L., Senecio flaccidus Less., Senecio flaccidus var. douglasii (DC.) B.L.Turner & T.M.Barkley, Senecio flaccidus var. monoensis (Greene) B.L.Turner & T.M.Barkley, Senecio fremontii Torr. & A.Gray, Senecio hydrophiloides Rydb., Senecio hydrophilus Nutt., Senecio integerrimus Nutt., Senecio integerrimus var. exaltatus (Nutt.) Cronquist, Senecio integerrimus var. major (A.Gray) Cronquist, Senecio integerrimus var. ochroleucus (A.Gray) Cronquist, Senecio jacobaea Loscos & Pardo, Senecio lyonii A.Gray ex Lyon, Senecio mohavensis A.Gray, Senecio pattersonensis Hoover, Senecio scorzonella Greene, Senecio serra var. serra, Senecio spartioides Torr. & A.Gray, Senecio sylvaticus L., Senecio triangularis Hook., Senecio vulgaris L., Senna armata (S.Watson) H.S.Irwin & Barneby, Senna artemisioides (Gaudich. ex DC.) Randell, Senna covesii (A.Gray) H.S.Irwin & Barneby, Senna didymobotrya (Fresen.) H.S.Irwin & Barneby, Senna marilandica (L.) Link, Sequoia sempervirens (D.Don) Endl., Sequoiadendron giganteum (Lindl.) J.T.Buchholz, Sesbania punicea (Cav.) Benth., Sesuvium verrucosum Raf., Setaria faberi R.A.W.Herrm., Setaria parviflora (Poir.) Kerguélen, Setaria sphacelata (Schumach.) Stapf & C.E.Hubb. ex Moss, Setaria verticillata (L.) P.Beauv., Setaria viridis (L.) P.Beauv., Shepherdia argentea (Pursh) Nutt., Shepherdia canadensis (L.) Nutt., Sherardia arvensis L., Sibara deserti (M.E.Jones) Rollins, Sibara filifolia (Greene) Greene, Sibbaldia procumbens L., Sida rhombifolia L., Sida spinosa L., Sidalcea calycosa M.E.Jones, Sidalcea covillei Greene, Sidalcea diploscypha (Torr. & A.Gray) A.Gray ex Benth., Sidalcea gigantea G.Clifton, R.E.Buck & S.R.Hill, Sidalcea glaucescens Greene., Sidalcea hartwegii A.Gray ex Benth., Sidalcea hickmanii Greene, Sidalcea hirsuta A.Gray, Sidalcea keckii Wiggins, Sidalcea malachroides (Hook. & Arn.) A.Gray, Sidalcea malviflora (DC.) A.Gray ex Benth., Sidalcea multifida Greene, Sidalcea neomexicana A.Gray, Sidalcea oregana (Nutt. ex Torr. & A.Gray) Gray, Sidalcea pedata A.Gray, Sidalcea ranunculacea Greene, Sidalcea reptans Greene, Sidalcea robusta A.Heller, Sidalcea stipularis J.T.Howell & True, Silene antirrhina L., Silene aperta Greene, Silene bernardina S.Watson, Silene bridgesii Rohrb., Silene campanulata S.Watson, Silene conoidea L., Silene douglasii var. douglasii, Silene gallica L., Silene grayi S.Watson, Silene hookeri Nutt. ex Torr. & A.Gray, Silene invisa C.L.Hitchc. & Maguire, Silene laciniata Cav., Silene latifolia Poir., Silene lemmonii S.Watson, Silene marmorensis Kruckeb., Silene menziesii Hook., Silene noctiflora L., Silene nuda (S.Watson) C.L.Hitchc. & Maguire, Silene occidentalis S.Watson, Silene oregana S.Watson, Silene parishii S.Watson, Silene pendula L., Silene salmonacea T.W.Nelson, J.P.Nelson & S.A.Erwin, Silene sargentii S.Watson, Silene suksdorfii Rob., Silene verecunda S.Watson, Silene vulgaris (Moench) Garcke, Silybum marianum (L.) Gaertn., Simmondsia chinensis (Link) C.K.Schneid., Sinapis alba L., Sinapis arvensis L., Sisymbrium altissimum L., Sisymbrium irio L., Sisymbrium loeselii L., Sisymbrium officinale (L.) Scop., Sisymbrium orientale L., Sisyrinchium bellum S.Watson, Sisyrinchium californicum (Ker Gawl.) Dryand., Sisyrinchium elmeri Greene, Sisyrinchium funereum E.P.Bicknell, Sisyrinchium halophilum Greene, Sisyrinchium hitchcockii Douglass M.Hend., Sisyrinchium idahoense E.P.Bicknell, Sisyrinchium idahoense var. idahoense, Sisyrinchium idahoense var. occidentale (E.P.Bicknell) Douglass M.Hend., Sisyrinchium longipes (E.P.Bicknell) Kearney & Peebles, Sium suave Walter, Smelowskia ovalis M.E.Jones, Smilax californica (A.DC.) A.Gray, Smilax jamesii G.A.Wallace, Solanum americanum Mill., Solanum aviculare G.Forst., Solanum carolinense L., Solanum dimidiatum Raf., Solanum douglasii Dunal, Solanum dulcamara L., Solanum elaeagnifolium Cav., Solanum furcatum Dunal, Solanum lanceolatum Cav., Solanum marginatum L.fil., Solanum nigrum L., Solanum parishii A.Heller, Solanum sisymbriifolium Lam., Solanum triflorum Nutt., Solanum umbelliferum Eschsch., Soleirolia soleirolii (Req.) Dandy, Solidago confinis A.Gray, Solidago elongata Nutt., Solidago guiradonis A.Gray, Solidago lepida var. salebrosa (Piper) Semple, Solidago multiradiata Aiton, Solidago spectabilis (D.C.Eaton) A.Gray, Solidago velutina DC., Soliva sessilis Ruiz & Pav., Sonchus arvensis L., Sonchus oleraceus L., Sonchus tenerrimus L., Sorbus aucuparia L., Sorbus californica Greene, Sorbus scopulina Greene, Sorbus sitchensis M.Roem., Sorbus sitchensis var. grayi (Wenz.) C.L.Hitchc., Sorbus sitchensis var. sitchensis, Sorghum bicolor (L.) Moench, Sorghum halepense (L.) Pers., Sparaxis tricolor (Schneev.) Ker Gawl., Sparganium angustifolium Michx., Sparganium emersum Rehmann, Sparganium eurycarpum Engelm., Sparganium natans L., Spartium junceum L., Spergula arvensis L., Spergularia atrosperma R.Rossbach, Spergularia canadensis subsp. occidentalis (R.Rossbach) A.Haines, Spergularia macrotheca (Hornem. ex Cham. & Schltdl.) Heynh., Spergularia macrotheca var. leucantha (Greene) B.L.Rob., Spergularia macrotheca var. longistyla R.Rossbach, Spergularia macrotheca var. macrotheca, Spergularia media subsp. media, Spergularia rubra (L.) J.Presl & C.Presl, Spermolepis echinata (Nutt.) A.Heller, Sphaeralcea ambigua A.Gray, Sphaeralcea angustifolia (Cav.) G.Don, Sphaeralcea coulteri (S.Watson) A.Gray, Sphaeralcea grossulariifolia (Hook. & Arn.) Rydb., Sphaeralcea munroana (Douglas ex Lindl.) Spach, Sphaeralcea orcuttii Rose, Sphaerophysa salsula (Pall.) DC., Sphenopholis obtusata (Michx.) Scribn., Spiraea douglasii Hook., Spiraea splendens Baumann ex K.Koch, Spiranthes porrifolia Lindl., Spiranthes romanzoffiana Cham., Sporobolus airoides (Torr.) Torr., Sporobolus contractus Hitchc., Sporobolus cryptandrus (Torr.) A.Gray, Sporobolus flexuosus (Vasey) Rydb., Sporobolus indicus (L.) R.Br., Sporobolus vaginiflorus (Torr. ex A.Gray) Alph.Wood, Sporobolus wrightii Scribn., Stachys ajugoides Benth., Stachys albens A.Gray, Stachys bullata Benth., Stachys chamissonis Benth., Stachys mexicana Benth., Stachys pilosa Nutt., Stachys pycnantha Benth., Stachys rigida Nutt. ex Benth., Stachys stricta Greene, Stanleya elata M.E.Jones, Stanleya viridiflora Nutt., Staphylea bolanderi A.Gray, Stellaria calycantha (Ledeb.) Bong., Stellaria crispa Cham. & Schltdl., Stellaria graminea L., Stellaria littoralis Torr., Stellaria longifolia (Regel) Muhl. ex Willd., Stellaria media (L.) Vill., Stellaria nitens Nutt., Stellaria obtusa Engelm., Stellaria umbellata Turcz., Stemodia durantifolia (L.) Sw., Stenotaphrum secundatum (Walter) Kuntze, Stenotus acaulis (Nutt.) Nutt., Stephanomeria cichoriacea A.Gray, Stephanomeria diegensis Gottlieb, Stephanomeria elata Nutt., Stephanomeria exigua Nutt., Stephanomeria lactucina A.Gray, Stephanomeria paniculata Nutt., Stephanomeria parryi A.Gray, Stephanomeria pauciflora (Torr.) A.Nelson, Stephanomeria virgata Benth., Stillingia linearifolia S.Watson, Stillingia paucidentata S.Watson, Stillingia spinulosa Torr., Streptanthus barbatus S.Watson, Streptanthus barbiger Greene, Streptanthus batrachopus J.L.Morrison, Streptanthus bernardinus (Greene) Parish, Streptanthus brachiatus F.W.Hoffm., Streptanthus breweri A.Gray, Streptanthus callistus J.L.Morrison, Streptanthus campestris S.Watson, Streptanthus cordatus Nutt., Streptanthus cordatus var. cordatus, Streptanthus cordatus subsp. piutensis D.W.Taylor, Streptanthus cordatus var. piutensis J.T.Howell, Streptanthus diversifolius S.Watson, Streptanthus drepanoides Kruckeb. & J.L.Morrison, Streptanthus farnsworthianus J.T.Howell, Streptanthus fenestratus (Greene) J.T.Howell, Streptanthus glandulosus Hook., Streptanthus gracilis Eastw., Streptanthus hesperidis Jeps., Streptanthus hispidus A.Gray, Streptanthus howellii S.Watson, Streptanthus insignis Jeps., Streptanthus longisiliquus G.Clifton & R.Buck, Streptanthus morrisonii F.W.Hoffm., Streptanthus oblanceolatus T.W.Nelson & J.P.Nelson, Streptanthus oliganthus Rollins, Streptanthus polygaloides A.Gray, Streptanthus tortuosus Kellogg, Streptanthus vernalis R.O'Donnell & R.Dolan, Stuckenia pectinata (L.) Börner, Stuckenia striata (Ruiz & Pav.) Holub, Stylocline citroleum Morefield, Stylocline intertexta Morefield, Stylocline masonii Morefield, Stylocline micropoides A.Gray, Stylocline psilocarphoides M.Peck, Stylocline sonorensis Wiggins, Suaeda calceoliformis (Hook.) Moq., Suaeda californica S.Watson, Suaeda esteroa Ferren & S.A.Whitmore, Suaeda occidentalis (S.Watson) S.Watson, Suaeda taxifolia (Standl.) Standl., Swallenia alexandrae (Swallen) Soderstr. & H.F.Decker, Swertia perennis L., Syagrus romanzoffiana (Cham.) Glassman, Symphoricarpos albus var. laevigatus (Fernald) S.F.Blake, Symphoricarpos longiflorus A.Gray, Symphoricarpos mollis Nutt. ex Torr. & A.Gray, Symphoricarpos rotundifolius A.Gray, Symphoricarpos rotundifolius var. parishii (Rydb.) Dempster, Symphyotrichum ascendens (Lindl.) G.L.Nesom, Symphyotrichum campestre (Nutt.) G.L.Nesom, Symphyotrichum chilense (Nees) G.L.Nesom, Symphyotrichum defoliatum (Parish) G.L.Nesom, Symphyotrichum foliaceum (DC.) G.L.Nesom, Symphyotrichum foliaceum var. apricum (A.Gray) G.L.Nesom, Symphyotrichum foliaceum var. parryi (D.C.Eaton) G.L.Nesom, Symphyotrichum frondosum (Nutt.) G.L.Nesom, Symphyotrichum greatae (Parish) G.L.Nesom, Symphyotrichum hendersonii (Fernald) G.L.Nesom, Symphyotrichum lanceolatum var. hesperium (A.Gray) G.L.Nesom, Symphyotrichum lentum (Greene) G.L.Nesom, Symphyotrichum spathulatum (Lindl.) G.L.Nesom, Symphyotrichum spathulatum var. intermedium (A.Gray) G.L.Nesom, Symphyotrichum spathulatum var. spathulatum, Symphyotrichum spathulatum var. yosemitanum (A.Gray) G.L.Nesom, Symphyotrichum subspicatum (Nees) G.L.Nesom, Symphyotrichum subulatum (Michx.) G.L.Nesom, Symphytum officinale L., Synthyris reniformis Benth., Syntrichopappus fremontii A.Gray, Syntrichopappus lemmonii A.Gray, Systenotheca vortriedei (Brandegee) Reveal & C.B.Hardham, Tagetes erecta L., Tagetes minuta L., Tamarix aphylla (L.) H.Karst., Tamarix chinensis Lour., Tamarix gallica L., Tamarix parviflora DC., Tamarix ramosissima Ledeb., Tanacetum bipinnatum (L.) Sch.Bip., Tanacetum parthenium (L.) Sch.Bip., Tanacetum vulgare L., Taraxacum californicum Munz & I.M.Johnst., Taraxacum officinale Weber ex F.H.Wigg., Tauschia arguta (Torr. & A.Gray) J.F.Macbr., Tauschia glauca (J.M.Coult. & Rose) Mathias & Constance, Tauschia hartwegii (A.Gray) J.F.Macbr., Tauschia howellii (J.M.Coult. & Rose) J.F.Macbr., Tauschia kelloggii (A.Gray) J.F.Macbr., Tauschia parishii (J.M.Coult. & Rose) J.F.Macbr., Taxus brevifolia Nutt., Teesdalia coronopifolia (Bergeret ex Steud.) Thell., Teesdalia nudicaulis (L.) W.T.Aiton, Tellima grandiflora (Pursh) Douglas ex Lindl., Tetracoccus dioicus Parry, Tetracoccus ilicifolius Coville & Gilman, Tetradymia argyraea Munz & J.C.Roos, Tetradymia axillaris A.Nelson, Tetradymia canescens DC., Tetradymia comosa A.Gray, Tetradymia glabrata Torr. & A.Gray, Tetradymia spinosa Hook. & Arn., Tetradymia stenolepis Greene, Tetradymia tetrameres (S.F.Blake) Strother, Tetraneuris acaulis var. arizonica (Greene) K.F.Parker, Teucrium glandulosum Kellogg, Thalictrum alpinum L., Thalictrum fendleri Engelm. ex A.Gray, Thalictrum occidentale A.Gray, Thalictrum sparsiflorum Turcz. ex Fisch. & C.A.Mey., Thamnosma montana Torr. & Frém., Thelesperma megapotamicum (Spreng.) Herter, Thelypodium brachycarpum (Torr.) Torr., Thelypodium crispum Greene ex Payson, Thelypodium flexuosum B.L.Rob., Thelypodium integrifolium (Nutt.) Endl., Thelypodium laciniatum (Hook.) Endl., Thelypodium milleflorum A.Nelson, Thelypodium stenopetalum S.Watson, Thelypteris nevadensis (D.C.Eaton) Clute, Thermopsis californica S.Watson, Thermopsis californica var. argentata (Greene) C.J.Chen & B.L.Turner, Thermopsis californica var. californica, Thermopsis californica var. semota (Jeps.) C.J.Chen & B.L.Turner, Thermopsis gracilis Howell, Thermopsis macrophylla Hook. & Arn., Thermopsis robusta Howell, Thlaspi arvense L., Thuja plicata Donn ex D.Don, Thymophylla pentachaeta var. belenidium (DC.) Strother, Thysanocarpus conchuliferus Greene, Thysanocarpus curvipes Hook., Thysanocarpus laciniatus Nutt., Thysanocarpus radians Benth., Thysanocarpus rigidus (Munz) P.J.Alexander & Windham, Tiarella trifoliata var. trifoliata, Tiarella trifoliata var. unifoliata (Hook.) Kurtz, Tidestromia lanuginosa (Nutt.) Standl., Tiquilia canescens (DC.) A.T.Richardson, Tiquilia canescens var. pulchella (I.M.Johnst.) A.T.Richardson, Tiquilia nuttallii (Benth. ex Hook.) A.T.Richardson, Tiquilia palmeri (A.Gray) A.T.Richardson, Tiquilia plicata (Torr.) A.T.Richardson, Tolmiea diplomenziesii Judd, Soltis & P.S.Soltis, Tolpis barbata (L.) Gaertn., Tonella tenella (Benth.) Jeps., Tonestus lyallii (A.Gray) A.Nelson, Torilis arvensis (Huds.) Link, Torilis nodosa (L.) Gaertn., Torreya californica Torr., Torreyochloa erecta (Hitchc.) Church, Torreyochloa pallida var. pauciflora (J.Presl) J.I.Davis, Townsendia condensata Parry, Townsendia leptotes (A.Gray) Osterh., Townsendia scapigera Eaton, Toxicodendron diversilobum (Torr. & A.Gray) Greene, Tracyina rostrata S.F.Blake, Tradescantia fluminensis Vell., Tradescantia ohiensis Raf., Tragia ramosa Torr., Tragopogon dubius Scop., Tragopogon porrifolius L., Tragopogon pratensis L., Trautvetteria caroliniensis (Walter) Vail, Triadica sebifera (L.) Small, Trianthema portulacastrum L., Tribulus terrestris L., Tricardia watsonii Torr. ex S.Watson, Trichophorum pumilum (Vahl) Schinz & Thell., Trichoptilium incisum (A.Gray) A.Gray, Trichostema austromontanum H.F.Lewis, Trichostema lanatum Benth., Trichostema lanceolatum Benth., Trichostema laxum A.Gray, Trichostema micranthum A.Gray, Trichostema oblongum Benth., Trichostema ovatum Curran, Trichostema parishii Vasey, Trichostema rubisepalum Elmer, Trichostema ruygtii H.Lewis, Trichostema simulatum Jeps., Trifolium albopurpureum Torr. & A.Gray, Trifolium alexandrinum L., Trifolium amoenum Greene, Trifolium andersonii A.Gray, Trifolium angustifolium L., Trifolium arvense L., Trifolium aureum Pollich, Trifolium barbigerum Torr., Trifolium beckwithii W.H.Brewer ex S.Watson, Trifolium bifidum A.Gray, Trifolium bolanderi A.Gray, Trifolium breweri S.Watson, Trifolium buckwestiorum Isely, Trifolium campestre Schreb., Trifolium cernuum Brot., Trifolium ciliolatum Benth., Trifolium cyathiferum Lindl., Trifolium depauperatum Desv., Trifolium depauperatum var. depauperatum, Trifolium dichotomum Hook. & Arn., Trifolium dubium Sibth., Trifolium fragiferum L., Trifolium fucatum Lindl., Trifolium glomeratum L., Trifolium gracilentum Torr. & A.Gray, Trifolium hirtum All., Trifolium howellii S.Watson, Trifolium hybridum L., Trifolium incarnatum L., Trifolium jokerstii Vincent & Rand.Morgan, Trifolium lemmonii S.Watson, Trifolium longipes Nutt., Trifolium macraei Hook. & Arn., Trifolium macrocephalum (Pursh) Poir., Trifolium microcephalum Pursh, Trifolium microdon Hook. & Arn., Trifolium monanthum A.Gray, Trifolium obtusiflorum Hook., Trifolium oliganthum Steud., Trifolium polyodon Greene, Trifolium pratense L., Trifolium productum Greene, Trifolium repens L., Trifolium resupinatum L., Trifolium striatum L., Trifolium subterraneum L., Trifolium tomentosum L., Trifolium trichocalyx A.Heller, Trifolium variegatum Nutt., Trifolium vesiculosum Savi, Trifolium wormskioldii Lehm., Triglochin maritima L., Triglochin palustris L., Triglochin striata Ruiz & Pav., Trillium albidum J.D.Freeman, Trillium angustipetalum (Torr.) J.D.Freeman, Trillium chloropetalum (Torr.) Howell, Trillium ovatum Pursh, Triodanis perfoliata (L.) Nieuwl., Triphysaria eriantha (Benth.) T.I.Chuang & Heckard, Triphysaria floribunda (Benth.) T.I.Chuang & Heckard, Triphysaria micrantha (Greene ex A.Heller) T.I.Chuang & Heckard, Triphysaria pusilla (Benth.) T.I.Chuang & Heckard, Triphysaria versicolor Fisch. & C.A.Mey., Tripleurospermum inodorum (L.) Sch.-Bip, Tripterocalyx crux-maltae (Kellogg) Standl., Tripterocalyx micranthus (Torr.) Hook., Trisetum canescens Buckley, Trisetum cernuum Trin., Trisetum spicatum (L.) K.Richt., Triteleia bridgesii (S.Watson) Greene, Triteleia clementina Hoover, Triteleia crocea (Alph.Wood) Greene, Triteleia dudleyi Hoover, Triteleia grandiflora Lindl., Triteleia hendersonii Greene, Triteleia hyacinthina (Lindl.) Greene, Triteleia ixioides (Dryand. ex W.T.Aiton) Greene, Triteleia laxa Benth., Triteleia lugens Greene, Triteleia montana Hoover, Triteleia peduncularis Lindl., Triteleia piutensis Kentner & K.E.Steiner, Triticum aestivum L., Tropaeolum majus L., Tropidocarpum californicum (Al-Shehbaz) Al-Shehbaz, Tropidocarpum capparideum Greene, Tropidocarpum gracile Hook., Tsuga heterophylla (Raf.) Sarg., Tsuga mertensiana (Bong.) Carrière, Tuberaria guttata (L.) Fourr., Tuctoria greenei (Vasey) Reeder, Tuctoria mucronata (Crampton) Reeder, Typha angustifolia L., Typha domingensis Pers., Typha latifolia L., Ulex europaeus L., Ulmus americana L., Ulmus parvifolia Jacq., Ulmus pumila L., Umbellularia californica (Hook. & Arn.) Nutt., Urospermum picroides (L.) Scop. ex F.W.Schmidt, Urtica dioica L., Urtica urens L., Utricularia gibba L., Utricularia intermedia Hayne, Utricularia macrorhiza Leconte, Utricularia minor L., Utricularia ×ochroleuca R.W.Hartm., Utricularia subulata L., Vaccinium deliciosum Piper, Vaccinium membranaceum Douglas ex Hook., Vaccinium ovatum Pursh, Vaccinium parvifolium Sm., Vaccinium scoparium Leiberg, Vaccinium shastense J.K.Nelson & Lindstrand, Valeriana californica A.Heller, Valeriana occidentalis A.Heller, Valeriana sitchensis Bong., Valerianella carinata Loisel., Valerianella locusta (L.) Laterr., Vancouveria chrysantha Greene, Vancouveria hexandra (Hook.) C.Mooren & Decne., Vancouveria planipetala Calloni, Velezia rigida L., Venegasia carpesioides DC., Ventenata dubia (Leers) Coss. & Durieu, Veratrum californicum var. californicum, Veratrum fimbriatum A.Gray, Veratrum insolitum Jeps., Veratrum viride Aiton, Verbascum blattaria L., Verbascum speciosum Schrad., Verbascum thapsus L., Verbascum virgatum Stokes, Verbena bonariensis L., Verbena bracteata Cav. ex Lag. & Rodr., Verbena californica Moldenke, Verbena hastata L., Verbena lasiostachys Link, Verbena litoralis Kunth, Verbena menthifolia Benth., Verbena scabra Vahl, Verbesina dissita A.Gray, Veronica americana (Raf.) Schwein. ex Benth., Veronica anagallis-aquatica L., Veronica arvensis L., Veronica catenata Pennell, Veronica copelandii Eastw., Veronica cusickii A.Gray, Veronica persica Poir., Veronica scutellata L., Veronica triphyllos L., Veronica wormskjoldii Roem. & Schult., Viburnum ellipticum Hook., Viburnum opulus L., Vicia benghalensis L., Vicia cracca L., Vicia disperma DC., Vicia faba L., Vicia hassei S.Watson, Vicia hirsuta (L.) Gray, Vicia lathyroides L., Vicia lutea L., Vicia pannonica Crantz, Vicia sativa L., Vicia tetrasperma (L.) Schreb., Vicia villosa Roth, Vinca major L., Viola arvensis Murray, Viola bakeri Greene, Viola beckwithii Torr. & A.Gray, Viola cuneata S.Watson, Viola douglasii Steud., Viola glabella Nutt., Viola hallii A.Gray, Viola howellii A.Gray, Viola langsdorffii Fisch. ex DC., Viola lobata Benth., Viola macloskeyi F.E.Lloyd, Viola nephrophylla Greene, Viola ocellata Torr. & A.Gray, Viola odorata L., Viola palustris L., Viola pedunculata Torr. & A.Gray, Viola pinetorum Greene, Viola praemorsa Douglas, Viola purpurea Kellogg, Viola sempervirens Greene, Viola sheltonii Torr., Viola tomentosa M.S.Baker & J.C.Clausen, Viscum album L., Vitis californica Benth., Vitis rupestris Scheele, Vitis vinifera L., Washingtonia filifera (Rafarin) H.Wendl. ex de Bary, Washingtonia robusta H.Wendl., Watsonia meriana (L.) Mill., Whipplea modesta Torr., Wigandia urens (Ruiz & Pav.) Kunth, Wolffia arrhiza (L.) Horkel ex Wimm., Wolffia borealis (Engelm.) Landolt, Wolffia brasiliensis Wedd., Wolffia columbiana H.Karst., Wolffia globosa (Roxb.) Hartog & Plas, Wolffiella lingulata (Hegelm.) Hegelm., Wolffiella oblonga (Phil.) Hegelm., Woodwardia fimbriata J.E.Sm., Wyethia angustifolia (DC.) Nutt., Wyethia glabra A.Gray, Wyethia helenioides (DC.) Nutt., Wyethia longicaulis A.Gray, Wyethia mollis A.Gray, Wyethia ovata A.Gray, 1868, Xanthium spinosum L., Xanthium strumarium L., Xerophyllum tenax (Pursh) Nutt., Xylorhiza cognata (H.M.Hall) T.J.Watson, Xylorhiza orcuttii (Vasey & Rose) Greene, Xylorhiza tortifolia var. tortifolia, Yabea microcarpa (Hook. & Arn.) Koso-Pol., Yucca baccata var. baccata, Yucca brevifolia Engelm., Yucca schidigera Roezl ex Ortgies, Zannichellia palustris L., Zantedeschia aethiopica (L.) Spreng., Zostera japonica Asch. & Graebn., Zostera marina L., Zygophyllum fabago L.)" ] } The dataset includes 89313335 records from 3500 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0015616-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences